Strategic packaging mechanization with sensor technologies for non-destructive in-situ quality and safety assessment of ready-to-eat fresh-cut fruits and vegetables - Kashish Chopra; Satish Kumar; Atul Dhiman; Neha Gautam (Food Control, 2027)

Association of Serum Calcitonin with COPD Severity and Its Relationship with Hypertension and Smoking Exposure: A Cross-Sectional Study - Sonali Singh; Atul Kabra; Pradeep Goyal (Journal of Pharmaceutical Innovation, 2027)

Assessing the environmental impact and biological safety of Co/Cu co-doped ZnO nanoparticles: from dose-dependent phytotoxicity to selective cytotoxicity - Yassine Slimani; Huseyin Tombuloglu; Firdos A. Khan; Atul Thakur; Sultan Akhtar (Environmental Nanotechnology, Monitoring & Management, 2026)

Evidence of circulating BPIV-3 genotype A in cattle and buffaloes in Maharashtra, India and clinico-pathological insights - Atul Kudale; Bhupesh Kamdi; Ranjit Ingole; Ashok Kumar; Sudhakar Awandkar; Srikant Erra; Syed Ali (Molecular Biology Reports, 2026)

Quality-by-design Assisted Laboratory Scale Up of Artemisinin Nanoemulsion Augmented Drug Delivery, Cytotoxicity and Cellular Uptake in Leishmania donovani Parasite, a Causative Agent for Cutaneous Leishmaniasis - Atul Mourya; Madhulika Namdeo; Shristi Arya; Samiksha Thote; Soham Loharkar; Gopal Bajad; Soyal Sayyed; Radheyshyam Maurya; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

Tree-crop interaction in Oryza sativa-based riverine agroforestry systems of Chhattisgarh, Central India: implications for climate-smart farming and food security - K. K. Chandra; Arun Kumar Shukla; Atul Kumar Bhardwaj; Rajesh Kumar; Chowlani Manpoong; A. K. Singh; Rajdeep Chanda; Shri Kant Tripathi (Agroforestry Systems, 2026)

Metabolic repatterning of volatile organic compounds during viral infection in passion fruit - Atul Kumar Srivastava; Junmei Jiang; Jinxi Zhang; Muhammad Arif; Ali Kamran; Nuo Zhang; Akhil Kumar; Xiangyang Li; Xin Xie (Physiological and Molecular Plant Pathology, 2026)

Sustainable wastewater treatments and energy production utilizing microbial fuel cells: A detailed review on advanced technologies - Renuka Devi Ravi; Atul A. Sagade; Abhishek Saxena; Sarojini Devi Nagesh; Rekha Pachaiappan (Desalination, 2026)

Photoregulation and substrate synergy mediated biofortification of radish (Raphanus sativus L.) microgreens: A dual factor approach - Priyanka Rana; Priyanka Thakur; Satish Kumar; Atul Dhiman (Plant Science, 2026)

Quantifying drainage divide reorganization using geomorphic metrics in a thrust-controlled landscape: Evidence from the MBT zone, NW Uttarakhand Himalaya - Manik Lakherwal; Girish Ch Kothyari; Atul Kumar Patidar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Methane assisted low temperature isothermal thermochemical water splitting over Pt/CeO2 nanorods - Dhanaji R. Naikwadi; Esha Varma; Geeta P. Kharabe; Erdni D. Batyrev; Dragos C. Stoian; Atul Bansode (Chemical Engineering Journal, 2026)

Diosmin as a Multitarget Therapeutic for Hydrocephalus: Insights from Network Pharmacology, Docking, and MD Simulation - Davood Ahmad Sheergojree; Ajay Singh Kushwah; Atul Kabra; Hassan A. Madkhali; Mohd Nazam Ansari; Yassine Riadi (Journal of Pharmaceutical Innovation, 2026)

QbD-driven RP-HPLC Method Development and Validation for Simultaneous Estimation of Iguratimod and Methotrexate in a Lipid-based Formulation - Atul Pandurang Kumbhar; Om Prakash Ranjan (Journal of Pharmaceutical Innovation, 2026)

Integration of Non-Timber forest products (NTFPs) in agroforestry systems - Rajesh Kumar; Amit Dixit; K. K. Chandra; Atul Kumar Bhardwaj; Bhavana Dixit (Agroforestry Systems, 2026)

Antifouling using ultrasonic vibrations with piezoceramic actuators - Atul A. Gavade; Siu Chun Ho; Devendra Patil; Gangbing Song (Biofouling, 2026)

Biomass-derived SiO2/C-Anchored ZnO quantum dots for sustainable photocatalytic wastewater treatment - Hendrix Abdul Ajiz; Ade Sonya Suryandari; Ulfiana Ihda Afifa; Widiyastuti Widiyastuti; Heru Setyawan; Lailatul Qomariyah; Mar’atul Fauziyah (Nanotechnology for Environmental Engineering, 2026)

Identification and Characterisation of Super Susceptible Bread Wheat (Triticum aestivum L.) Landraces against Leaf Rust Pathogen (Puccinia triticina Eriks.) - Naman Raj; Ujjwal Kapoor; Ramesh Bhurta; Vrinda Batra; Subhash Bijarania; Niharika Mallick; M. G. Mallikarjuna; Vaibhav Kumar Singh; Atul Kumar; Om Prakash Gangwar; Pramod Prasad; Subhash Chander Bhardwaj; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

Cyclodextrin nanosponges enhance the oral pharmacokinetics and antiplatelet efficacy of prasugrel hydrochloride in Wistar rats - Atul Suryawanshi; Mukesh Ratnaparkhi; Rushikesh Shinde (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Montelukast Ameliorates Antimony-Induced Neurotoxicity Accompanied by Alterations in Oxidative Stress, Neuroinflammation, and Mitochondrial Function - Atul; Surbhi Gupta; Sachin Tyagi; Chhavi Panwar; Vishal Panwar; Prabhat Singh (Biological Trace Element Research, 2026)

Integrated in silico and in vivo approaches reveal naltrexone as a synergistic modulator of TLR4 and μ-opioid receptors restoring redox homeostasis via Nrf2/Keap-1/HO-1 and HIF-1α/VEGF pathways in COPD - Soni; Atul Srivastava; Pratikkumar Gaglani; Vandana Yadav; Vinita Pandey; Subhashini (Molecular and Cellular Biochemistry, 2026)

Volumetric analysis of a playa lake using SWOT data: An improved understanding of the inflows to Kati Thanda-Lake Eyre - Atul Kumar Rai; Timothy J. Cohen; Moshe Armon; Samuel K. Marx (Journal of Hydrology, 2026)

Assessing spatiotemporal changes in water-related ecosystem services using quickflow and baseflow indicators in a data-scarce Himalayan watershed - Atul Chauhan; Souvanic Roy; Abhinandita Kundu (Sustainable Water Resources Management, 2026)

Growth optimisation and physiological performance of red-bellied pacu, Piaractus brachypomus (Cuvier, 1818) in low-salinity culture systems - Pachiyamman Sakthivel Prathib; Debajit Sarma; Madhuri S. Pathak; Paramita Banerjee Sawant; Tincy Varghese; Madhurya Sharma; Surya Kanagaraju; Jakir Hussain; Atul Kumar Singh; Vanlaltlan Kima; G. Harini; Gokul S.; et al. (Fish Physiology and Biochemistry, 2026)

Silica based nanocarriers for combination immunotherapy targeting the tumor immune microenvironment - Shamim Shamim; Atul Pratap Singh; Himanchal Sharma; Smriti Gohri; Dhananjay Taumar; Vatan Chaudhary (Drug Delivery and Translational Research, 2026)

Evaluation of amplitude–duration parameters for rapid magnitude estimation in earthquake early warning systems - Atul Saini; Himanshu Mittal; Mohit Agrawal; Rajiv Kumar (Bulletin of Earthquake Engineering, 2026)

Bioinformatics based characterization and in silico expression profiling of the glutathione S-transferase gene family in spinach (Spinacia oleracea L.) - Shivani Tiwari; Shilpi Srivastava; Mahesh Basantani; Atul Bhargava (Vegetos, 2026)

GHG emissions and mitigation potential in decentralised composting supply chain: Insights from 517 residential sites across multiple cities - Atul Kumar; G. Venkatesh; Arun Kansal (Waste Management, 2026)

Baicalin as a multifunctional flavone glycoside: pharmacological mechanisms, ADME profile, and therapeutic potential - Alpana Kumari; Atul Kabra (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Impact of lycopene supplementation on oxidative balance, heat-shock proteins, and lipid profile in heat-stressed goat kids - Atul Kumar Verma; Gulab Chandra; Rakesh Kumar Singh; Devesh Kumar Yadav; Prem Sagar Maurya; Ahmad Fahim; Debashis Roy; Pratibha Singh; Priyanka Rani; Mala Singh (International Journal of Biometeorology, 2026)

Diagnosing Linearity Along the Carbon Cascade in Terrestrial Biosphere Models and Observations - Huanyuan Zhang‐Zheng; Vivek K. Arora; Peter Anthoni; Thomas A. M. Pugh; Atul K. Jain; Wenping Yuan; Yadvinder Malhi; Julia Nabel; Daniel S. Goll; Julia Pongratz; Benjamin Poulter; Anthony P. Walker; et al. (Global Change Biology, 2026)
Elevated carbon dioxide (eCO 2 ) acts as a fertiliser for photosynthesis, driving an increase in gross primary production (GPP). However, it is unclear how effectively increased GPP propagates along the ‘carbon (C) cascade’ to increase net primary production (NPP) and vegetation C stocks ( C veg ) in different plant compartments. Vegetation models were criticised for being overly sensitive to photosynthesis (source‐driven), neglecting sink‐driven processes which may attenuate (or amplify) changes in NPP and vegetation C stocks. Here, we introduce an analytical framework to diagnose linearity ( L ) as ratios of relative changes in linked fluxes and pools. We then apply this framework to 16 models of the TRENDY v11 ensemble and to observation‐based estimates of CO 2 sensitivities. We found widely varying global patterns in L across models. Six models showed a majority of grid cells with larger relative changes in NPP than in GPP ( L NPP:GPP > 1 for > 60% of gridcells), indicating increased vegetation carbon use efficiency under eCO 2 . Only three models had L NPP:GPP 60% of gridcells. Four models showed a majority of gridcells with larger relative changes in estimated steady‐state C veg than in NPP, while five models showed the opposite—in both cases with a large spread of L Cveg*:NPP across grid cells within models. Observations‐based analysis reveals median L Cveg*:NPP C veg , ( L Croot:Cveg > 1) while five models showed the opposite. Most field evidence shows L Croot:Cveg > 1. Widely differing distributions of L among models and links in the C cascade reveal a strong influence of nonlinear behaviour in individual models. However, due to the spread in L , across the whole models ensemble, L deviations from 1 were roughly balanced, leading to an overall linear behaviour of terrestrial C cycle representations in the multi‐model‐mean.

Association of Haematological and Biochemical Inflammatory Indices with Angiographic Severity of Coronary Artery Disease in Chronic Stable Angina - Kuldeep Kumar Gaur; Ankit Kumar Yadav; Sojit Tomo; Mayank Yadav; Atul Kaushik; Rahul Choudhary; Surender Deora (Indian Journal of Clinical Biochemistry, 2026)

Carbon sequestration by harvested wood products by direct inventory method: a case study - Shweta B. Kukreti; Atul Kumar; Anubhab Pradhan (Journal of the Indian Academy of Wood Science, 2026)

Growth responses and metabolic adaptations to sugar mill effluents in Terminalia arjuna - Priyanshi Singh; Aanchal Verma; Pratibha Bharti; Vijay Kumar; Atul Kumar Anand; Vineet Kumar Singh; Alka Kumari (Physiology and Molecular Biology of Plants, 2026)

Design and development of the multispectral sensor with CIE Tristimulus colorimetry and machine learning framework for organic/non-organic tomato classification - Tejashree A. Aher; A. D. Shaligram; Supriya S. Patil; Varsha Atul Shukre (Organic Agriculture, 2026)

Analysing the effect of bending process on microstructure of Grevillea robusta wood - Priyank Maithani; Kamal Mishra; Atul Kumar (Journal of the Indian Academy of Wood Science, 2026)

Correction: Microbial secretome-mediated nanotechnology: an antibacterial strategy for future - Raghvendra Pratap Singh; Atul Kumar Srivastava; Geetanjali Manchanda; Simpal Kumari; Alok Ramkesh Rai (Archives of Microbiology, 2026)

Minimal Adverse Effects of lpa1 and lpa2 Mutations on Seed Germination and Vigour in Low-Phytate Maize - Vinay Rojaria; Ashvinkumar Katral; Sudipta Basu; Rajkumar Uttamrao Zunjare; Govinda Rai Sarma; Vinay Bhatt; Atul Kumar; Ashwani Kumar; Gyanendra Singh; Firoz Hossain; Vignesh Muthusamy (Journal of Plant Growth Regulation, 2026)

Design and development of an optical setup to study light attenuation by suspended sediments in water - Prasanna Babanrao Khaire; Virendra N. Barai; Sachin B. Nandgude; Atul A. Atre; Mamta S. Patwardhan (Environmental Monitoring and Assessment, 2026)

Cyclodextrins: Synthesis, Pharmaceutical Applications, Drug Delivery Systems and Safety Perspectives - Aman Kumar; Ravi Raj Pal; Preeti Patel; Atul Jain; Nitin Sharma; Umesh Kumar Patil; Balak Das Kurmi (AAPS PharmSciTech, 2026)

Network pharmacology and computational insights into the therapeutic potential of natural inositol from Madhuca longifolia as a safer alternative to synthetic Methylinositol targeting GSK-3β in Alzheimer's disease - Noopur Khare; Atul Kumar; Tanvi Jain; Sachidanand Singh (Next Research, 2026)

Interfacial charge reconfiguration via fluorination in ZnIn2S4/F-gC3N4 for visible-light-driven detoxification of antibiotics and organic pollutants - Awanti S. Talmale; Saumya Meghwani; Diksha Mohod; Atul V. Wankhade (Journal of Water Process Engineering, 2026)

Transglutaminase-assisted development of millet-legume-based mock meat - Riya Joshi; Umesh C. Lohani; Navin Chandra Shahi; Ashok K. Verma; Atul Singh; Iqbal Hussain; Sanjay Kumar (Food and Humanity, 2026)

Regenerative and Stem Cell-Based Therapies for Arthritis: Harnessing Mesenchymal Stem Cells, Exosomes, and Bioengineered Scaffolds for Functional Joint Repair - Abhishek Sharma; Aman Kumar; Ravi Raj Pal; Preeti Patel; Atul Jain; Balak Das Kurmi (Stem Cell Reviews and Reports, 2026)

Seismic performance assessment of single and twin tunnels subjected to earthquake and rail loads - Avni Katariwala; Twinsy Palsanawala; Mohit Bhandari; Atul Desai (Bulletin of Earthquake Engineering, 2026)

Microbial secretome-mediated nanotechnology: an antibacterial strategy for future - Raghvendra Pratap Singh; Atul Kumar Srivastava; Geetanjali Manchanda; Simpal Kumari; Alok Ramkesh Rai (Archives of Microbiology, 2026)

Conditioned medium from 1-nitropyrene induced THP-1 foam cells promotes pro-tumorigenesis in lung epithelial cells - Ankita Bagde; Atul Katarkar; K. Krishnamurthi (Toxicology in Vitro, 2026)

Developing intensity prediction equations from ground-motion parameters in the northwestern Himalaya - Rajiv Kumar; Himanshu Mittal; Atul Saini; Rimpy Taya; Shanker Pal (Soil Dynamics and Earthquake Engineering, 2026)

Nano-pesticides in agroecosystems: Environmental fate, ecotoxicological impacts, and sustainable risk mitigation strategies - Lukman Ahamad; Sudeepta Pattanayak; Mohammad Danish; Guy Smagghe; Atul Kumar Srivastava; Sanwei Yang; Xin Xie (Pesticide Biochemistry and Physiology, 2026)

A practical duct design to improve the performance of Darrieus hydrokinetic turbine kept in river flows - S. Madhankumar; Atul Kumar Soti (Ocean Engineering, 2026)

Cambered blade effects on fixed-pitch and variable-pitch Darrieus hydrokinetic turbine performance - Dhanjita Medhi; Atul Kumar Soti (Ocean Engineering, 2026)

Rheological behavior of egg yolk: Processing impacts and applications in food systems - Yogesh Kumar; Atul Khalangre; Federico Drudi; Neeraj Ghanghas; Rajat Suhag (Journal of Food Engineering, 2026)

Synergistic synthesis of MnO2-Co3O4@Polypyrrole ternary nanocomposite for achieving superior energy storage performance and long-term stability - Shivam Shitole; Tajala Magray; Omkar Nalawade; Pradip Sarawade; Vishwanath Patil; Atul Chaskar (Chemical Engineering Journal, 2026)

Hydrodynamics Investigation of Electrodeionization Resin Bed for Improved Ultrapure Water Production - Pankaj D. Indurkar; Parthiv Dixit; Bhupendra K. Markam; Atul Maldhure; Vaibhav Kulshrestha (Water Conservation Science and Engineering, 2026)

Application of infrared thermography for identification of estrus in Sahiwal females (Bos indicus) - Atul Singh Rajput; Mukesh Bhakat; Tushar Kumar Mohanty; Rubina Kumari Baithalu; Sanjit Maity; Goutam Mondal; Asheq Ahmed Mir; Gayathri Sherly Lal; Manmohan Singh Rajput; Nadeem Shah (Tropical Animal Health and Production, 2026)

Estimation of location-specific precipitation using Deep Neural Networks - Bipin Kumar; Bhvisy Kumar Yadav; Soumyodeep Mukhopadhyay; Rakshit Rohan; Bhupendra Bahadur Singh; Rajib Chattopadhyay; Nagraju Chilukoti; Atul Kumar Sahai (Theoretical and Applied Climatology, 2026)

Deciphering Long-Term Variation of Aerosol Characteristics and Their Climatic Implication over the World’s Wettest Place: Mawsynram - Mamta Devi; Sumit Kumar Mishra; Kartika Pandey; Supreet Kaur; Anikender Kumar; Vijay Kumar Soni; Amarendra Singh; Atul Kumar Srivastva (Journal of the Indian Society of Remote Sensing, 2026)

Development and Optimization of Candesartan Cilexitil-Loaded Ethosomal Gel for Enhanced Delivery: Improving Transdermal Therapeutics Via Box‒Behnken Statistical Design - Abhishek Sharma; Mridul Modgil; Abdulaziz S. Saeedan; Sara A Aldossary; Atul Kabra (Journal of Pharmaceutical Innovation, 2026)

Targeted Lithium Delivery Via Nasal Gel: Improving Efficacy and Safety in Bipolar Disorder Therapy - Dhaval Bhavsar; Atul Phatak; Ujwala Desai (Journal of Pharmaceutical Innovation, 2026)

Molecular Perspective of GPNMB in the Progression of End-Stage Liver Disease - Ram Aasarey; Shyam Prakash; Kajal Yadav; Priyatma; Shahid Khan; Medha; Naval K. Vikram; Suneeta Meena; Atul Sharma; Shivam Pandey (Indian Journal of Clinical Biochemistry, 2026)

Effect of Early Use of Botulinum Toxin A on Goal Attainment in Post-Stroke Spasticity - Atul Patel; Jinming Zhang; Simon Page; Sarah Harding; Mathieu Beneteau; Alberto Esquenazi (Toxicon, 2026)

Enhancing Botulinum Toxin Delivery in Spasticity Care: A Time Motion and Workflow Analysis Using QI-Inspired Methods - Fatima Nadeem; Rajiv Reebye; Atul Patel; Stefano Carda (Toxicon, 2026)

Late Quaternary evolution of piedmont faults in the Darjeeling-Sikkim Himalaya, India - Atul Kumar Singh; Kimi K. Basumatary; Pankaj Kumar; Rajveer Sharma; Manoj Kumar Jaiswal (Quaternary International, 2026)

In silico retrieval of sulfiredoxin from Setaria italica, Panicum miliaceum, and Eleusine coracana: Sequence characterization, structural modeling, and protein–protein interaction analysis - Rahul Thakur; Arvind Gupta; Kanchan Rauthan; Deepti Dixit; Arzoo Choudhary; Ashutosh Kumar Pandey; Atul Krishna Dev; Saurabh Yadav (Plant Gene, 2026)

Dynamic stability of a moored barge with time-delayed feedback control under regular sea waves - Saikat Suvra Mondal; Ranjan Kumar Mitra; Atul Krishna Banik (Ocean Engineering, 2026)

Saturated steam-assisted texturized plant protein as a sustainable and physicochemically comparable alternative to boneless chicken breast - Kannan Vignesh; Dadasaheb Wadikar; Dev Kumar Yadav; Atul Kumar; Phani Kumar Garlapati; Johnsy George; Aisha Tabassum; R. Kumar (International Journal of Gastronomy and Food Science, 2026)

Exploration of genetic diversity and population structure in North Indian Aegle marmelos accessions using ISSR markers - Prince Minhas; Rajvinder Minhas; Atul Chamyal; Rakesh Kumar; Kanika Aggarwal; Rahul Kumar; Maneet Rana; Vikas Sharma (Ecological Genetics and Genomics, 2026)

Effect of dietary supplementation of 25-(OH) cholecalciferol on egg production and shell quality in extended laying cycle - Marappan Gopi; Venkata Hanumat Sastry Kochiganti; Arumbackam Vijayarangam Elangovan; Atul Purushottam Kolte; Vaibhav Bhagwan Awachat; Bagath Madiajagan; Corbon David; Jyotirmoy Ghosh; Ravikiran Gorti; Ippala Janardhan Reddy (Tropical Animal Health and Production, 2026)

Long-Term Assessment of Near-Surface Air Pollutants at Jaipur: Source Identifications and Their Association with Surface Meteorology - Akanksha Gupta; Atul Kumar Srivastava; Deewan Singh Bisht; Charu Jhamaria (Pure and Applied Geophysics, 2026)

Fisetin: a multitarget flavonol bridging oxidative stress, inflammation, aging, and cancer - Simerjeet Kaur Chahal; Atul Kabra; Abdulaziz S. Saeedan; Mohd Nazam Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Targeting NMDA receptors in pain management: therapeutic innovations through piracetam repurposing - Nidhi Dhama; Aadesh Kumar; Lakhan Singh; Sokindra Kumar; Shah Alam Khan; Neeraj Kumar Fuloria; Atul Partap Singh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Assessing neotectonic deformation and terrain evolution through geospatial morphometric techniques across the MBT zone, NW Himalaya - Jayshree Changmai; Atul Kumar Patidar; Girish Ch. Kothyari (Journal of Mountain Science, 2026)

Corrigendum to “Assessment of urban environment quality using analytical hierarchical process and multi-dimensional decomposition analysis for Mumbai metropolitan region, India”. [Adv. Space Res., 75/3 (2025) 2792–2809] - Rabin Chakrabortty; Atul Kumar; S. Rahman; Malay Pramanik; Ram Avtar; Harekrishna Manna; Mohamed Zhran (Advances in Space Research, 2026)

Spatiotemporal flood hazard mapping in Kolkata based on Sentinel-1 SAR observations - Abhinandita Kundu; Souvanic Roy; Atul Chauhan (Advances in Space Research, 2026)

In silico evaluation of natural opioid ligands interaction and their therapeutic prospects in neuroinflammation - Pratikkumar Gaglani; Shalini Sharma; Atul Srivastava; Vinita Pandey; Vandana Yadav; Soni; Subhashini (In Silico Pharmacology, 2026)

Managing sustainable agricultural supply chains in smart cities with IoT and blockchain - Saikat Samanta; Achyuth Sarkar; Jitendra Singh Yadav; Atul Srivastava; Vijay Shankar Sharma; Jagadish S. Kallimani; Siddhanta Kumar Singh (Environment, Development and Sustainability, 2026)

Exploring the potential cross-reactivity of allergenic proteins from Anacardium occidentale using in-silico approaches - Rashi Chugh; Yadvi Sandhir; Ranjit Singh Gujjar; Vikas Handa; Atul Kumar Upadhyay (Journal of Proteins and Proteomics, 2026)

Incorporation of a hypoplastic material model for sandy soils into a dynamic ALE formulation suitable for structures subjected to moving loads - Atul Anantheswar; Sebastian Ullmann; Ines Wollny; Sebastian Skatulla; Ivo Herle; Michael Kaliske (Transportation Geotechnics, 2026)

Landslide susceptibility assessment using AHP and RF techniques: Special reference to Kumaun lesser Himalaya, Uttarakhand, India - Achla Joshi; Girish Ch Kothyari; Atul Kumar Patidar; Khyati Gupta (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Additive-mediated controlled growth of printed perovskite for planar and heterostructure solar cells - Anjali Thakran; Yen-Yu Wang; Rohan Paste; Atul Dhage; Yu-Te Chen; Mario Hofmann; Yu-Jung Lu; Chung Hsin Lu; Shih- I. Lu; Yan-Duo Lin; Chih Wei Chu (Chemical Engineering Journal, 2026)

A sustainable approach for synthesizing Mo2C MXene to reduce the wastage of gallium for energy storage devices - Pramod Kumar; Ananya Bansal; Atul Pandey; Vipin Chawla; Neha Sardana; Ramesh Chandra (Chemical Engineering Journal, 2026)

Geohazard dynamics in Kumaon and Garhwal regions of Uttarakhand Himalayas: a critical review of trends and socio-environmental impacts - Jayshree Changmai; Atul Kumar Patidar; Girish Ch. Kothyari; C. M. Bhatt (Spatial Information Research, 2026)

Exploring myricetin: A comprehensive review of its pharmacological potential, formulation strategies, and clinical outlook - Amita Devi; Atul Kabra; Abdulaziz S. Saeedan; Mohd Nazam Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Urban flood risk criteria ranking of a coastal city along the Southeastern Arabian Sea using fuzzy Delphi method - Hudha Abdul Salam; Mahua Mukherjee; Brijesh Kumar Yadav; Atul Kumar (Natural Hazards, 2026)

Correction to: Ursolic Acid Emulgel Augmented Drug Delivery in Leishmania donovani, A Causative Agent for Cutaneous Leishmaniasis: In Vitro Characterization and Anti-Amastigote Activity - Spandana Gollapalli; Soyal Sayyed; Soham Loharkar; Atul Mourya; Gopal Bajad; Shristi Arya; Dinesh Kumar Chandanapalli; Pankaj Kumar Singh; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

Identification of HLA Variants Associated with Symptomatic and Asymptomatic COVID-19 Using a Machine Learning Approach - Atul Rawal; Zuben Sauna (The AAPS Journal, 2026)

Evaluating the IITM-CFSv2 extended-range daily rainfall hindcast skills for the seasonal Kharif rice yield estimation of Warangal district, using the DSSAT crop-growth model - Hemadri Bhusan Amat; Sathya Uma Lakshmi Kandasamy; Avijit Dey; Dillip Kumar Swain; Atul Kumar Sahai; Karumuri Ashok (Journal of Earth System Science, 2026)

Two-year real-world retrospective safety evaluation with onabotulinumtoxinA across multiple therapeutic indications: Findings from the SYNCHRONIZE study - Grace Forde; Kimberly Becker Ifantides; Angeli Mayadev; Atul T. Patel; Christopher Rhyne; Theodore Brown; Ritu Singh; Mariana Nelson; Ahunna Ukah; Simona Battucci; Benjamin M. Brucker (Toxicon, 2026)

Assessing the impact of climatic variability and anthropogenic pressures on wetland (Kanwar Lake, India): A multi-seasonal analysis using remote sensing and statistical approaches - Kumar Abhinay; Mahua Mukherjee; Subir Sen; Atul Kumar (Remote Sensing Applications: Society and Environment, 2026)

Synergistic antibiotic degradation via hydrothermally synthesized 2D Bi2WO6/Ti3C2Tx heterostructures - Atul Verma; Esakkinaveen Dhanaraman; Yi-Jing Zhang; Jesus Gonzalez-Julian; Cheng-Kang Chiang; Chuan-Pei Lee; Yen-Pei Fu (Journal of Water Process Engineering, 2026)

Tunable polypyrrole-coated cellulose aerogel via in situ polymerization for high-performance solar-powered water purification: Effects of porosity, photothermal conversion, and long-term stability - Atul A. Pawar; Hern Kim (Desalination, 2026)

Opportunities for hydrogen recovery from seawater electro-chlorination in desalination plants for sustainable energy transition: A perspective review - Felipe M. Galleguillos Madrid; Ayleen Collao; Susana Leiva-Guajardo; Galvarino Casanueva Yáñez; Víctor M. Jiménez-Arévalo; Alvaro Soliz; Atul Sagade (Desalination, 2026)

Black carbon aerosol characteristics over Gangotri glacier valley in North-Western Himalaya: Long-range transport and implications to radiative forcing - Abhishek Thakur; Chhavi P. Pandey; Aman Shrivas; Atul K. Srivastava; Pyar S. Negi (Atmospheric Environment, 2026)

Significant contribution of primary brown carbon to the light absorption at Delhi, India: An implication for incomplete oxidation - Atar Singh Pipal; Parminder Kaur; Atul Kumar Srivastava; Yu-Hsiang Cheng; Deewan Singh Bisht; Vivek Singh; Yi-Wen Chen; Kuan-Ting Liu (Atmospheric Pollution Research, 2026)

1-Methylcyclopropene for Quality Preservation of Apple (Malus domestica): A Complete Paradigm on Application Stage, Physiological Effects, and Induction of Ripening In Integration with Other Approaches - Priyanka Thakur; Atul Dhiman; Satish Kumar; Rajni Saini (Journal of Plant Growth Regulation, 2026)

Fabrication of a cellulose paper based rotating paper disc as sustainable extraction device for anesthetic drug analysis in postmortem blood - Rajeev Jain; Atul Bajaj; Sarah Alharthi; Mohammed Idris; Lateefa A. Al-Khateeb (Sustainable Chemistry and Pharmacy, 2025)

Microplastic contamination and health risk assessment in economically important freshwater fish (Labeo rohita and Channa punctatus) from the Pawna River, India - Amol Shivaji Mali; Shailesh Ghodake; Utkarsh Maheshwari; Kirti Zare; Atul Kolhe; Pravin Gorde; Mayur Jagtap; Sandip Nehe (Food Bioscience, 2025)

Number and characteristics of microplastics contamination in commercial red palm oils - Elfi Anis Saati; Roy Hendroko Setyobudi; Iswahyudi Iswahyudi; Rokhmatul Asiyah; Moh Taufiq; Miftha Churochman; Murtafi’atul Aula; Satriyo Krido Wahono; Arini Hidayati; Marchel Putra Garfansa; Fadjar Kurnia Hartati; Annisa Dwi Puspitarini; et al. (Food and Humanity, 2025)

Assessing the Effectiveness of Handpump-Attached Fluoride Removal Units in Rural India - Riya Yadav; Nidhi Sahu; Kirti Virwani; Neha Wachasunder; Atul Maldhure; Vilas Shinde; Gajanan Kanade; Pawan Labhasetwar (Water Conservation Science and Engineering, 2025)

SARS-CoV-2 accessory proteins ORF3a and ORF6 alter the miRNome of human lung epithelial cells - Apoorva; Atul Kumar; Sankha Shubhra Chakrabarti; Sunit Kumar Singh (Molecular Biology Reports, 2025)

Enhancing Bioavailability of Lumefantrine: Development, Characterization, and Anti-Plasmodial Activity of a Ternary Amorphous Solid Dispersion - Ajay Subbevarapu; Anjana Elsa Viju; Omkar Londhe; Sayalee Mane; Atul Kumbhar; Om Prakash Ranjan; Vinoth Rajendran; Swapnil Jayant Dengale (Journal of Pharmaceutical Innovation, 2025)

Ursolic Acid Emulgel Augmented Drug Delivery in Leishmania Donovani, A Causative Agent for Cutaneous Leishmaniasis: In Vitro Characterization and Anti-Amastigote Activity - Spandana Gollapalli; Soyal Sayyed; Soham Loharkar; Atul Mourya; Gopal Bajad; Shristi Arya; Dinesh Kumar Chandanapalli; Pankaj Kumar Singh; Jitender Madan (Journal of Pharmaceutical Innovation, 2025)

Regenerative Fruit Waste Upcycling: Transformational Approaches Upcycling Waste to Wealth for Socio-Economic and Environmental Sustainability - Anika Panwar; Satish Kumar; Vikas Kumar; Atul Dhiman; Priyanka Thakur (Circular Economy and Sustainability, 2025)

Seasonal diet of the smooth-coated otter (Lutrogale perspicillata) in traditional brackish-water agroecosystems of Goa, India - Stephen Jonah Dias; Neeha Sinai Borker; Ashish Kumar Yadav; Jonathan D’Costa; Atul Sinai Borker; Paresh C. Porob (Aquatic Ecology, 2025)
The diet of the smooth-coated otter (Lutrogale perspicillata) was assessed in a representative agro-ecosystem complex called “Khazan Lands”, situated within the human-dominated estuarine landscape of the Zuari River of Goa, India. This was achieved by analyzing undigested prey remains from 815 fecal (spraint) samples. Overall, fish dominated otter diet (Percentage Biomass, BIO% = 59%; Relative Frequency of Occurrence, RFO% = 49%), followed by shrimp (BIO% = 37%; RFO% = 42%) and crabs (BIO% = 3%; RFO% = 8%). Other prey groups, including insects, molluscs, amphibians, birds, and mammals, were present in minor quantities (BIO% = 200 mm) were consumed less frequently (seasonal RFO% = 13–19%). The composition of economically significant prey (fish, shrimp, and crabs) was high (RFO% = 97%), whereas that of economically insignificant prey (molluscs, birds, amphibians, insects, and mammals) was low (RFO% = 3%). Furthermore, the occurrence of high-value fish families was marginally higher (seasonal RFO% = 50–62%) than low-value families (seasonal RFO% = 38–50%). Our observations suggest an opportunistic feeding habit by the species and a considerable overlap between resources exploited by fisherfolk and L. perspicillata. This study highlights the adaptability of this species, and the importance of Khazans for otter populations in the unprotected, human-dominated estuarine landscapes of Goa, India.

Unlocking the potential of nanocellulose in biomedical innovations: A sustainable marvel - Murthy Chavali; Meenakshi Singh; Atul Srivastava; Manoj Kumar Enamala; Chandrasekhar Kuppam; Rosa Anna Nastro; Sahil Kapoor; Ritendra Mishra (Science of The Total Environment, 2025)

A comparative investigation of aggressive pathogenesis by guava root-knot nematode Meloidogyne enterolobii - K.P. Adhuna; Artha Kundu; Manoranjan Dash; Jyoti Yadav; Matiyar Rahaman Khan; Malkhan Singh Gujjar; Nisha Jaiswal; Atul Kumar; Pankaj; Vishal Singh Somvanshi (Physiological and Molecular Plant Pathology, 2025)

Micronization by supercritical fluid technologies for green encapsulation and stabilization of food bioactives: A comprehensive review of mechanisms and applications - Pravashi Katelia; Rajni Saini; Atul Dhiman (Food Bioscience, 2025)

Formononetin: pharmacological properties and therapeutic potential - Navneet Sharma; Atul Kabra (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Epidemiology of adolescent and young adult cancer and associated disparities in cancer pattern and care in India: findings from Varanasi’s population-based cancer registry, 2017–2019 - Divya Khanna; Rajesh Vishwakarma; Anand N. Sharma; Atul Budukh; Rahul K. Verma; Aman Riguvanshi; Fahad Mahmood; Pankaj Chaturvedi; Satyajit Pradhan (Cancer Causes & Control, 2025)
Introduction Adolescents and Young Adults (AYAs) aged 15–39 represent a unique oncology demographic due to their distinct developmental needs. However, there is limited data on cancer burden and care disparities among the Indian AYAs. This study examines the burden, pattern, and disparities among AYAs in Varanasi, Uttar Pradesh. Methods This study collected data from Varanasi's population-based cancer registry (PBCR) between 2017 and 2019. Data were analyzed for demographic, clinical, and cancer-related variables. Sex and site-specific crude, age-adjusted, and truncated rates for incidence and mortality per 100,000 population were calculated. Disparities in cancer pattern for age, sex, cancer site, and geographical region, sociodemographic and cancer care characteristics were assessed using standardized rate ratios and multivariable regression. Adjusted ratios with 95% confidence intervals were calculated. AAIR of the leading cancer site was compared with 24 Indian PBCRs from Cancer Incidence Five data and GLOBOCAN (2022) data. Results Of 6821 cancer patients, 1105 (16.2%) were AYAs. The truncated age-adjusted incidence rate (AAIR) was 21 per 100,000 population, with mouth (16.5%), breast (12.2%), and tongue (6.2%) cancers leading. Oral cancer was most common cancer in male AYAs, with truncated AAIR of 9.2 per 100,000, ranking third highest among Indian PBCRs. Females had higher risks of stomach, gallbladder, and thyroid cancers. AYAs were more likely to access diagnostic and definitive treatment but faced income and employment vulnerabilities when compared with adults aged ≥ 40 years. Conclusion This study highlights significant cancer burden and disparities among AYAs in Varanasi. Targeted screening, tobacco control policies, and region-specific interventions, especially social support schemes, are crucial to addressing these inequities and improving outcomes.

In silico approaches to identify therapeutic drug targets against COVID-19: a detailed review with a case study - Tanmayee Basu; Atul Kumar Upadhyay (In Silico Pharmacology, 2025)

Industry 4.0 solutions to address paradoxical effect of flexible work arrangements: tri-dimensional review and forward outlook - Ganesh Narkhede; Vishal Naranje; Vivek Deshpande; Atul Kulkarni; Vaishali Patil (Environment, Development and Sustainability, 2025)

Ligilactobacillus salivarius and Limosilactobacillus reuteri improve growth and intestinal health in broilers via modulating gut microbiota and immune response - Neha Chavan; Mahesh Gupta; Krushna Bibichand Bahiram; Jayant Pandurang Korde; Mukund Kadam; Atul Dhok; Sachin Kumar (Research in Veterinary Science, 2025)

Enhancing the photocatalytic nitrogen reduction reaction, acetaminophen degradation, and energy recovery in fuel cells via the heterojunction of B-doped g-C3N4/BiOBr - Esakkinaveen Dhanaraman; Antonysamy Soundarya Mary; Atul Verma; Palanichamy Murugan; Yen-Pei Fu (Journal of Environmental Chemical Engineering, 2025)

Paleoproterozoic to Cambro-Ordovician crustal evolution in the northern Indian margin: Evidence from whole-rock geochemical, zircon U–Pb, Hf and O isotope signatures in the granitoids of Arunachal Himalaya, Northeast India - Bidyananda Maibam; Waikhom Nongdon; Pankaj Kumar; Yoann Gréau; Jasper Berndt; Stephen Foley; Atul Kumar Singh; Deeksha Khandelwal (Gondwana Research, 2025)

Breaking the temperature barrier: Unveiling the potential of ceria nanorods for low temperature thermochemical water splitting - Dhanaji R.Naikwadi; Vaishnavi Ganesh; Hesham Sharaf; Michele Offidani; Stefania Albonetti; Nikolaos Dimitratos; Atul Bansode (Fuel, 2025)

Effect of convective drying temperature and tray load density on bioactive compounds, antioxidant properties, and functional quality of radish Sango microgreens - Mahendra Gunjal; Atul Khalangre; Mansuri M. Tosif; Jyoti Singh; Sawinder Kaur; Riaz Ullah; Prasad Rasane (Food Chemistry, 2025)

Fabrication of sodium alginate-hydroxypropyl methylcellulose based bioadhesive eutectogel of Eberconazole for improved anti-fungal activity - Jay Chachad; Shidhanto Dey; Atul Sherje; Pankaj Dangre; Maheshkumar R. Borkar (Carbohydrate Polymers, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

ML-Based Geophysical Well Log Prediction for Subsurface Energy Applications: A Stratified Analysis of Feature Sets and Model Performance - Atul Kumar Patidar; Sarthak Singh; Shubham Anand (Pure and Applied Geophysics, 2025)

Boosting the catalytic efficiency of UGT51 for efficient production of rare ginsenoside Rh2 - Mohamed Yassin Ali; Mohnad Abdalla; Ahmed F. Roumia; Mohamed A. Tammam; Mohamed Fawzy Ramadan; Mohmmed Abdelssalam Hassan Edrees; Atul Kabra; Daochen Zhu (Folia Microbiologica, 2025)

Predictive Value of Lymphocyte Based Indices to Determine Major Adverse Cardiovascular Events in Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention - Vivek Mohanty; Surender Deora; Atul Kaushik; Rahul Choudhary; Dharamveer Yadav; Kuldeep Singh (Indian Journal of Clinical Biochemistry, 2025)

Improved performance of Andrographis paniculata in litchi-based agroforestry systems - Aseem Khan; Yamini Sharma; Prem Prakash Sharma; Aman Deep Ranga; Ankita Bhatia; Devansh Dogra; Atul Gupta (Agroforestry Systems, 2025)

Degradation of metronidazole by heat-activated persulfate: mechanism, water matrix, ecotoxicity removal, and energy-efficiency analysis - Himani Arora; Atul Patel; Jemi Gandhi; Athul Krishna Makkoottathil; Halan Prakash (Environmental Science and Pollution Research, 2025)

Advancing sustainable food Packaging: Integrating machine learning, deep learning, and artificial intelligence - Jyoti; Atul K. Gupta; Ashok Kumar; Bhuvnesh Kumar (Trends in Food Science & Technology, 2025)

Genetic diversity analysis in Cordia dichotoma from Himalayan foothills and plains of north India using ISSR markers - Atul Chamyal; Navpreet Parmar; Shubham Chauhan; Nishant Chauhan; Rakesh Kumar; Pitamber Dutt Sharma; Vikas Sharma (Ecological Genetics and Genomics, 2025)

Protein carbonylation reveals the molecular basis of cryoinjury in buffalo spermatozoa - S.K. Bhure; D.S. Kumara Wodeyar; Atul Kumar Sharma; Abhishek Kumar; Ajay Kumar; Manish Mahawar; S.K. Ghosh; G. Taru Sharma (Cryobiology, 2025)

A novel THINC scheme-based CLSVOF method for axisymmetric two-phase flows - Orkodip Mookherjee; Shantanu Pramanik; Atul Sharma (Computer Physics Communications, 2025)

Continuous antisolvent crystallization of paracetamol with an in-line hydrodynamic cavitation device - Vidit Tiwari; Subhrajit Swain; Raj Wagh; Atul Bari; Vivek V. Ranade (Chemical Engineering Journal, 2025)

PiPho85, a cyclin-dependent kinase of Piriformospora indica rescue colonized maize plants grown under salt stress - Arun Kumar Kashyap; Paras Kumar; Aayushi Bajaj; Rupesh Aggarwal; Pawan Kumar Sharma; Pooja Panwar; Shubhankar Pandey; Vikas Yadav; Ralf Oelmuller; Meenakshi Dua; Atul Kumar Johri (World Journal of Microbiology and Biotechnology, 2025)

Optimising Processing Technologies for Coloured-Skinned Potato Wedges: Analysis of Bioactive Compounds, Structural Integrity, and Sensory Properties - Rajni Saini; Sukhpreet Kaur; Poonam Aggarwal; Satpal Sharma; Atul Dhiman (Potato Research, 2025)

Comparative Transcriptome Analysis of Potato (Solanum tuberosum L.) Tubers at Different Developmental Stages of the Cryopreserved Germplasm - Tanmayee Basu; Arshwinder Singh; Vanishree G; Virupaksh U. Patil; Jagesh Kumar Tiwari; Ranjit Singh Gujjar; Atul Kumar Upadhyay (Potato Research, 2025)

A self-channel attention-based chaotic atrous convolutional BiLSTM network to predict soil erosion - Atul Kumar Ramotra; Goldi Chandrapal Jarbais (Earth Science Informatics, 2025)

Pathological and molecular findings associated with BRSV in cattle and buffaloes with pulmonary disease - Bhupesh Kamdi; Ranjit Ingole; Atul Kudale; Ashok Kumar; Sunil Hajare; Sudhakar Awandkar; Nitin Kurkure (Brazilian Journal of Microbiology, 2025)

Assessing the role of regional characteristics in estimating the volume of glacial lakes in the upper Indus-Ganga-Brahmaputra basins, Hindu Kush Himalaya - Atul Kumar; Suraj Mal; Udo Schickhoff; Simon Allen; A.P. Dimri (Journal of Hydrology, 2025)

“Fault dynamics and paleoseismic evidence in the Darjeeling-Sikkim Himalayan foothills: A study of fault-controlled landscapes” - Chandreyee Chakrabarti Goswami; Petra Štěpančíková; Atul Singh; Manoj K. Jaiswal; Prasun Jana (Geomorphology, 2025)

Sex-specific Alterations in the mRNA Expression of Histone Deacetylases (HDACs) in the Rat Brain Following Prolonged Abstinence from Methamphetamine Self-administration - Michael T. McCoy; Atul P. Daiwile; Bruce Ladenheim; Jean Lud Cadet (Molecular Neurobiology, 2025)

Harvest of algal biomass with bioflocculants for biofuel with upstream and downstream processes: State-of-the-art towards sustainable alternative - Kajol Goria; Richa Kothari; Har Mohan Singh; Deepak Pathania; D. Buddhi; Atul Sharma; V. V. Tyagi (Energy, Ecology and Environment, 2025)

Brassicaceae microgreens: Pioneering sustainable solutions for functional benefits in modern diets and food security - Ajay Kumar; Anika Panwar; Satish Kumar; Vikas Kumar; Atul Dhiman; Vishant Sharma; Shweta Sharma (South African Journal of Botany, 2025)

A Terrestrial record of ∼3000 years of extreme floods from the Kaveri and adjacent river basins, Tamil Nadu, India - Mahadev; Diptimayee Behera; Pankaj Kumar; Manoj Kumar Jaiswal; Atul Kumar Singh (Quaternary International, 2025)

Component identification of solid biomass fuels using reflected light microscopy: Interlaboratory study 2 - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Menandro N. Acda; Tushar Adsul; Neža Malenšek Andolšek; Lorenzo Animali; Omid H. Ardakani; Telma Ataide; Demberelsuren Batbold; Mohd Younus Bhat; et al. (International Journal of Coal Geology, 2025)

Impact of green synthesized iron oxide nanoparticles from Rhododendron arboretum on wheat (Triticum aestivum): Evaluation of morpho-physiological, biochemical and yield attributes - Atul Singh; Tanuja Rawat; Oddem Govardhan; Chhavi Sharma; Pushpa Lohani; Anuj Kumar; Shabir Hassan; Hemant Singh; Sundip Kumar; Raju Ratan Yadav; Sneh Gautam (Biocatalysis and Agricultural Biotechnology, 2025)

Exploring the impact of Curvularia pathogens on medicinal and aromatic plants: insights into history, pathogenicity, and host–pathogen interactions - Atul Kumar Srivastava; Mehran Khan; Xiangyang Li; Pooja Misra; Ashish; Akhil Kumar; Entaj Tarafder; Xin Xie; Raghvendra Pratap Singh (World Journal of Microbiology and Biotechnology, 2025)

Reflectivity-Rain Rate Relationship for Orographic Rainfall at Mahabaleshwar Over the Indian Western Ghats - Amit Kumar; Atul Kumar Srivastava; Kaustav Chakravarty; Manoj Kumar Srivastava (Pure and Applied Geophysics, 2025)

Retraction Note: Durability studies on conventional concrete and slag-based geopolymer concrete in aggressive sulphate environment - Atul Garg; Parveen Jangra; Dhirendra Singhal; Thong M. Pham; Deepankar Kumar Ashish (Energy, Ecology and Environment, 2025)

Physical, optical and radiative attributes of atmospheric aerosols produced due to bonfire during the Holika festival - Bharat Ji Mehrotra; Arti Choudhary; Atul K. Srivastava; Sudhir Kumar Sharma; Manoj K. Srivastava (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Development and nutritional analysis of biscuits incorporating guava pomace and chickpea flour - Deepika Kohli; Atul Pal; Rajesh Kandari; Sanjay Kumar; Afzal Hussain; Shuchi Upadhyaya (Journal of Stored Products Research, 2025)

India’s Earthquake Early Warning Systems: A Review of Developments and Challenges - Himanshu Mittal; Shanker Pal; Rajiv Kumar; Atul Saini; Yih-Min Wu; Ambikapathy Ammani; R. C. Patel; Sandeep; O. P. Mishra (Surveys in Geophysics, 2025)

Unveiling the Genetic Dynamics of Heat Stress Responses in Wheat RILs for Identifying Heat-Tolerant Genotypes - Mandeep Redhu; Vikram Singh; Somveer Nimbal; Ram Niwas; Atul Loyal; Chetan Singh; Mehdi Rahimi (Plant Molecular Biology Reporter, 2025)

Management of cyanobacteria and cyanotoxins in drinking water: A comprehensive review on occurrence, toxicity, challenges and treatment approaches - Nidhi Sahu; Atul Maldhure; Pawan Labhasetwar (Science of The Total Environment, 2025)

Process optimization for microgreens-based dairy (lassi) beverage: Consumer acceptability, bioactive composition, and storage life using kinetic modelling - Mahendra Gunjal; Atul Khalangre; Jyoti Singh; Sawinder Kaur; Sezai Ercisli; Emine Macit; Prasad Rasane (Journal of Stored Products Research, 2025)

Pre-Himalayan crustal evolution in the northern margin of India: Implications from zircon U–Pb, Hf and O isotope study of Chhota Shigri granitoids, Himachal Himalaya, Northwest India - Waikhom Nongdon; Bidyananda Maibam; Pankaj Kumar; Yoann Gréau; Jasper Berndt; Stephen Foley; Atul Kumar Singh; Deeksha Khandelwal (Gondwana Research, 2025)

Degradation of cefixime antibiotic by continuous flow ultraviolet-C persulfate based advanced oxidation process: Fresh and marine water matrices, antibacterial activity removal, and cost analysis - Atul Patel; Laxman G. Raikar; Jemi Gandhi; Halan Prakash (Chemical Engineering Journal, 2025)

Estimation of earthquake recurrence parameters for the Himalayan seismic belt: a comprehensive analysis - Rajiv Kumar; R. B. S. Yadav; Himanshu Mittal; Atul Saini; O. P. Mishra (Natural Hazards, 2025)

Stability analysis and prediction of Bimslope failures using numerical modelling and hybrid meta-heuristic models - Arunava Ray; Gopika C. Atul; Sanjog Chhetri Sapkota; Prasenjit Saha; Sourav Das; Rajesh Rai; Manoj Khandelwal (Natural Hazards, 2025)
Bimsoil slope (Bimslope) or Soil-Rock-Mixture slopes are complex geological formations made up of geotechnically important ‘blocks’ enclosed in a finer-textured ‘matrix.’ These geomaterials possess heterogeneous properties owing to changes in the block and matrix properties that can arise from natural weathering processes or various anthropogenic activities. The present study focuses on the stability analysis of a Bimslope under varying block properties (orientation and volumetric block proportion), matrix type (Loamy sand, Sandy loam, and Silt loam) and matrix water content. The study indicates that the failure of a Bimslope is not governed by only one physical parameter but rather by a critical combination of block properties, matrix type and matrix water content. When the water content (< 25% saturation) and block content (< 25%) are less, the failure is governed by matrix only. With the increase in block content, the failure is governed by block however under fully saturated (100% saturation) conditions, the failure is solely governed by matrix type irrespective of block properties. In addition to that, the data generated using numerical analysis was used to predict the factor of safety using hybridized ensembled methods considering the XGB model and three other novel meta-heuristic algorithms (MHA): political optimization (POA), the Leopard Seal algorithm (LSA), and the Giant Armadillo Algorithm (GAA). It has been found that among all the models, the GAA-XGB algorithm exhibits better results with R 2 and RMSE values as 0.99628, 0.055436 in training and 0.985664, 0.063092 in the testing stage. Furthermore, SHAP-based analysis has been performed to identify the most influential parameters.

The effect of enhanced glycolysis on cardiac aging - Anna Faakye; Kylene M. Harold; Satoshi Matsuzaki; Atul Pranay; Maria F. Mendez Garcia; Brooke L. Loveland; Sandra N. Rigsby; Frederick F. Peelor; Craig Eyster; Benjamin F. Miller; Timothy M. Griffin; Michael Kinter; et al. (GeroScience, 2025)
Cardiac aging is associated with metabolic changes, including an increased reliance on glycolysis, and an increased susceptibility to cardiovascular diseases. This study explores the relationship between enhanced cardiac glycolysis and aging using the Glyco Hi mouse model, characterized by constitutively elevated glycolysis. We compared cardiac function, metabolism, mitochondrial performance, and hallmarks of aging between aged (21 and 24 months) Glyco Hi and wild-type (WT) mice across sexes. Our findings reveal modest reductions in cardiac function in aged Glyco Hi mice compared to WT mice, with sex-specific differences in heart size and collagen concentration. Female Glyco Hi hearts exhibited hypertrophy without fibrosis, while males showed elevated collagen levels. Whole-body metabolic assessments revealed similar energy expenditure and respiratory patterns across genotypes, with females displaying less circadian-associated variation in metabolism. Mitochondrial analyses showed that aged Glyco Hi hearts maintained metabolic adaptations favoring glycolysis but did not exhibit significant bioenergetic dysfunction or oxidative stress. Pyruvate dehydrogenase activity, initially elevated in younger Glyco Hi hearts, normalized to WT levels with age. Proteomic and metabolomic analyses highlighted distinct profiles between genotypes, with Glyco Hi hearts exhibiting increased glycolytic enzyme levels and reduced abundance of fatty acid oxidation proteins. Despite these differences, indicators of oxidative stress, proteostasis, and cellular senescence were comparable between genotypes, suggesting no acceleration of aging-related dysfunction. This study demonstrates that increased cardiac glycolysis alone does not suffice to drive accelerated cardiac aging. Instead, metabolic and functional changes in aged Glyco Hi hearts reflect adaptations rather than pathological declines, providing insights into potential metabolic targets for interventions against cardiac aging.

Erratum to: Flooding (or breaching) of inter-connected proglacial lakes by cascading overflow in the arid region of Western Mongolia (Mt. Tsambagarav, Mongolian Altai) - Otgonbayar Demberel; Chinmay Dash; Battsetseg Dugersuren; Munkhbat Bayarmaa; Yeong Bae Seong; Elora Chakraborty; Batsuren Dorjsuren; Atul Singh; Nemekhbayar Ganhuyag (Journal of Mountain Science, 2025)

Decadal seasonal characteristics of precipitation microphysics over the Western Ghats using the space-borne precipitation radar - Amit Kumar; Atul Kumar Srivastava; Bharat Ji Mehrotra; Manoj Kumar Srivastava; D.R. Pattanaik (Atmospheric Research, 2025)

Assessment of Surface PM2.5 Concentrations over India using Modern-Era Retrospective Analysis for Research and Applications, Version 2 (MERRA-2) Reanalysis Data - Sumit Singh; Amarendra Singh; Atul Kumar Srivastava; Virendra Pathak; Ajay Kumar; Vivek Singh (Pure and Applied Geophysics, 2025)

Correction: Space‑borne RADARs for Precipitation Measurement - Atul Kumar Varma (Journal of the Indian Society of Remote Sensing, 2025)

Eudragit S 100 Assisted Molecular Solid Dispersion of Andrographolide Tendered Augmented Drug Delivery and Apoptosis in Human Colon Cancer, HT-29 Cells - Pawan Devangan; Anamika Sharma; Nitin Wadate; Atul Mourya; Jitender Madan (AAPS PharmSciTech, 2025)

Non-essential use of benzotriazole ultraviolet stabilizers in single-use plastics manufactured in India: An avoidable class of plastic additives - Ankur Khare; Pradip Jadhao; Atul Narayan Vaidya; Asirvatham Ramesh Kumar (Science of The Total Environment, 2025)

Effect of pretreatments on seed germination of musk rose (Rosa moschata Herrm.) - Vikas Yadav Patade; Nirbhay Singh; Atul Grover; Madhu Bala (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Comparison of different freezing rates on post-thaw viability, proliferation, and stemness of sheep spermatogonial stem cells - Balakrishnan Binsila; Tomy A. Tomcy; Balaganur Krishnappa; Muhammed Sadikh; Natesan Ramachandran; Atul P. Kolte; Sellappan Selvaraju (Cryobiology, 2025)

Analysis of soybean cultivars response to mosaic and mottle disease caused by soybean yellow mottle mosaic virus - M. Srikant; Nagamani Sandra; Atul Kumar; Sandeep Kumar Lal; Sanjay Kumar Lal; Bikash Mandal (VirusDisease, 2025)

Spatiotemporal dynamics of rice cultivation in India - Netrananda Sahu; Ravi Kesharwani; Pritiranjan Das; Anil Kumar; Ayush Varun; Atul Saini; Suraj Kumar Mallick; Martand Mani Mishra (Tropical Ecology, 2025)

Gold Nanoparticles as a Tool to Detect Biomarkers in Osteoarthritis: New Insights - Atul Mourya; Shristi Arya; Ayush Singh; Gopal Bajad; Soham Loharkar; Shubhra; Pawan Devangan; Neelesh Kumar Mehra; Rahul Shukla; Ramesh Chandra; Jitender Madan (Indian Journal of Microbiology, 2025)

Exploration of Abiraterone acetate loaded Nanostructured lipid carriers for bioavailability improvement and circumvention of fast-fed variability - Saurabh Shah; Paras Famta; Ganesh Vambhurkar; Abhishek Sharma; Atul Mourya; Dadi A. Srinivasarao; Akshay Shinde; Sajja Bhanu Prasad; Giriraj Pandey; Jitender Madan; Saurabh Srivastava (Drug Delivery and Translational Research, 2025)

Regulation of stress-responsive transcription factors of rice by CPPU, a synthetic cytokinin, during water deficit stress at protein level - Ranjit Singh Gujjar; Kanyaratt Supaibulwatana; Sangeeta Srivastava; Atul Kumar Upadhyay (Cereal Research Communications, 2025)

Parallel propagation effects on the dust acoustic drift instability in the equatorial electrojet - Sanjib Sarkar; Jyoti K. Atul; Modhuchandra Laishram; Dan Dan Zou; Ishita Gulati; Manoranjan K. Singh; Prabal K. Chattopadhyay (Advances in Space Research, 2025)

Postbiotics: an exposition on next generation functional food compounds- opportunities and challenges - Priyanka Suthar; Satish Kumar; Vikas Kumar; Vishal Sharma; Atul Dhiman (Critical Reviews in Food Science and Nutrition, 2025)

Morphotectonics, slope stability and paleostress studies from the Bhagirathi river section, western Himalaya (Uttarakhand, India) - Nikhil Puniya; Soumyajit Mukherjee; Atul Kumar Patidar; Mohit Kumar Puniya; Mery Biswas; Tuhin Biswas (Journal of Structural Geology, 2025)

Climatic reconstruction of the Late Palaeocene using sedimentary archives from the Bikaner-Nagaur Basin, Rajasthan, India - Dinesh Kumar; Tushar Adsul; Ofentse M. Moroeng; Zoremsiami Pachuau; Ashutosh Panigrahi; Santanu Ghosh; Asmita Datta; Rupayan Sen; Atul Kumar Varma (International Journal of Coal Geology, 2025)

Basin-scale spatio-temporal development of glacial lakes in the Hindukush-Karakoram-Himalayas - Atul Kumar; Suraj Mal; Udo Schickhoff; A.P. Dimri (Global and Planetary Change, 2025)

Rice bran: Nutritional value, health benefits, and global implications for aflatoxin mitigation, cancer, diabetes, and diarrhea prevention - Anup Kodape; Atul Kodape; Ria Desai (Food Chemistry, 2025)

Double optimization of 2D Bi2WO6 flowers into sheets with AgBr and Ag loading towards enhanced acetaminophen removal and H2 production - Atul Verma; Esakkinaveen Dhanaraman; Yi-Syuan Peng; Yen-Pei Fu (Chemical Engineering Journal, 2025)

Advanced Normal-Phase HPTLC Profiling of Eltrombopag Olamine with Automated Development and Box-Behnken Optimizations - Pranay M. Hadole; Saurabh B. Ganorkar; Suraj R. Chaudhari; Vaishali N. Sonawane; Preeti S. Bobade; Amod S. Patil; Atul A. Shirkhedkar (Journal of Pharmaceutical Innovation, 2025)

The incidence of symptomatic CSF viral escape in patients on antiretroviral therapy in western India: a retrospective cohort study - Atul Patel; Ketan Patel; Niyati Patel; Kinjal Shah; Ambuj Kumar (Journal of NeuroVirology, 2025)

Assessment of urban environment quality using analytical hierarchical process and multi-dimensional decomposition analysis for Mumbai metropolitan region, India - Rabin Chakrabortty; Atul Kumar; Sajedur Rahman Mishuk; Malay Pramanik; Ram Avtar; Harekrishna Manna; Mohamed Zhran (Advances in Space Research, 2025)

Unravelling the proteome of Saccharum officinarum cv. BO91 for novel defense-related proteins during C. falcatum infection - Ranjit Singh Gujjar; Deeksha Joshi; Sanjay Kumar Goswami; Rajeev Kumar; Arjun Singh; Atul Kumar Upadhyay (Acta Physiologiae Plantarum, 2025)

Non‐Native Invasive Fish Species ( NIFS ) in Inland Waters of India: Management Issues, Strategies and Suggestions - Atul K. Singh (Fisheries Management and Ecology, 2025)
In India, there are 626 non‐native invasive fish species (NIFS), with 16 becoming invasive in inland waters, adversely impacting native biodiversity, and fisheries by altering the abundance of NIFS in commercial catches. Scientific findings highlight that the movement of NIFS interacts with agricultural activities and the evolving environment, facilitating their spread and establishment. The scenario of NIFS invasion disrupts biological communities, ecosystem services and fisherfolk livelihoods. Despite the implementation of existed guidelines, issues related to NIFS have persisted and escalated over time scale putting increased pressure on indigenous aquatic biological resources in inland waters. This paper suggests the need of framing a new management plans, guidelines and regulatory policies to control NIFS invasions, protecting riverine fish biodiversity and ecosystem services. Proposed management strategies include functional response (FR) and adaptive response (AR)‐based approaches, which are discussed to address NIFS management in inland waters.

An environmentally benign process to synthesize vanillin and other substituted phenyl aldehydes using natural phenylpropenes - Sarita Singh; Swati Singh; Asha Budakoti; Neha Kumari; Ram Swaroop Verma; Arvind Singh Negi; Karuna Shanker; Sudeep Tandon; Alok Kalra; Atul Gupta (Food Chemistry, 2025)

Spatiotemporal mapping of groundwater recharge potential zones for physical planning process—A case of Ajmer City, India - Vivekanand Tiwari; Atul Kumar; Mahua Mukherjee (Ecohydrology & Hydrobiology, 2025)

Relationship of aerosol with cloud and precipitation over the Gangetic plain of India - Vikram Raj; P. Parth Sarthi; Archisman Barat; Atul Kumar Srivastava (Theoretical and Applied Climatology, 2025)

Assessing the Sustainability and Food Security Implications of Introduced Pangasianodon hypophthalmus (Sauvage, 1878) and Clarias gariepinus (Burchell, 1822) Into Indian Aquaculture: A OneHealth Perspective - Atul K. Singh (Reviews in Aquaculture, 2025)
The introduced striped catfish ( Pangasianodon hypophthalmus , Sauvage, 1878) and North African catfish ( Clarias gariepinus , Burchell, 1822) are popular choices in Indian aquaculture due to their high productivity and ease of management. Among all introduced non‐native fish species, catfish production is particularly notable, with P. hypophthalmus contributing 1.6 million metric tons (mmt) and C. gariepinus reaching 0.4 mmt. This paper examines the ecological, biodiversity, environmental, and disease concerns associated with the intensive aquaculture of the non‐native catfish species, using a OneHealth approach to assess sustainability. Generated information on biological plasticity, resource competition, genetic interactions, invasion risks, biodiversity impacts, food safety, and disease risks in extensive aquaculture of non‐native catfish are presented. A risk assessment (RA) was performed using an Excel–based developed module having 28 attributes and rated on a scale of 1 to 5. The results indicated significant risks, particularly for C. gariepinus , which had a risk score of 116 out of total 140 response points obtained from 65 farmers, manifesting 82.85% risk. In comparison, P. hypophthalmus had a response score of 85, displaying 60.71% risk. The findings suggest that C. gariepinus poses a higher ecological risk than P. hypophthalmus , primarily due to poorly controlled aquaculture practices, inadequate biosecurity, and insufficient regulatory measures. To tackle these issues, it is recommended that stringent policy with clear regulatory framework on the OneHealth approach will ascertain safe interconnectedness of aquaculture, environment, fish, and human health while improving the biosafety of non‐native catfish aquaculture practices safeguarding human health, fish populations, and overall ecosystem health.

New insights into residual triiodide ion removal from iodinated water using magnetic CoFe2O4 nanoparticles: exploring adsorption behavior and mechanisms - Manish Naagar; Sonia Chalia; Fayu Wan; Preeti Thakur; Pritam Babu Sharma; Atul Thakur (Environmental Science and Pollution Research, 2024)

Critical minerals for energy transition: The emerging regime complex - Nidhi Srivastava; Atul Kumar (The Extractive Industries and Society, 2024)

Superoxide dismutase positively regulates Cu/Zn toxicity tolerance in Sorghum bicolor by interacting with Cu chaperone for superoxide dismutase - Junmei Jiang; Nuo Zhang; Atul Kumar Srivastava; Guandi He; Zheng Tai; Zehui Wang; Sanwei Yang; Xin Xie; Xiangyang Li (Journal of Hazardous Materials, 2024)

Thiolated hyper-crosslinked tetraphenylborate with tunable selectivity for sequential recovery of Pd and Pt from autocatalyst leachate - Erwin C. Escobar; John Edward L. Sio; Atul A. Pawar; Gebremedhn T. Gebremichael; Negasi T. Weldesemat; Hern Kim; Wook-Jin Chung; Grace M. Nisola (Chemical Engineering Journal, 2024)

Fisetin ameliorates polycystic ovary syndrome in rats via a mechanistic modulation of AMP-activated protein kinase and SIRT1 molecular pathway - Simerjeet Kaur Chahal; Atul Kabra (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Identification and structural characterization of a pathogenic ARSA missense variant in two consanguineous families from Jammu and Kashmir (India) with late infantile metachromatic leukodystrophy - Yaser Rafiq Mir; Ashish Kumar Agrahari; Asima Hassan; Abhishek Choudhary; Shailendra Asthana; Atul Kumar Taneja; Shah Nawaz; Mohd Ilyas; Claudia Scotti; Raja A. H. Kuchay (Molecular Biology Reports, 2024)

Space-borne RADARs for Precipitation Measurement - Atul Kumar Varma (Journal of the Indian Society of Remote Sensing, 2024)

Formulation Optimization of Metformin-Loaded Propyl Moringa Gum Beads - Atul Kaushik; Rimpy Pahwa; Rashmi Sharma; Vikramjeet Singh; Munish Ahuja (Journal of Pharmaceutical Innovation, 2024)

Assessment of Active Deformation in the Surrounding Regions of the 7th to 12th AD Monuments in the Central Kumaon Himalayas: A Seismotectonic Approach using PSInSAR - Girish Ch. Kothyari; Achla Joshi; Rakesh K. Dumka; Bahadur S. Kotlia; Atul Kumar Patidar; Moulishree Joshi; Khayingshing Luirei; Sambit Prasanajit Naik; Ajay K. Taloor; Mayank Joshi; Hem Ch. Kothyari (Geoheritage, 2024)

Association of IL1RN VNTR and NKG2A polymorphisms with hepatitis E infection, a case study from western India - Anuradha S. Tripathy; Priyanka Wagh; Gajendra Shahapure; Atul M. Walimbe; Nalini Kadgi; Leena Nakate (Archives of Virology, 2024)

Damaging earthquakes of the Eastern Indian subcontinent and seismic hazard potential: insights from palaeoseismology - Atul Brice; Arjun Pandey; R. Jayangondaperumal; Anusuya Mohanta; Rao Singh Priyanka; Madhusudan Sati; Yashpal Sundriyal (International Geology Review, 2024)

Allergic potential & molecular mechanism of skin sensitization of cinnamaldehyde under environmental UVB exposure - Sunil Kumar Patel; Apeksha Vikram; Diksha Pathania; Rashi Chugh; Prakriti Gaur; Gaurav Prajapati; Sumana Y. Kotian; G.N.V. Satyanarayana; Akhilesh Kumar Yadav; Atul Kumar Upadhyay; Ratan Singh Ray; Ashish Dwivedi (Chemosphere, 2024)

Intensification mechanisms and moisture dynamics of super cyclonic storm ‘Amphan’ over the Bay of Bengal: Implications for aerosol re-distribution - Vivek Singh; Atul Kumar Srivastava; Anu Gupta; Rakesh Teja Konduru; Amarendra Singh; Sumit Singh; Arun Kumar; Deewan Singh Bisht; Abhay Kumar Singh (Science of The Total Environment, 2024)

Ultrasonic Assisted Synthesis of CuFe2O4-Ag infused Gum Hydrogels Nanocomposite for photocatalytic Degradation of Organic Dye from Wastewater - Meenu; Pratibha Sharma; Roli Purwar; Navita Sharma; Pooja Rawat; Seema R. Pathak; Atul Thakur; Hyunook Kim; Monu Verma; Sudip Majumder; Chandra Mohan Srivastava (Water, Air, & Soil Pollution, 2024)

Sustainable and efficient removal of cationic and neutral dyes from aqueous solution using nano-engineered CuFe2O4/Peanut shell magnetic composite - Atul Sharma; Arshi Choudhry; Bindu Mangla; Saif Ali Chaudhry (Clean Technologies and Environmental Policy, 2024)

Fe-doped nano-cobalt oxide green catalysts for sulfoxidation and photo degradation - Atul Soni; Minaxi S. Maru; Parth Patel; Jagriti Behal; Deepika Kaushal; Manish Kumar; Maheshwar S. Thakur; Sunil Kumar (Clean Technologies and Environmental Policy, 2024)

Extraction of tectonic imprints using geospatial techniques: Evidence from Mandakini River basin, Uttarakhand, India - Atul Kumar Patidar; Girish Ch. Kothyari; Manmohan Kaushik; Sushil Khanduri (Journal of Mountain Science, 2024)

Osmosonication for dehydration of fruits and vegetables: Mechanistic understanding, mathematical models and comprehensive applications in processing - Abhishek Rana; Atul Dhiman; Satish Kumar; Rajat Suhag; Rajni Saini (Trends in Food Science & Technology, 2024)

Sequential investment decisions for mining projects using compound multiple volatility real options approach - Atul Chandra; Peter R. Hartley (Resources Policy, 2024)

A state-of-art review on photovoltaic systems: Design, performance, and progress - Abhishek Saxena; Rajneesh Kumar; Atul A. Sagade; Desh Bandhu Singh; V.V. Tyagi; Erdem Cuce; Varun Goel (Process Safety and Environmental Protection, 2024)

Inter-seasonal variation of rainfall microphysics as observed over New Delhi, India - Mohit Kumar; Kaustav Chakravarty; Sachin Deshpande; Sumit Kumar; Atul Srivastava (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Neoproterozoic crustal evolution of Indo-Australo-Antarctic Suture domain and Gamburtsev Subglacial Mountains, East Antarctica: Insights from offshore sediments - Rashmi Gupta; Mayuri Pandey; Devsamridhi Arora; Akash K. Pandey; Naresh C. Pant; K. Batuk Joshi; Pankaj Kumar; M. Satyanarayanan; Atul Singh (Gondwana Research, 2024)

Exploring coffee's impact: Aflatoxins, phytochemicals, and public health considerations - Anup Kodape; Atul Kodape (Food Bioscience, 2024)

In-silico Based Genome-Wide Identification and Analysis of Glutathione S-Transferase Gene Family in Beet (Beta vulgaris subsp. vulgaris) - Shivani Tiwari; Swati Vaish; Nootan Singh; Mahesh Basantani; Atul Bhargava (Sugar Tech, 2024)

A bibliometric analysis for Indian summer monsoon variability - Netrananda Sahu; Pritiranjan Das; Satyaban B. Ratna; Atul Saini; Suraj Kumar Mallick; Anil Kumar; Mrutyunjay Mohapatra (Spatial Information Research, 2024)

Assessing sediment dynamics and retention services in the vulnerable mountain ecosystem of the Indian Himalayas - Atul Chauhan; Souvanic Roy; Abhinandita Kundu (Environmental Monitoring and Assessment, 2024)

Flooding (or breaching) of inter-connected proglacial lakes by cascading overflow in the arid region of Western Mongolia (Mt. Tsambagarav, Mongolian Altai) - Otgonbayar Demberel; Chinmay Dash; Battsetseg Dugersuren; Munkhbat Bayarmaa; Yeong Bae Seong; Elora Chakraborty; Batsuren Dorjsuren; Atul Singh; Nemekhbayar Ganhuyag (Journal of Mountain Science, 2024)

Polystyrene nanoplastics: optimized removal using magnetic nano-adsorbent and toxicity assessment in zebrafish embryos - Chaitanya Kumar; Harpreet Singh; Debopriya Ghosh; Atul Jain; Shailendra Kumar Arya; Madhu Khatri (Journal of Environmental Health Science and Engineering, 2024)

Algal consortia as the flexible bio-system for wastewater treatment: Effect of different light intensities on photosynthetic performance, anti-oxidative system and biodiesel production of consortia - Dig Vijay Singh; Atul Kumar Upadhyay; Ranjan Singh; Rana Pratap Singh (Biocatalysis and Agricultural Biotechnology, 2024)

Hydrothermal infra-red (HT-IR): the most effective technology for enhancing the shelf-life of pearl millet flour without compromising with the nutrient density and flour quality - Ranjeet R. Kumar; Neha Singh; Suneha Goswami; T. Vinutha; Sumer P. Singh; Gyan P. Mishra; Atul Kumar; Girish K. Jha; C. Tara Satyavathi; Shelly Praveen; Aruna Tyagi (Journal of Plant Biochemistry and Biotechnology, 2024)

Garlic (Allium sativum L.): A review on bio-functionality, allicin's potency and drying methodologies - Priyanka Thakur; Atul Dhiman; Satish Kumar; Rajat Suhag (South African Journal of Botany, 2024)

Revealing the urban heat Island: Investigating spatiotemporal surface temperature dynamics, modeling, and interactions with controllable and non-controllable factors - Aneesh Mathew; Arunab K. S.; Atul Kumar Sharma (Remote Sensing Applications: Society and Environment, 2024)

Understanding switching intentions towards renewable energy technologies using push-pull-mooring framework - Shiksha Kushwah; Rajesh Iyer; Atul Agrawal; Sanjna Korpal (Journal of Cleaner Production, 2024)

Perspectives on life cycle analysis of solar technologies with emphasis on production in India - Shweta Singh; Atul Dhar; Satvasheel Powar (Journal of Environmental Management, 2024)

Decoding paleomire conditions of paleogene superhigh-organic-sulfur coals - Tushar Adsul; Molly D. O'Beirne; David A. Fike; Santanu Ghosh; Josef P. Werne; William P. Gilhooly; Paul C. Hackley; Javin J. Hatcherian; Bright Philip; Bodhisatwa Hazra; Sudip Bhattacharyya; Ritam Konar; et al. (International Journal of Coal Geology, 2024)

Innovative solutions for potential use of waste polyethylene terephthalate bottle cap as aggregates in concrete - Sudhir Bhaskarrao Gayake; Atul K. Desai (Innovative Infrastructure Solutions, 2024)

Evolution of tectonic landscapes and deformation in the southeast Kumaun and western Nepal Himalaya - Khayingshing Luirei; Girish Ch. Kothyari; Param K. Gautam; Ambar Solanki; Atul Kumar Patidar; Sentisenla Jamir; Anirudh Datta; Tanupriya Choudhury (Journal of Mountain Science, 2024)

Enhanced nitrous oxide emission factors due to climate change increase the mitigation challenge in the agricultural sector - Linchao Li; Chaoqun Lu; Wilfried Winiwarter; Hanqin Tian; Josep G. Canadell; Akihiko Ito; Atul K. Jain; Sian Kou‐Giesbrecht; Shufen Pan; Naiqing Pan; Hao Shi; Qing Sun; et al. (Global Change Biology, 2024)
Effective nitrogen fertilizer management is crucial for reducing nitrous oxide (N 2 O) emissions while ensuring food security within planetary boundaries. However, climate change might also interact with management practices to alter N 2 O emission and emission factors (EFs), adding further uncertainties to estimating mitigation potentials. Here, we developed a new hybrid modeling framework that integrates a machine learning model with an ensemble of eight process‐based models to project EFs under different climate and nitrogen policy scenarios. Our findings reveal that EFs are dynamically modulated by environmental changes, including climate, soil properties, and nitrogen management practices. Under low‐ambition nitrogen regulation policies, EF would increase from 1.18%–1.22% in 2010 to 1.27%–1.34% by 2050, representing a relative increase of 4.4%–11.4% and exceeding the IPCC tier‐1 EF of 1%. This trend is particularly pronounced in tropical and subtropical regions with high nitrogen inputs, where EFs could increase by 0.14%–0.35% (relative increase of 11.9%–17%). In contrast, high‐ambition policies have the potential to mitigate the increases in EF caused by climate change, possibly leading to slight decreases in EFs. Furthermore, our results demonstrate that global EFs are expected to continue rising due to warming and regional drying–wetting cycles, even in the absence of changes in nitrogen management practices. This asymmetrical influence of nitrogen fertilizers on EFs, driven by climate change, underscores the urgent need for immediate N 2 O emission reductions and further assessments of mitigation potentials. This hybrid modeling framework offers a computationally efficient approach to projecting future N 2 O emissions across various climate, soil, and nitrogen management scenarios, facilitating socio‐economic assessments and policy‐making efforts.

Catalytic activity of Zr/CeO2-Al2O3 catalyst for diesel soot oxidation: synthesis, characterization, and performance evaluation - Mritunjay Kumar Shukla; Vibhuti Bangwal; Atul Dhar; Thallada Bhaskar; Adarsh Kumar (Environmental Science and Pollution Research, 2024)

Impact of urban growth in Delhi and It's Peri-urban environment on urban heat exposure - Suraj Kumar Mallick; Netrananda Sahu; Pritiranjan Das; Biswajit Maity; Ayush Varun; Anil Kumar; Ravi Keswarwani; Atul Saini; Somnath Rudra (Urban Climate, 2024)

Integrating blockchain technology success factors in the supply chain of circular economy-driven construction materials: An environmentally sustainable paradigm - Atul Kumar Singh; V.R. Prasath Kumar (Journal of Cleaner Production, 2024)

Assessing the land use dynamics and thermal environment using geospatial techniques in the industrial city of Chotanagpur Plateau Region, India - Biplab Banerjee; Anindita Pal; Atul K. Tiwari; Rolee Kanchan (Environmental Monitoring and Assessment, 2024)

Low frequency dust acoustic drift instability in the equatorial electrojet - Sanjib Sarkar; Jyoti K. Atul; Modhuchandra Laishram; Anirban Saha; Prabal K. Chattopadhyay (Advances in Space Research, 2024)

Assessment of higher demand of household energy consumption in different households in India: an inter-comparative study and solar savings valuation - Abhishek Saxena; Atul A. Sagade; Erdem Cuce; Desh Bandhu Singh; Avnish Kumar; Parul Gupta (Environmental Science and Pollution Research, 2024)

Overcoming equilibrium constraints in the reverse water gas shift with counter-current gas–solid flow and oxygen transport in La0.75Sr0.25Cr0.5Mn0.5O3-δ - Martin Keller; Atul Sharma (Journal of Environmental Chemical Engineering, 2024)

Assessment of Trachyspermum ammi essential oil against Aspergillus flavus, aflatoxin B1 contamination, and post-harvest quality of Sorghum bicolor - Prem Pratap Singh; Atul Kumar Jaiswal; Ritu Singh; Akshay Kumar; Vishal Gupta; Tanya Singh Raghuvanshi; Angad Sharma; Bhanu Prakash (Food Chemistry, 2024)

RETRACTED ARTICLE: Durability studies on conventional concrete and slag-based geopolymer concrete in aggressive sulphate environment - Atul Garg; Parveen Jangra; Dhirendra Singhal; Thong M. Pham; Deepankar Kumar Ashish (Energy, Ecology and Environment, 2024)

Comparative Interpretation of Structural, Functional, Phytochemical and Pasting Profile of Coloured Variety Potato Flakes Prepared Using Different Drying Techniques - Rajni Saini; Sukhpreet Kaur; Poonam Aggarwal; Atul Dhiman; Sumit Grover (Potato Research, 2024)

Phylogeography and gene pool analysis of highly pathogenic avian influenza H5N1 viruses reported in India from 2006 to 2021 - Deeksha S. Tare; Sachin S. Keng; Atul M. Walimbe; Shailesh D. Pawar (Archives of Virology, 2024)

Corrigendum to “Electrostatically robust CoFeOF nanosheet against chloride for green-H2 production in alkaline seawater electrolysis” [Chem. Eng. J. 480 (2024) 146545] - Supriya A. Patil; Atul C. Khot; Vijay D. Chavan; Iqra Rabani; Deok-kee Kim; Jongwan Jung; Hyunsik Im; Nabeen K. Shrestha (Chemical Engineering Journal, 2024)

The resurgence of old material: The impact of boehmite-derived catalytic material on the formation of dihydropyran compounds and its application to access fragrant derivatives - Manas Barik; Brijesh Patel; Shilpa Dabas; Parul Rathour; Dharm S. Padariya; Lakhya Jyoti Konwar; Atul Kumar; Rajendra Srivastava; Palani S. Subramanian; Saravanan Subramanian (Chemical Engineering Journal, 2024)

GIS and AHP-based groundwater recharge potential zones in urban region: A study of Ajmer City, Rajasthan, India - Vivekanand Tiwari; Atul Kumar; Mahua Mukherjee (Urban Climate, 2024)

Co-movement between carbon emissions and forex market: A tale of COVID-19 outbreak and Russia-Ukraine invasion - Rabindra Nepal; Miklesh Prasad Yadav; Rupinder Katoch; Himani Gupta; Atul Kumar (Resources Policy, 2024)

Colletotrichum falcatum influences sucrose accumulation in sugarcane stalks by modulating the expression of SPS, SPP, SuSy, and invertases - Ranjit Singh Gujjar; Rajeev Kumar; Sanjay Kumar Goswami; Sangeeta Srivastava; Atul Kumar Upadhyay (Physiological and Molecular Plant Pathology, 2024)

Fully finite volume method on a curvilinear grid-based arbitrary Lagrangian Eulerian approach for computational fluid flexible-structure interaction - Sumant R. Morab; Atul Sharma; Janani S. Murallidharan (Computer Physics Communications, 2024)

Cultural, morphological and molecular characterization of Stemphylium vesicarium isolates causing onion blight - Niranjan Prasad; Atul Kumar; Vijay Dunna; Jeetendra K Ranjan; Jameel Akhtar; Gyan P Mishra; Anju Bala Sharma; Shaily Javeria (Indian Phytopathology, 2024)

“Long COVID” and Its Impact on The Environment: Emerging Concerns and Perspectives - Parul Rana; Shilpa Patial; Vatika Soni; Pardeep Singh; Atul Khosla; Sourbh Thakur; Chaudhery Mustansar Hussaisn; Patricia de Carvalho Nagliate; Lucas Meili; Rangabhashiyam Selvasembian; Pankaj Raizada (Environmental Management, 2024)

QbD-driven development of phospholipid-embedded lipidic nanocarriers of raloxifene: extensive in vitro and in vivo evaluation studies - Anjali Pant; Gajanand Sharma; Sumant Saini; Gurjeet Kaur; Atul Jain; Anil Thakur; Bhupinder Singh (Drug Delivery and Translational Research, 2024)

A non-catalytic diesel autothermal reformer for on-board hydrogen generation - Ravinder Kumar; Mahesh M. Haridasan; Inzamam Ahmad; Atul Bhargav; Suman Roy Choudhuri (Fuel, 2024)

Impact of Types of Aerosol and Meteorological Conditions on Rain Rate Over India - Vikram Raj; P. Parth Sarthi; Atul Kumar Srivastava (Pure and Applied Geophysics, 2024)

Air pollution status and attributable health effects across the state of West Bengal, India, during 2016–2021 - Buddhadev Ghosh; Harish Chandra Barman; Sayoni Ghosh; Md Maimun Habib; Jayashree Mahato; Lovely Dayal; Susmita Mahato; Priti Sao; Atul Chandra Murmu; Ayontika Deb Chowdhury; Sourina Pramanik; Rupsa Biswas; et al. (Environmental Monitoring and Assessment, 2024)

Monitoring forest cover changes and its impact on land surface temperature using geospatial technique in Talra Wildlife Sanctuary, Shimla, India - Pawan Kumar Thakur; Sher Singh Samant; Raj Kumar Verma; Atul Saini; Monika Chauhan (Environment, Development and Sustainability, 2024)

Botulinum Neurotoxin Treatment Dynamics and Persistence Over 2 Years in Patients With Cervical Dystonia or Spasticity: A Retrospective Claims Database Analysis - David M. Simpson; Jonathan Bouchard; Simon Page; Dean Spurden; Seth Goldfarb; Atul T. Patel (Toxicon, 2024)

Real-world Retrospective Safety Analysis of OnabotulinumtoxinA for the Treatment of Patients With Concurrent Cervical Dystonia and Chronic Migraine - Christopher Rhyne; Kenneth Martinez; Juliana Stoilova; Atul Patel; Kim Becker Ifantides; Ritu Singh; Irina Yushmanova; Marjan Sadeghi; Simona Battucci; Forde Grace (Toxicon, 2024)

Improvement in Spasticity-Associated Limb Position Abnormality in Adults Following Treatment With IncobotulinumtoxinA: A Pooled Analysis - Franco Molteni; Jörg Wissel; Klemens Fheodoroff; Michael C. Munin; Atul T. Patel; Michael Althaus; Georg Comes; Andrzej Dekundy; Irena Pulte; Astrid Scheschonka; Matteo Vacchelli; Andrea Santamato (Toxicon, 2024)

Improvement in Spasticity-Associated Dressing- and Hygiene-Related Disability in Adults Following Treatment With IncobotulinumtoxinA: A Pooled Analysis - Franco Molteni; Jörg Wissel; Klemens Fheodoroff; Michael C. Munin; Atul T. Patel; Michael Althaus; Georg Comes; Andrzej Dekundy; Irena Pulte; Astrid Scheschonka; Matteo Vacchelli; Andrea Santamato (Toxicon, 2024)

Real-World Retrospective Safety Analysis of OnabotulinumtoxinA for the Concomitant Treatment of Patients With Spasticity and Other Therapeutic Indications - Angeli Mayadev; Ziyad Ayyoub; Atul Patel; Kim Becker Ifantides; Ahunna Ukah; Mariana Nelson; Simona Battucci; Theodore Brown (Toxicon, 2024)

Patient Perspectives on the Conduct of a Head-to-Head Study Comparing AbobotulinumtoxinAWith OnabotulinumtoxinA for Upper Limb Spasticity - Alberto Esquenazi; Ziyad Ayyoub; Monica Verduzco-Gutierrez; Pascal Maisonobe; Simon Page; Atul T. Patel (Toxicon, 2024)

Long-Term Safety of Repeat Treatments of DaxibotulinumtoxinA for Injection in Adults With Isolated Cervical Dystonia in Phase 3, Open-label, Multicenter ASPEN-OLS Trial - Peter McAllister; H.A. Jinnah; Virgilio Evidente; Atul T. Patel; Todd M. Gross; Domenico Vitarella (Toxicon, 2024)

Exploiting the potential of fabric phase sorptive extraction for forensic food safety: Analysis of food samples in cases of drug facilitated crimes - Bharti Jain; Rajeev Jain; Abuzar Kabir; Torki Zughaibi; Atul Bajaj; Shweta Sharma (Food Chemistry, 2024)

The prospect of CuxO-based catalysts in photocatalysis: From pollutant degradation, CO2 reduction, and H2 production to N2 fixation - Atul Verma; Yen-Pei Fu (Environmental Research, 2024)

Nanoemulsion based edible coatings for quality retention of fruits and vegetables-decoding the basics and advancements in last decade - Anika Panwar; Vikas Kumar; Atul Dhiman; Priyanka Thakur; Vishal Sharma; Ajay Sharma; Satish Kumar (Environmental Research, 2024)

Analysis of the key hydrogen fuel vehicles adoption barriers to reduce carbon emissions under net zero target in emerging market - Atul Rawat; Chandra Prakash Garg; Priyank Sinha (Energy Policy, 2024)

Electrostatically robust CoFeOF nanosheet against chloride for green-H2 production in alkaline seawater electrolysis - Supriya A. Patil; Atul C. Khot; Vijay D. Chavan; Iqra Rabani; Deok-kee Kim; Jangwon Jung; Hyunsik Im; Nabeen K. Shrestha (Chemical Engineering Journal, 2024)

Chitosan scaffolds: Expanding horizons in biomedical applications - Amol D. Gholap; Satish Rojekar; Harshad S. Kapare; Nikhar Vishwakarma; Sarjana Raikwar; Atul Garkal; Tejal A. Mehta; Harsh Jadhav; Mahendra Kumar Prajapati; Uday Annapure (Carbohydrate Polymers, 2024)

Trihalomethanes in developed and developing countries - Anjali Kothe; Neha Wachasunder; Anupama Rodge; Pawan Labhasetwar; Atul Maldhure (Environmental Monitoring and Assessment, 2024)

Modelling the relationship between digital twins implementation barriers and sustainability pillars: Insights from building and construction sector - Ahmed Farouk Kineber; Atul Kumar Singh; Abdulwahed Fazeli; Saeed Reza Mohandes; Clara Cheung; Mehrdad Arashpour; Obuks Ejohwomu; Tarek Zayed (Sustainable Cities and Society, 2023)

Simultaneous observations of atmospheric vertical potential gradient from coastal Antarctic stations Bharati and Maitri - Krishnamoorthy Jeeva; Geeta Vichare; Gopi K. Seemala; Atul S. Kulkarni; Elango Paramasivan; Subrata Moulik; Anoop K. Soman; Pranjal Saikia (Polar Science, 2023)

Climatology of quiet time geomagnetic field variations at two locations in Antarctica - Geeta Vichare; Atul Kulkarni; Rahul Rawat; Gopi K. Seemala; Anoop K. Soman; Pritimay Patro (Polar Science, 2023)

Influence of B-atom in g-C3N4 matrix to enhance the photocatalytic dinitrogen to ammonia conversion - Esakkinaveen Dhanaraman; Atul Verma; Pandiyarajan Anand; Yen-Pei Fu (Journal of Environmental Chemical Engineering, 2023)

Insights into the antimicrobial efficacy of Coleus aromaticus essential oil against food-borne microbes: Biochemical and molecular simulation approaches - Prem Pratap Singh; Atul Kumar Jaiswal; Tanya Singh Raghuvanshi; Bhanu Prakash (Food and Chemical Toxicology, 2023)

Evaluation of synergistic adsorption approach for terbinafine removal by cotton shell powder immobilized zerovalent copper: Adsorption kinetics and DFT simulation - Parminder Kaur; Khadim Hussain; Atul Kumar; Janpreet Singh; J. Nagendra Babu; Sandeep Kumar (Environmental Nanotechnology, Monitoring & Management, 2023)

Immunodominant conserved moieties on spike protein of SARS-CoV-2 renders virulence factor for the design of epitope-based peptide vaccines - Subhashree Mohapatra; Santosh Kumar; Shashank Kumar; Atul Kumar Singh; Bismita Nayak (VirusDisease, 2023)

Specific Genetic Polymorphisms Contributing in Differential Binding of Gliadin Peptides to HLA-DQ and TCR to Elicit Immunogenicity in Celiac Disease - Pratibha Banerjee; Ramprasad Chaudhary; Atul Kumar Singh; Pratima Parulekar; Shashank Kumar; Sabyasachi Senapati (Biochemical Genetics, 2023)

Benzotriazole UV stabilizers (BUVs) as an emerging contaminant of concern: a review - Ankur Khare; Pradip Jadhao; Atul Narayan Vaidya; Asirvatham Ramesh Kumar (Environmental Science and Pollution Research, 2023)

Selective aerobic coupling of amines to imines using solar spectrum-responsive flower-like Nen-graphene quantum dots (GQDs) decorated with 2, 4-dinitrophenylhydrazine (PH) as a photocatalyst - Neetesh Kumar; Rajesh K. Yadav; Ahmad Umar; Ahmed A. Ibrahim; Satyam Singh; Rehana Shahin; Atul P. Singh; Abhishek K. Gupta; Navneet K. Gupta; Jin Ook Baeg; Dilip K. Dwivedi; Sotirios Baskoutas (Chemosphere, 2023)

Hyperspectral imaging-based classification of post-consumer thermoplastics for plastics recycling using artificial neural network - Mukesh Kumar Singh; Subrata Hait; Atul Thakur (Process Safety and Environmental Protection, 2023)

Reduced global warming potential in carbon-based perovskite solar modules: Cradle-to-gate life cycle analysis - Shweta Singh; Priyanka Kajal; Atul Dhar; Nripan Mathews; Pablo P. Boix; Satvasheel Powar (Journal of Cleaner Production, 2023)

Geochemical evaluation and environmental risk assessment of heavy metals: A case study from Ireland using Tellus stream sediment data (2011–2017) - Pragya Pandit; Atul Saini; Netrananda Sahu; Rohit Mehra (Groundwater for Sustainable Development, 2023)

Conventional and emerging innovative processing technologies for quality processing of potato and potato-based products: A review - Rajni Saini; Sukhpreet Kaur; Poonam Aggarwal; Atul Dhiman; Priyanka Suthar (Food Control, 2023)

Synthesis, Characterization and Potential Application of Functionalised Binary Metallic Sulphide for Water Reclamation - Md. Sajid; Atul Sharma; Arshi Choudhry; Saif Ali Chaudhry (Colloids and Surfaces C: Environmental Aspects, 2023)

Polyaniline doped silk fibroin-PCL Electrospunfiber: An electroactive fibrous sheet for full-thickness wound healing study - Ragavi Rajasekaran; Atul Kumar Ojha; Venkata Sundeep Seesala; Arman Kunwar Hansda; Nantu Dogra; Jhansi Lakshmi Parimi; Sabyasachi Roy; Ritobrata Goswami; Mamoni Banerjee; Santanu Dhara (Chemical Engineering Journal, 2023)

A new calibration correction method for INSAT-3D/3DR brightness temperatures to improve rainfall estimation - Neerja Sharma; Munn Vinayak Shukla; P. K. Thapliyal; Atul Kumar Varma (International Journal of Remote Sensing, 2023)

Role of Shape and Kinematics in the Hydrodynamics of a Fish-like Oscillating Hydrofoil - Siddharth Gupta; Atul Sharma; Amit Agrawal; Mark C. Thompson; Kerry Hourigan (Journal of Marine Science and Engineering, 2023)
In the present two-dimensional numerical study, we investigate the roles of geometrical parameters of a hydrofoil (shape/curvature of the leading and trailing edges and thickness) and kinematic parameters (phase difference between heave and pitch (ϕ)) on the propulsive performance of different-shaped hydrofoils oscillating at maximum angles of attack up to αmax=30∘. The study was carried out at a fixed non-dimensional maximum heave to chord ratio h∘/C=0.75, Strouhal number St=0.25, and Reynolds number Re=5000. Our findings reveal that hydrofoil performance and stability improve with leading and trailing edge curvatures but decline as thickness increases. By analyzing the near-wake structure, we establish that even minimal flow separation increases power consumption while moderate flow separation enhances thrust. Over the range of different-shaped hydrofoils at different αmax and ϕ, maximum propulsion efficiency occurs for those parameters for which there is a small degree of flow separation but with no roll-up of a separating vortex. In comparison, maximum thrust generation occurs when there is a moderately strong flow separation but without induction of a significant amount of fluid around the trailing edge. These insights offer valuable knowledge for understanding fish propulsion efficiency and have applications in designing autonomous underwater vehicles (AUVs) and micro-air vehicles (MAVs).

End of life management of crystalline silicon and cadmium telluride photovoltaic modules utilising life cycle assessment - Shweta Singh; Satvasheel Powar; Atul Dhar (Resources, Conservation and Recycling, 2023)

Molecular fossil chronicles and geochemical probes of Paleogene coals from Meghalaya, India - Tushar Adsul; Molly D. O'Beirne; Santanu Ghosh; Josef P. Werne; Devleena Mani; Sudip Bhattacharyya; Atul Kumar Varma (Organic Geochemistry, 2023)

Discovery of differentially expressed novel miRNAs in breast normal cells and their putative targets - Mohd Shuaib; Kumari Sunita Prajapati; Atul Kumar Singh; Shashank Kumar (Molecular and Cellular Biochemistry, 2023)

Whole-Blood Metabolomics of a Rat Model of Repetitive Concussion - Ahmad Raza Khan; Samiya Zehra; Atul Kumar Baranwal; Dinesh Kumar; Raisuddin Ali; Saleem Javed; Kamlesh Bhaisora (Journal of Molecular Neuroscience, 2023)

Fruit peel bioactives, valorisation into nanoparticles and potential applications: A review - Rajat Suhag; Rohit Kumar; Atul Dhiman; Arun Sharma; Pramod K. Prabhakar; Krishna Gopalakrishnan; Ritesh Kumar; Anurag Singh (Critical Reviews in Food Science and Nutrition, 2023)

Evolutionary analysis of all eleven genes of species C rotaviruses circulating in humans and domestic animals - Madhuri S. Joshi; Atul M. Walimbe; Shalu A. Arya; Varanasi Gopalkrishna (Molecular Phylogenetics and Evolution, 2023)

Interlaboratory study: Testing reproducibility of solid biofuels component identification using reflected light microscopy - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Tushar Adsul; Neža Malenšek Andolšek; Omid Haeri Ardakani; Tara Congo; Batbold Demberelsuren; Bryon S. Donohoe; Ashley Douds; Deolinda Flores; et al. (International Journal of Coal Geology, 2023)

Efficacy of nanoparticles against purple blotch (Alternaria porri) of onion - G. Chaithanya; Atul Kumar; D. Vijay; Praveen Kumar Singh; Zakir Hussain; Sudipta Basu; Sandeep Kumar Lal (Indian Phytopathology, 2023)

Association of inhibitory NKG2A and activating NKG2D natural killer cell receptor genes with resistance to SARS-CoV-2 infection in a western Indian population - Anuradha S. Tripathy; Priyanka Wagh; Kadambari Akolkar; Atul M. Walimbe; Varsha A. Potdar; Manohar Lal Choudhary; Nalini Kadgi; Leena Nakate; Priya Abraham (Archives of Virology, 2023)

Unfolding the Chemical composition, antioxidant and antibacterial activities of Drymaria cordata (Linn.) Willd. against chloramphenicol-resistant Bacillus subtilis and β-lactams-resistant Pseudomonas aeruginosa - Atul Arya; Suresh Kumar; Dolly Kain; Ab Majeed Ahanger; Amrita Suryavanshi; Vandana (Vegetos, 2023)

Evaluating the issue of sustainable tourism with a system dynamic approach: evidence from Uttarakhand, India - Atul Rawat; Shivam Joshi; Sushil Kumar Rai (Environment, Development and Sustainability, 2023)

Splitter plate-based flow control study for two square cylinders in tandem arrangement - Prabir Sikdar; Sunil Manohar Dash; Kalyan Prasad Sinhamahapatra; Atul Sharma (Ocean Engineering, 2023)

Environmental and economic assessment of waste collection and transportation using LCA: A case study - Yash Aryan; Atul Kumar; Subham; Sukha Ranjan Samadder (Environmental Research, 2023)

Global co-occurrences of multi-(emerging)-contaminants in the hotspots of arsenic polluted groundwater: A pattern of menace - Manish Kumar; Nilotpal Das; Sachin Tripathi; Atul Verma; Pawan Kumar Jha; Prosun Bhattacharya; Jürgen Mahlknecht (Current Opinion in Environmental Science & Health, 2023)

Transient response to perturbations in flow synthesis of citrate capped gold nanoparticles - Atul H. Bari; Neerja Shukla; Asterios Gavriilidis; Amol A. Kulkarni (Chemical Engineering Journal, 2023)

Design, synthesis, and pharmacological evaluation of [1, 3] dioxolo-chromeno[2,3-b]pyridines as anti-seizure agents - Visarapu Malathi; Nissi Sharon; Pannala Padmaja; Deepak Lokwani; Saurabh Khadse; Prashant Chaudhari; Atul A. Shirkhedkar; Pedavenkatagari Narayana Reddy; Vinod G. Ugale (Molecular Diversity, 2023)

Performance Evaluation of Hydro-Estimator Technique-Based Rain Products from INSAT-3DR During Indian Summer Monsoon 2020 - Amit Kumar; Neerja Sharma; Atul Kumar Varma; S. C. Bhan (Journal of the Indian Society of Remote Sensing, 2023)

Experimental analysis of solar air heater duct with discrete arc-pattern combined staggered element roughness on absorber plate - Sanjeev Kumar Yadav; Atul Lanjewar (Environment, Development and Sustainability, 2023)

Investigation of barriers and mitigation strategies to blockchain technology implementation in construction industry: an interpretive structural modeling approach - Atul Kumar Singh; Varadhaiya Gounder Ranganathan Pras Kumar; Jin Hu; Muhammad Irfan (Environmental Science and Pollution Research, 2023)

Analysis of atmospheric and oceanic conditions during unusual occurrence of tropical cyclone Gulab and Shaheen in North Indian Ocean - Neeru Jaiswal; M Jishad; Sanjib K Deb; Atul K Varma; Neeraj Agarwal; Rashmi Sharma (Journal of Earth System Science, 2023)

Flavonoids as omnipotent candidates for cancer management - Pallavi Chand; Hitesh Kumar; Rupshee Jain; Atul Jain; Vikas Jain (South African Journal of Botany, 2023)

Occurrence, spatio-temporal variation and ecological risk assessment of benzotriazole ultraviolet stabilizers (BUVs) in water and sediment of rivers in central India - Ankur Khare; Pradip Jadhao; Shatabdi Kawre; Gajanan Kanade; Mahendra Patil; Atul Narayan Vaidya; Asirvatham Ramesh Kumar (Science of The Total Environment, 2023)

Reply to the comments by Dr. Janusz Olszak on “Luminescence chronology of the Sankosh river terraces in the Assam–Buthan foothills of the Himalayas: Implications to climate and tectonics” by Quaternary Geochronology 72, 101364 - Belligraham Narzary; Atul K. Singh; Sribas Malik; Mahadev; Manoj K. Jaiswal (Quaternary Geochronology, 2023)

Potential of biogenic and non-biogenic waste materials as flocculant for algal biomass harvesting: Mechanism, parameters, challenges and future prospects - Har Mohan Singh; Mriduta Sharma; V.V. Tyagi; Kajol Goria; D. Buddhi; Atul Sharma; Frank Bruno; Shane Sheoran; Richa Kothari (Journal of Environmental Management, 2023)

The prominence of carbon capture, utilization and storage technique, a special consideration on India - Atul Kumar Patidar; Rahul Kumar Singh; Tanupriya Choudhury (Gas Science and Engineering, 2023)

Characterization of piggery farm waste-borne bacterial transposable elements associated with antimicrobial resistance phenotypes - Priyanka Kumari Thakur; Rajib Deb; Seema Rani Pegu; Ranjeet Parihar; Jagana Niharika; Pranab Jyoti Das; Gyanendra Singh Sengar; Joyshikh Sonowal; Parul Chaudhary; Arutkumaran Selvaradjou; Atul Raj; Vivek Kumar Gupta (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Assessing the role of ACC deaminase-producing bacteria in alleviating salinity stress and enhancing zinc uptake in plants by altering the root architecture of French bean (Phaseolus vulgaris) plants - Shikha Gupta; Sangeeta Pandey; Vashista Kotra; Atul Kumar (Planta, 2023)

Naringin dihydrochalcone potentially binds to catalytic domain of matrix metalloproteinase-2: molecular docking, MM-GBSA, and molecular dynamics simulation approach - Atul Kumar Singh; Shashank Kumar (Natural Product Research, 2023)

Investigating the barriers to the adoption of blockchain technology in sustainable construction projects - Atul Kumar Singh; V.R. Prasath Kumar; Gholamreza Dehdasht; Saeed Reza Mohandes; Patrick Manu; Farzad Pour Rahimian (Journal of Cleaner Production, 2023)

Environmental drivers inducing habitat expansion and shift of introduced alien trout in the Himalayan ecosystem and management concerns - Atul K. Singh; Sharad C. Srivastava (Journal for Nature Conservation, 2023)

Financial viability of hydrogen-enriched gas produced adopting air-steam gasification for power generation: A detailed comparative study and sensitivity analysis with air gasification systems - Narasimhan Kodanda Ram; Perumal Raman; Adeel Khan; Atul Kumar (Bioresource Technology Reports, 2023)

Contamination of Natural Water and Health Risk Assessment in Western Himalayan Region, India - Vandana Sethi; Atul Kumar; Yogesh Kumar Walia (Water, Air, & Soil Pollution, 2023)

A multi-model forecasting approach for solid waste generation by integrating demographic and socioeconomic factors: a case study of Prayagraj, India - Atul Srivastava; Pawan Kumar Jha (Environmental Monitoring and Assessment, 2023)

Multi-functional auto-fluorescent nanogels for theranostics - Arti Vashist; Andrea D. Raymond; Prem Chapagain; Atul Vashist; Adriana Yndart Arias; Nagesh Kolishetti; Madhavan Nair (Journal of NeuroVirology, 2023)
Here in the present article, the state of art for nanotechnology-enabled nanogel theranostics and the upcoming concepts in nanogel-based therapeutics are summarized. The benefits, innovation, and prospects of nanogel technology are also briefly presented.

Interactive effects of the El Niño-Southern Oscillation and Indian Ocean Dipole on the tropical net ecosystem productivity - Ran Yan; Jun Wang; Weimin Ju; Daniel S. Goll; Atul K. Jain; Stephen Sitch; Hanqin Tian; Poulter Benjamin; Fei Jiang; Hengmao Wang (Agricultural and Forest Meteorology, 2023)

Cardiac safety profile of type II kinase inhibitors: Analysis of post-marketing reports from databases of European Medicine Agency & World Health Organization - Atul Khurana; Mandeep Kumar Arora; Harikesh Dubey (DARU Journal of Pharmaceutical Sciences, 2023)

A numerical study on breakup of a liquid jet in an axial electric field - Dev S. Hathi; Pratik M. Panchal; Atul Sharma; Rochish Thaokar; Absar M. Lakdawala (Journal of Aerosol Science, 2023)

A pathway for multi-stage cyclone-induced hazard tracking—case study for Yaas - Atul Kumar Varma; Neeru Jaiswal; Ayan Das; Mukesh Kumar; Nikhil V. Lele; Rojalin Tripathy; Saroj Maity; Mehul Pandya; Bimal Bhattacharya; Anup Kumar Mandal; M. Jishad; M. Seemanth; et al. (Natural Hazards, 2023)

Seismic fragility estimation of cable-stayed bridges with various pylon shapes considering soil-pile interaction - Jigar P. Variyavwala; Kaushik M. Gondaliya; Atul K. Desai; Ehsan Noroozinejad Farsangi (Bulletin of Earthquake Engineering, 2023)

Skeletal and cardiac muscle have different protein turnover responses in a model of right heart failure - Danielle R. Bruns; Benjamin D. McNair; Frederick F. Peelor; Agnieszka K. Borowik; Atul Pranay; Aykhan Yusifov; Benjamin F. Miller (GeroScience, 2023)

Trends in extreme climate indices in Cherrapunji for the period 1979 to 2020 - Raju Kalita; Dipangkar Kalita; Atul Saxena (Journal of Earth System Science, 2023)

Does human capital complement sustainable development goals? Evidence from leading carbon emitter countries - Ahmad Haseeb Payab; Pradeep Kautish; Rajesh Sharma; Aaliyah Siddiqui; Atul Mehta; Mujahid Siddiqui (Utilities Policy, 2023)

Inter-seasonal characterization and correlation of Surface Urban Heat Island (SUHI) and Canopy Urban Heat Island (CUHI) in the urbanized environment of Delhi - Atul Kumar; Mahua Mukherjee; Ajanta Goswami (Remote Sensing Applications: Society and Environment, 2023)

The loss of cardiac SIRT3 decreases metabolic flexibility and proteostasis in an age-dependent manner - Ping Li; Maria F. Newhardt; Satoshi Matsuzaki; Craig Eyster; Atul Pranay; Frederick F. Peelor; Albert Batushansky; Caroline Kinter; Kumar Subramani; Sandeep Subrahmanian; Jasimuddin Ahamed; Pengchun Yu; et al. (GeroScience, 2023)
SIRT3 is a longevity factor that acts as the primary deacetylase in mitochondria. Although ubiquitously expressed, previous global SIRT3 knockout studies have shown primarily a cardiac-specific phenotype. Here, we sought to determine how specifically knocking out SIRT3 in cardiomyocytes (SIRTcKO mice) temporally affects cardiac function and metabolism. Mice displayed an age-dependent increase in cardiac pathology, with 10-month-old mice exhibiting significant loss of systolic function, hypertrophy, and fibrosis. While mitochondrial function was maintained at 10 months, proteomics and metabolic phenotyping indicated SIRT3 hearts had increased reliance on glucose as an energy substrate. Additionally, there was a significant increase in branched-chain amino acids in SIRT3cKO hearts without concurrent increases in mTOR activity. Heavy water labeling experiments demonstrated that, by 3 months of age, there was an increase in protein synthesis that promoted hypertrophic growth with a potential loss of proteostasis in SIRT3cKO hearts. Cumulatively, these data show that the cardiomyocyte-specific loss of SIRT3 results in severe pathology with an accelerated aging phenotype.

Identification of environmental stress parameters to study the natural colour change of water in highly saline inland Crater Lake at Lonar, India - Atul Maldhure; Anupama Rodge; Anjali Kothe; Pranav Nagarnaik; Gajanan Khadse; Amit Bafana; Mahesh Kumar; Pawan Labhasetwar (Environmental Monitoring and Assessment, 2023)

Antioxidant additive melatonin in tris-based egg yolk extender improves post-thaw sperm attributes in Hariana bull - Dileep Kumar Yadav; Anuj Kumar; Shashikant Gupta; Pratishtha Sharma; Gyanesh Kumar; Vikas Sachan; Brijesh Yadav; Sarvajeet Yadav; Atul Saxena; Dilip Kumar Swain (Animal Reproduction Science, 2023)

Trace and rare earth elements in the Permian shales: geochemical paradigms - Balram Tiwari; Santanu Ghosh; Susheel Kumar; Atul Kumar Varma (Arabian Journal of Geosciences, 2023)

Kinetic proteomics identifies targeted changes in liver metabolism and the ribo-interactome by dietary sulfur amino acid restriction - William O. Jonsson; Agnieszka K. Borowik; Atul Pranay; Michael T. Kinter; Emily T. Mirek; Jordan L. Levy; Elizabeth M. Snyder; Benjamin F. Miller; Tracy G. Anthony (GeroScience, 2023)
Dietary sulfur amino acid restriction (SAAR) protects against diet-induced obesity, extends healthspan, and coincides with an overall reduction in hepatic protein synthesis. To explore the underpinnings of SAAR-induced slowed growth and its impact on liver metabolism and proteostasis, we resolved changes in hepatic mRNA and protein abundances and compared synthesis rates of individual liver proteins. To achieve this, adult male mice were provided deuterium-labeled drinking water while freely consuming either a regular-fat or high-fat diet that was SAA restricted. Livers from these mice and their respective dietary controls were used to conduct transcriptomic, proteomic, and kinetic proteomic analyses. We found that remodeling of the transcriptome by SAAR was largely agnostic to dietary fat content. Shared signatures included activation of the integrated stress response alongside alterations in metabolic processes impacting lipids, fatty acids, and amino acids. Changes to the proteome correlated poorly with the transcriptome, and yet, functional clustering of kinetic proteomic changes in the liver during SAAR revealed that the management of fatty acids and amino acids were altered to support central metabolism and redox balance. Dietary SAAR also strongly influenced the synthesis rates of ribosomal proteins and ribosome-interacting proteins regardless of dietary fat. Taken together, dietary SAAR alters the transcriptome and proteome in the liver to safely manage increased fatty acid flux and energy use and couples this with targeted changes in the ribo-interactome to support proteostasis and slowed growth.

Origanum vulgare manganese ferrite nanocomposite: An advanced multifunctional hybrid material for dye remediation - Arshi Choudhry; Atul Sharma; Sharf Ilahi Siddiqui; Irshad Ahamad; Md Sajid; Tabrez Alam Khan; Saif Ali Chaudhry (Environmental Research, 2023)

Adsorption and Desorption Study of Reusable Magnetic Iron Oxide Nanoparticles Modified with Justicia adhatoda Leaf Extract for the Removal of Textile Dye and Antibiotic - Nikita Ghosh; Subhadeep Sen; Goutam Biswas; Atul Saxena; Prabir Kumar Haldar (Water, Air, & Soil Pollution, 2023)

Ethnopharmacological survey of indigenous medicinal plants of Palampur, Himachal Pradesh in north-western Himalaya, India - Atul Arya; Suresh Kumar; Rajinder Paul; Amrita Suryavanshi; Dolly Kain; Rudra Narayan Sahoo (Advances in Traditional Medicine, 2023)

Association of antibiotics and heavy metal arsenic to horizontal gene transfer from multidrug-resistant clinical strains to antibiotic-sensitive environmental strains - Ashish Kothari; Prashant Kumar; Amit Gaurav; Karanvir Kaushal; Atul Pandey; Shashi Ranjan Mani Yadav; Neeraj Jain; Balram Ji Omar (Journal of Hazardous Materials, 2023)

A review on S-scheme and dual S-scheme heterojunctions for photocatalytic hydrogen evolution, water detoxification and CO2 reduction - Amit Kumar; Atul Khosla; Sunil Kumar Sharma; Pooja Dhiman; Gaurav Sharma; Lalitha Gnanasekaran; Mu. Naushad; Florian J. Stadler (Fuel, 2023)

An Algorithm for the Retrieval of Ocean Surface Precipitation from SCATSAT-1 Measurements - Atul Kumar Varma; Abhisek Chakraborty (Journal of the Indian Society of Remote Sensing, 2023)

Geospatial multi-criteria evaluation to identify groundwater potential in a Himalayan District, Rudraprayag, India - Atul Kumar; Malay Pramanik; Shairy Chaudhary; Mahabir Singh Negi; Sylvia Szabo (Environment, Development and Sustainability, 2023)

Andrographolide-Soya-L-α-Phosphatidyl Choline Complex Augmented Solubility and Drug Delivery in Leishmania donovani, a Causative Agent for Cutaneous and Visceral Leishmaniasis - Purva Pingle; Atul Mourya; Madhulika Namdeo; Katta Chanti Babu; Harithasree Veerabomma; Radheshyam Maurya; Pankaj Kumar Singh; Neelesh Kumar Mehra; Saurabh Srivastava; Jitender Madan (AAPS PharmSciTech, 2023)

Experimental testing of solar-based air heater roughed with discrete V-down rib and staggered element - Piyush Kumar Jain; Atul Lanjewar; Prem Kumar Chaurasiya; Damodar Tiwari; Vinod Kumar Sharma (Environmental Science and Pollution Research, 2023)

Chlorophyll fluorescence and antioxidants activity as influenced by zinc nutrition in wheat under late sown conditions - Dheeraj Chatti; Atul Kumar (Vegetos, 2023)

Assessing thermo-physical products’ efficiency in the building and construction industry: a bibliometric analysis approach - Atul Kumar Singh; Sharath Chandra Sathvik; Loganathan Krishnaraj; Muhammad Irfan; Varudhaiya Ranganath Prasath Kumar; Cem Işik (Environmental Science and Pollution Research, 2023)

Morphological and elemental tuning of BiOCl/BiVO4 heterostructure for uric acid electrochemical sensor and antibiotic photocatalytic degradation - Pandiyarajan Anand; Atul Verma; Yi-An Hong; Anren Hu; Dhayanantha Prabu Jaihindh; Ming-Show Wong; Yen-Pei Fu (Chemosphere, 2023)

Unravelling the causes of 2015 winter monsoon extreme rainfall and floods over Chennai: Influence of atmospheric variability and urbanization on the hydrological cycle - Rakesh Teja Konduru; G. Mrudula; Vivek Singh; Atul Kumar Srivastava; Abhay K. Singh (Urban Climate, 2023)

Laminating STRATH block chain technology- SWOT architectures to endure business strategy between digital transformation, firms and supply chains capabilities for sustainability - Atul Kumar Sahu; Nitin Kumar Sahu; Anoop Kumar Sahu (Journal of Cleaner Production, 2023)

Association of underlying comorbidities and progression of COVID-19 infection amongst 2586 patients hospitalised in the National Capital Region of India: a retrospective cohort study - Rashmi Rana; Vivek Ranjan; Naveen Kumar; Parul Chugh; Kamini Khillan; Atul Gogia; Devinder Singh Rana; Nirmal Kumar Ganguly (Molecular and Cellular Biochemistry, 2023)

Microbial biofilms are shaped by the constant dialogue between biological and physical forces in the extracellular matrix - Lan Li Wong; Sudarsan Mugunthan; Binu Kundukad; James Chin Shing Ho; Scott A. Rice; Jamie Hinks; Thomas Seviour; Atul N. Parikh; Staffan Kjelleberg (Environmental Microbiology, 2023)

An approach for selection of solid waste treatment and disposal methods based on fuzzy analytical hierarchy process - Amarjeet Kumar; Atul Sharma; Nekram Rawal (Waste Disposal & Sustainable Energy, 2022)

Evaluation and Development of a Predictive Model for Geophysical Well Log Data Analysis and Reservoir Characterization: Machine Learning Applications to Lithology Prediction - Aditya Mishra; Anjali Sharma; Atul Kumar Patidar (Natural Resources Research, 2022)

Morpho-pathological characterization of Sarocladium oryzae causing sheath rot in paddy - M. G. Venkatesh; Atul Kumar; Sandeep Kumar Lal; Bishnu Maya Bashyal; Prolay Kumar Bhowmick; S. C. Dubey; Dinesh Singh; Nagamani Sandra; Shaily Javeria (Indian Phytopathology, 2022)

Relative performance of fungicides and crude leaf extract of Azadirachta indica against leaf blight of onion - Anju Bala Sharma; Atul Kumar; Anjali Sidhu (Indian Phytopathology, 2022)

Geochemical and petrographical fingerprints of coal bed methane potential in the Son-valley Basin, India - Susheel Kumar; Atul Kumar Varma; Vinod Atmaram Mendhe; Shikhar Kumar; Uday Bhan (Arabian Journal of Geosciences, 2022)

Modified Hydro-Estimator: Pixel-Scale Instantaneous Measurement of Precipitation from Indian Geostationary Satellites - Atul Kumar Varma; Neerja Sharma (Journal of the Indian Society of Remote Sensing, 2022)

Northward propagation of convection over Arabian Sea and Bay of Bengal: a perspective from vorticity equation - Nirupam Karmakar; Susmitha Joseph; Atul Kumar Sahai (Climate Dynamics, 2022)

Performance evaluation of an industrial solar dryer in Indian scenario: a techno-economic and environmental analysis - Ankit Srivastava; Abhishek Anand; Amritanshu Shukla; Anil Kumar; Atul Sharma (Clean Technologies and Environmental Policy, 2022)

Identification and Annotation of Peptide Allergens in Prunus dulcis - Arshwinder Singh; Atul Kumar Upadhyay (International Journal of Peptide Research and Therapeutics, 2022)

Mechanistic understanding and potential application of electrospraying in food processing: a review - Atul Dhiman; Rajat Suhag; Arashdeep Singh; Pramod K. Prabhakar (Critical Reviews in Food Science and Nutrition, 2022)

Sex-Dependent Alterations in the mRNA Expression of Enzymes Involved in Dopamine Synthesis and Breakdown After Methamphetamine Self-Administration - Aaron E. Miller; Atul P. Daiwile; Jean Lud Cadet (Neurotoxicity Research, 2022)

p-Coumaric acid protects against D-galactose induced neurotoxicity by attenuating neuroinflammation and apoptosis in mice brain - Pratibha Atul Daroi; Shrikant Ninaji Dhage; Archana Ramesh Juvekar (Metabolic Brain Disease, 2022)

A study of rapid intensification of tropical cyclone Ockhi using C-band polarimetric radar - Sambit Kumar Panda; Anup Kumar Mandal; Bipasha Paul Shukla; Neeru Jaiswal; Chandra Mohan Kishtawal; Atul Kumar Varma (Meteorology and Atmospheric Physics, 2022)

Converting the genomic knowledge base to build protein specific machine learning prediction models; a classification study on thermophilic serine protease - Jithin S. Sunny; Atul Kumar; Khairun Nisha; Lilly M. Saleena (Biologia, 2022)

Issues on the inclusion of Puntius denisonii (Day), a freshwater ornamental fish of global value, as Schedule-I species under the Wild Life (Protection) Amendment Act, 2021 of India - Atul Kumar Jain; T. V. A. Mercy; Abhinika Jain (Frontiers in Marine Science, 2022)
Puntius denisonii is popularly known as Miss Kerala in India or Denison barb or Red line torpedo barb in the global ornamental fish trade. The species is endemic to fast-flowing rivers and streams of the Western Ghats of India. The species was not very popular earlier in aquatic trade but has been in great demand in global aquarium trade since it was exhibited at AQARAMA 1997 in Singapore and ranked third under the new species category. The export of the species from India started in 1996–1997, which increased progressively and constituted about 60%–65% of a total of 1.44 million US$ worth of ornamental fish exported from India in 2007–2008. Thereafter, it started declining and presently became negligible. It was attributed to depleting stocks of P. denisonii in rivers and streams of Western Ghats. The species was recommended to be listed as endangered on the IUCN red list in a CAMP workshop held at NBFGR, Lucknow, India in September 1997, owing to habitat degradation and the declining number of mature individuals in the wild. It was categorized as Vulnerable in 2009 and Endangered in 2015 under the IUCN red list. The Department of Fisheries, Government of Kerala has restricted the collection of smaller size fish from natural water bodies since 2008 to revive wild stocks. The Ministry of Environment, Forest and Climate Change, Government of India has now proposed to include P. denisonii along with two other freshwater fish species, Semiplotus semiplotus (Assamese kingfish) and Osteobrama belangeri (Manipur osteobrama), as Schedule-I species under the Wild Life (Protection) Amendment Act, 2021 of India. The species listed under this Schedule are prohibited to be hunted throughout the country. The captive breeding technology of P. denisonii has already been developed in the country more than a decade back, and fish is being produced commercially at several farms presently including hatcheries of the Kerala Government. The species is also being cultured and produced on a commercial scale by many ornamental fish farmers of Indonesia and supplied to the global ornamental fish trade at cheaper rates, and more color strains. The major factors that are responsible for the depletion of the stocks of P. denisonii and the overall fish biodiversity of Western Ghat regions are discussed in detail. The conflicts and repercussions that will arise because of the inclusion of Denison Barb or any other freshwater fish as Schedule-I species under the Wild Life (Protection) Amendment Act, 2021 of India are also discussed.

High-Altitude Air Pollutants Monitored from Rainwater Chemistry in the Central Himalaya - Deewan Singh Bisht; Atul Kumar Srivastava; Vivek Singh; Suresh Tiwari; Alok Sagar Gautam; Sneha Gautam; M. Santosh; Sanjeev Kumar (Water, Air, & Soil Pollution, 2022)

Contamination level, source identification and health risk evaluation of potentially toxic elements (PTEs) in groundwater of an industrial city in eastern India - Gourisankar Panda; Krishnendu Kumar Pobi; Supratik Gangopadhyay; Manash Gope; Atul Kumar Rai; Sumanta Nayek (Environmental Geochemistry and Health, 2022)

Impact of vertical wind shear in modulating tropical cyclones eye and rainfall structure - Neerja Sharma; Atul Kumar Varma (Natural Hazards, 2022)

Habitat selection of smooth-coated otters (Lutrogale perspicillata) in the peri-coastal, urbanised landscape of Goa, India - Stephen Jonah Dias; Patrick James Ciaran White; Atul Sinai Borker; Nandini Vaz Fernandes (Mammal Research, 2022)
Human development can have detrimental impacts on the environment and its contained ecosystems. However, several species have adapted to thrive in human-modified landscapes. This study was aimed to assess habitat selection of threatened smooth-coated otters ( Lutrogale perspicillata ) in the peri-coastal landscape of Goa, India. In the Indian context, there are significant gaps in knowledge pertaining to factors that influence otter occurrence in such environments. Otter presence/absence in 78 1 km 2 plots across two river catchments was modelled against several habitat variables including measures of agricultural pollution, salinity, mangrove cover, and fishing presence. The effect size and direction of relationships between the probability of otter occurrence and the habitat variables were analysed by building a set of candidate generalised linear models. The models were subsequently ranked using small-sample Akaike’s information criterion (AICc). Analysis indicated that water salinity, mangrove cover, and fishing presence had a significant positive influence on otter occurrence. However, the concentrations of agricultural pollutants (nitrates, phosphates, and sulphates) were not contributing factors in influencing otter occurrence in the surveyed landscape. The metrics used in this study can be applied for preliminary assessments of presence and occupancy of otters in other coastal landscapes of India, and aid in the conservation of the species.

Microplastic properties and their interaction with hydrophobic organic contaminants: a review - Archana Prajapati; Atul Narayan Vaidya; Asirvatham Ramesh Kumar (Environmental Science and Pollution Research, 2022)

Withania somnifera phytochemicals possess SARS-CoV-2 RdRp and human TMPRSS2 protein binding potential - Kumari Sunita Prajapati; Atul Kumar Singh; Prem Prakash Kushwaha; Mohd Shuaib; Santosh Kumar Maurya; Sanjay Gupta; Sabyasachi Senapati; Surya Pratap Singh; Mohammad Waseem; Shashank Kumar (Vegetos, 2022)

Advances in methodologies for seismic time history analysis for safety of offshore modular platform foundation in cohesive soil by 3D FEM - Arpit A. Parikh; Atul K. Desai; Shailesh R. Gandhi (Arabian Journal of Geosciences, 2022)

Exploring the nexus between environment quality, economic development and industrialization in BRICS nations: the role of technological innovation and income inequality - Sushil Kumar Rai; Atul Rawat (Environmental Science and Pollution Research, 2022)

Multi-residue determination of pesticides in vegetables and assessment of human health risks in Western Himalayan region of India - Neelam Sharma; Atul Kumar; Siddhartha Singh; Suresh Kumar; Robin Joshi (Environmental Monitoring and Assessment, 2022)

Raloxifene-loaded SLNs with enhanced biopharmaceutical potential: QbD-steered development, in vitro evaluation, in vivo pharmacokinetics, and IVIVC - Atul Jain; Teenu Sharma; Rajendra Kumar; O. P. Katare; Bhupinder Singh (Drug Delivery and Translational Research, 2022)

Experimental study of thermal characteristics of ZrO2/EG nanofluid for application of heat transfer - Rohinee M. Barai; Devesh Kumar; Atul V. Wankhade; Aamir R. Sayed; Anup A. Junankar (Environmental Science and Pollution Research, 2022)

Modelling the deformation behaviour of an unsaturated soil reinforced with geocell for different freezing–thawing cycles - Bhavita Subhashbhai Dave; Chandresh H. Solanki; Atul K. Desai (Innovative Infrastructure Solutions, 2022)

SARS-CoV-2-associated haemorrhagic encephalitis mimicking Herpes encephalitis - Rahul Handa; Satyan Nanda; Atul Prasad; Rajiv Anand; Man Mohan Mehndiratta; Dhruv Zutshi; Aarti Pahuja; Rajesh Kumar Pandey; Payal Mittal; Sachal Sharma; Sujata K Dass; Prabhjeet Kaur Bedi; et al. (Journal of NeuroVirology, 2022)

Effect of expansion of human umbilical cord blood CD34 + cells on neurotrophic and angiogenic factor expression and function - Ashalyn P. Watt; Mark Kirkland; Lakshmi Nekkanti; Yen Pham; Courtney McDonald; Atul Malhotra; Guy Moeneclaey; Suzanne L. Miller; Graham Jenkin (Cell and Tissue Research, 2022)
The use of CD34 + cell-based therapies has largely been focused on haematological conditions. However, there is increasing evidence that umbilical cord blood (UCB) CD34 + -derived cells have neuroregenerative properties. Due to low cell numbers of CD34 + cells present in UCB, expansion is required to produce sufficient cells for therapeutic purposes, especially in adults or when frequent applications are required. However, it is not known whether expansion of CD34 + cells has an impact on their function and neuroregenerative capacity. We addressed this knowledge gap in this study, via expansion of UCB-derived CD34 + cells using combinations of LDL, UM171 and SR-1 to yield large numbers of cells and then tested their functionality. CD34 + cells expanded for 14 days in media containing UM171 and SR-1 resulted in over 1000-fold expansion. The expanded cells showed an up-regulation of the neurotrophic factor genes BDNF, GDNF, NTF-3 and NTF-4, as well as the angiogenic factors VEGF and ANG. In vitro functionality testing showed that these expanded cells promoted angiogenesis and, in brain glial cells, promoted cell proliferation and reduced production of reactive oxygen species (ROS) during oxidative stress. Collectively, this study showed that our 14-day expansion protocol provided a robust expansion that could produce enough cells for therapeutic purposes. These expanded cells, when tested in in vitro, maintained functionality as demonstrated through promotion of cell proliferation, attenuation of ROS production caused by oxidative stress and promotion of angiogenesis.

A telephonic survey of health-related quality of life of outpatient department dropout Parkinson’s disease patients during the COVID-19 pandemic - Atul Goel; Sunil K. Narayan; Ramkumar Sugumaran (Acta Neurologica Belgica, 2022)

Using interview surveys and multispecies occupancy models to inform vertebrate conservation - Rajeev Pillay; David A. W. Miller; R. Raghunath; Atul A. Joshi; Charudutt Mishra; A. J. T. Johnsingh; M. D. Madhusudan (Conservation Biology, 2022)
Species distribution data are an essential biodiversity variable requiring robust monitoring to inform wildlife conservation. Yet, such data remain inherently sparse because of the logistical challenges of monitoring biodiversity across broad geographic extents. Surveys of people knowledgeable about the occurrence of wildlife provide an opportunity to evaluate species distributions and the ecology of wildlife communities across large spatial scales. We analyzed detection histories of 30 vertebrate species across the Western Ghats biodiversity hotspot in India, obtained from a large‐scale interview survey of 2318 people who live and work in the forests of this region. We developed a multispecies occupancy model that simultaneously corrected for false‐negative (non‐detection) and false‐positive (misidentification) errors that interview surveys can be prone to. Using this model, we integrated data across species in composite analyses of the responses of functional species groups (based on disturbance tolerance, diet, and body mass traits) to spatial variation in environmental variables, protection, and anthropogenic pressures. We observed a positive association between forest cover and the occurrence of species with low tolerance of human disturbance. Protected areas were associated with higher occurrence for species across different functional groups compared with unprotected lands. We also observed the occurrence of species with low disturbance tolerance, herbivores, and large‐bodied species was negatively associated with developmental pressures, such as human settlements, energy production and mining, and demographic pressures, such as biological resource extraction. For the conservation of threatened vertebrates, our work underscores the importance of maintaining forest cover and reducing deforestation within and outside protected areas, respectively. In addition, mitigating a suite of pervasive human pressures is also crucial for wildlife conservation in one of the world's most densely populated biodiversity hotspots.

Eco-friendly management of seed discolouration of paddy - Praveen S. Patted; Atul Kumar; Sandeep Kumar Lal; Shyamal K. Chakrabarty; Bishnu Maya Bashyal; Ranjit Ranjan Kumar; Prolay Kumar Bhaumick; Shaily Javeria (Indian Phytopathology, 2022)

A critical review on different roughness geometries and their effect on heat transfer and friction factor - Sumer Singh Patel; Atul Lanjewar (Environmental Science and Pollution Research, 2022)

Watershed prioritization for soil erosion mapping in the Lesser Himalayan Indian basin using PCA and WSA methods in conjunction with morphometric parameters and GIS-based approach - Atul Kumar; Sunil Singh; Malay Pramanik; Shairy Chaudhary; Ashwani Kumar Maurya; Manoj Kumar (Environment, Development and Sustainability, 2022)

Bioaccumulation and Toxicity of As in the Alga Chlorococcum sp.: Prospects for As Bioremediation - Atul Kumar Upadhyay; Lav Singh; Ranjan Singh; D. P. Singh; Gauri Saxena (Bulletin of Environmental Contamination and Toxicology, 2022)

Modelling suspended sediment concentration and discharge relationship using neural network and adaptive neuro-fuzzy inference system - Atul Kumar Rahul; Nikita Shivhare; Sujeet Kumar; Shyam Bihari Dwivedi; Prabhat Kumar Singh Dikshit (Arabian Journal of Geosciences, 2022)

Functional group chemistry and its functions in coal carbonization: a scientific intelligence from infrared spectroscopy - Debadatta Sen; Santanu Ghosh; Atul Kumar Varma (Arabian Journal of Geosciences, 2022)

Unexplored nutritive potential of tomato to combat global malnutrition - Sanskriti Vats; Ruchi Bansal; Nitika Rana; Surbhi Kumawat; Vacha Bhatt; Pravin Jadhav; Vijay Kale; Atul Sathe; Humira Sonah; Ravin Jugdaohsingh; Tilak Raj Sharma; Rupesh Deshmukh (Critical Reviews in Food Science and Nutrition, 2022)

Biomedical waste generation and management during COVID-19 pandemic in India: challenges and possible management strategies - Ashish Dehal; Atul Narayan Vaidya; Asirvatham Ramesh Kumar (Environmental Science and Pollution Research, 2022)

Land evaluation and sustainable development of ecotourism in the Garhwal Himalayan region using geospatial technology and analytical hierarchy process - Shairy Chaudhary; Atul Kumar; Malay Pramanik; Mahabir Singh Negi (Environment, Development and Sustainability, 2022)

Functional characterization of a high‐affinity iron transporter ( PiFTR ) from the endophytic fungus Piriformospora indica and its role in plant growth and development - Nidhi Verma; Om Prakash Narayan; Durga Prasad; Abhimanyu Jogawat; Sneh Lata Panwar; Meenakshi Dua; Atul Kumar Johri (Environmental Microbiology, 2022)
Summary Iron (Fe) is a micronutrient required for plant growth and development; however, most Fe forms in soil are not readily available to plants, resulting in low Fe contents in plants and, thereby, causing Fe deficiency in humans. Biofortification through plant‐fungal co‐cultivation might be a sustainable approach to increase crop Fe contents. Therefore, we aimed to examine the role of a Piriformospora indica Fe transporter on rice Fe uptake under low Fe conditions. A high‐affinity Fe transporter ( PiFTR ) from P . indica was identified and functionally characterized. PiFTR fulfilled all criteria expected of a functional Fe transporter under Fe‐limited conditions. Additionally, PiFTR expression was induced when P . indica was grown under low Fe conditions, and PiFTR complemented a yeast mutant lacking Fe transport. A knockdown (KD) P . indica strain was created via RNA interference to understand the physiological role of PiFTR . We observed that the KD‐ PiFTR ‐ P . indica strain transported a significantly lower amount of Fe to colonized rice ( Oryza sativa ) than the wild type (WT) P . indica . WT P . indica ‐colonized rice plants were healthier and performed significantly better than KD‐ PiFTR ‐ P . indica‐colonized rice plants. Our study offers potential avenues for an agronomically sound amelioration of plant growth in low Fe environments.

Predicting blast-induced pull using regression tree - Aditya Rana; Narayan Kumar Bhagat; Atul Singh; Pradeep Kumar Singh (Arabian Journal of Geosciences, 2022)

Genomic characterization of ZIP genes in pigeonpea (CcZIP) and their expression analysis among the genotypes with contrasting host response to pod borer - Atul Nag; Kapil Gupta; Neeraj Dubey; Sujit K. Mishra; Jogeswar Panigrahi (Physiology and Molecular Biology of Plants, 2021)

LIPOID SPC-3-Based Coprecipitates for the Enhancement of Aqueous Solubility and Permeability of Ranolazine - Darshan R. Telange; Sarita A. Ukey; Atul T. Hemke; Milind J. Umekar; Anil M. Pethe; Prashant S. Kharkar (Journal of Pharmaceutical Innovation, 2021)

Spatial pattern of groundwater recharge in Jhansi district in the Bundelkhand region, central India - Atul Tiwari; Suneel Kumar Joshi; Shashi Kant Tripathi; Rani Saxena (Environment, Development and Sustainability, 2021)

Mulch Laying Technology for Horticulture in India: A Review - Rohit Namdeo; Atul Kumar Shrivastava (Agricultural Research, 2021)

Decoding trend of Indian summer monsoon rainfall using multimethod approach - Atul Saini; Netrananda Sahu (Stochastic Environmental Research and Risk Assessment, 2021)

Multi-scale pore characterization of Barakar shale in the Mand-Raigarh Basin, India: scientific upshots from geochemical approaches and imaging techniques - Susheel Kumar; Atul Kumar Varma; Vinod Atmaram Mendhe; Balram Tiwari (Arabian Journal of Geosciences, 2021)

Multi-analytical approach of provenance signatures and indication of marine environment in coal and shale bearing sequence from Makum Coalfield, India - Sanki Biswas; Atul Kumar Varma; Madhav Kumar; Binoy K. Saikia (Arabian Journal of Geosciences, 2021)

Carps, Catla catla, Cirrhinus mrigala and Hypophthalmichthys molitrix Are Resistant to Experimental Infection with Tilapia Lake Virus (TiLV) - Pravata Pradhan; Dev Verma; Shrish Yadav; Atul Dev; Thangaraj Swaminathan; Anutosh Paria; Rajendran Valappil; Neeraj Sood (Fishes, 2021)
Tilapia tilapinevirus, also known as tilapia lake virus (TiLV), is an emerging fish virus that primarily affects tilapines. However, the virus has also been detected in a few non-tilapines. As tilapia is generally farmed in polyculture systems along with carps in South Asian countries, there is a likelihood that TiLV-infected tilapia can transmit the virus to the co-cultured species. In view of the above, the susceptibility of three carp species, namely catla (Catla catla), mrigal (Cirrhinus mrigala) and silver carp (Hypophthalmichthys molitrix) was evaluated vis-à-vis tilapia, following experimental infection with TiLV. No clinical signs and histopathological alterations could be observed in carps. RT-qPCR revealed that TiLV copy numbers in liver and brain of all the three carps were almost negligible and did not show any increase with time, suggesting that the virus did not replicate in liver and brain, the target organs of TiLV. Further, TiLV could not be isolated from pooled liver and brain tissues of carps using permissive CFF cell line. On the contrary, in tilapia, typical clinical signs and histopathological lesions were observed and there was significant increase in TiLV copy number up to 6 days post-injection. Furthermore, the virus was successfully isolated from pooled liver and brain tissue of infected tilapia. From the above findings, it could be concluded that C. catla, C. mrigala and H. molitrix are resistant to TiLV infection and unlikely to be carriers for this virus.

Nanoferrites heterogeneous catalysts for biodiesel production from soybean and canola oil: a review - Manish Naagar; Sonia Chalia; Preeti Thakur; S. N. Sridhara; Atul Thakur; P. B. Sharma (Environmental Chemistry Letters, 2021)

Contrasting machine learning regression algorithms used for the estimation of permeability from well log data - Naman Khilrani; Piyush Prajapati; Atul Kumar Patidar (Arabian Journal of Geosciences, 2021)

Changes in morpho-physiological attributes in nine genotypes of linseed (Linum usitatissimum L.) under different level of salt (NaCl) stress - Atul Singh; Shashi Shekhar; Shailesh Marker; P. W. Ramteke (Vegetos, 2021)

Comparing Efficacy of Nano Zinc on Performance, Nutrient Utilization, Immune and Antioxidant Status in Hariana Cattle - Sharish Kumar; Vinod Kumar; Muneendra Kumar; Shalini Vaswani; Raju Kushwaha; Avinash Kumar; Atul Prakash (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Quantum Dots Based Fluorescent Probe for the Selective Detection of Heavy Metal Ions - Akshaya Biranje; Namrah Azmi; Abhishekh Tiwari; Atul Chaskar (Journal of Fluorescence, 2021)

The pylon shape influence on the dynamic response of a cable-stayed bridge for high-speed rail - Jigar P. Variyavwala; Atul K. Desai (Innovative Infrastructure Solutions, 2021)

Pathogenic association of Albifimbria terrestris with rice seeds - Anju Bala Sharma; Atul Kumar; Shaily Javeria (Indian Phytopathology, 2021)

Crop Response to Iron Deficiency is Guided by Cross-Talk Between Phytohormones and their Regulation of the Root System Architecture - Pandurang R. Divte; Poonam Yadav; Atul Bhagawan Pawar; Vasundhara Sharma; Anjali Anand; Raghunath Pandey; Bhupinder Singh (Agricultural Research, 2021)

Detection of aflatoxin M1 in bovine milk from different agro-climatic zones of Chhattisgarh, India, using HPLC-FLD and assessment of human health risks - Ajeet Kumar Pandey; Sanjay Shakya; Anil Patyal; Syed Liaquat Ali; Dhirendra Bhonsle; Choodamani Chandrakar; Atul Kumar; Rizwan Khan; Diksha Hattimare (Mycotoxin Research, 2021)

Assessment of near-surface air pollutants at an urban station over the central Indo-Gangetic Basin: Role of pollution transport pathways - Amarendra Singh; Atul Kumar Srivastava; V. Varaprasad; Sunil Kumar; Virendra Pathak; Arvind Kumar Shukla (Meteorology and Atmospheric Physics, 2021)

Trace metal leaching from quarry by-product-stabilized marine sediments - Atul Singh; Margaret Houlihan; Asli Y. Dayioglu; Ahmet H. Aydilek (Marine Georesources & Geotechnology, 2021)

Performance analysis of multi-gap V-roughness with staggered elements of solar air heater based on artificial neural network and experimental investigations - Piyush Kumar Jain; Atul Lanjewar; Rahul Jain; Kunj Bihari Rana (Environmental Science and Pollution Research, 2021)

Deciphering the complexity of sperm transcriptome reveals genes governing functional membrane and acrosome integrities potentially influence fertility - Sellappan Selvaraju; Laxman Ramya; Sivashanmugam Parthipan; Divakar Swathi; Bala Krishnan Binsila; Atul P Kolte (Cell and Tissue Research, 2021)

Exploration of intrinsic peroxidase-like activity of Acidithiobacillus ferrooxidans spent medium and its application for glutathione detection - Umesh Jadhav; Tejas Gawade; Sunil Bhapkar; Atul Bharde (Archives of Microbiology, 2021)

Greening drylands despite warming consistent with carbon dioxide fertilization effect - Alemu Gonsamo; Philippe Ciais; Diego G. Miralles; Stephen Sitch; Wouter Dorigo; Danica Lombardozzi; Pierre Friedlingstein; Julia E. M. S. Nabel; Daniel S. Goll; Michael O'Sullivan; Almut Arneth; Peter Anthoni; et al. (Global Change Biology, 2021)
The rising atmospheric CO 2 concentration leads to a CO 2 fertilization effect on plants—that is, increased photosynthetic uptake of CO 2 by leaves and enhanced water‐use efficiency (WUE). Yet, the resulting net impact of CO 2 fertilization on plant growth and soil moisture (SM) savings at large scale is poorly understood. Drylands provide a natural experimental setting to detect the CO 2 fertilization effect on plant growth since foliage amount, plant water‐use and photosynthesis are all tightly coupled in water‐limited ecosystems. A long‐term change in the response of leaf area index (LAI, a measure of foliage amount) to changes in SM is likely to stem from changing water demand of primary productivity in water‐limited ecosystems and is a proxy for changes in WUE. Using 34‐year satellite observations of LAI and SM over tropical and subtropical drylands, we identify that a 1% increment in SM leads to 0.15% (±0.008, 95% confidence interval) and 0.51% (±0.01, 95% confidence interval) increments in LAI during 1982‒1998 and 1999‒2015, respectively. The increasing response of LAI to SM has contributed 7.2% (±3.0%, 95% confidence interval) to total dryland greening during 1999‒2015 compared to 1982‒1998. The increasing response of LAI to SM is consistent with the CO 2 fertilization effect on WUE in water‐limited ecosystems, indicating that a given amount of SM has sustained greater amounts of photosynthetic foliage over time. The LAI responses to changes in SM from seven dynamic global vegetation models are not always consistent with observations, highlighting the need for improved process knowledge of terrestrial ecosystem responses to rising atmospheric CO 2 concentration.

Characterization of phytochemicals and validation of antioxidant and anticancer activity in some Indian polyherbal ayurvedic products - Prem Prakash Kushwaha; Ramesh Kumar; Panchi Rani Neog; Malay Ranjan Behara; Pratibha Singh; Ajay Kumar; Kumari Sunita Prajapati; Atul Kumar Singh; Mohd Shuaib; Amit Kumar Sharma; Abhay Kumar Pandey; Shashank Kumar (Vegetos, 2021)

Micro-array Analysis of Cold Tolerant Tomato Expressing Nicotiana tabacum Osmotin - Vikas Yadav Patade; Atul Grover; Anukriti; Sanjay Mohan Gupta; M. Nasim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Design and development of a laboratory model for generation of dynamic stress in soil - Pooja S. Rao; Atul K. Desai; Chandresh H. Solanki (Innovative Infrastructure Solutions, 2021)

Phospholipid complex-loaded self-assembled phytosomal soft nanoparticles: evidence of enhanced solubility, dissolution rate, ex vivo permeability, oral bioavailability, and antioxidant potential of mangiferin - Darshan R. Telange; Nazish K. Sohail; Atul T. Hemke; Prashant S. Kharkar; Anil M. Pethe (Drug Delivery and Translational Research, 2021)

Informing the new developments and future of cancer immunotherapy - Atul Kumar; Courtney A. Swain; Lalita A. Shevde (Cancer and Metastasis Reviews, 2021)

Role of ZBTB7A zinc finger in tumorigenesis and metastasis - Atul Kumar Singh; Shiv Verma; Prem Prakash Kushwaha; Kumari Sunita Prajapati; Mohd Shuaib; Shashank Kumar; Sanjay Gupta (Molecular Biology Reports, 2021)

Advanced strategies for development of vaccines against human bacterial pathogens - Abhinay Sharma; Pooja Sanduja; Aparna Anand; Pooja Mahajan; Carlos A. Guzman; Puja Yadav; Amit Awasthi; Emanuel Hanski; Meenakshi Dua; Atul Kumar Johri (World Journal of Microbiology and Biotechnology, 2021)
Infectious diseases are one of the main grounds of death and disabilities in human beings globally. Lack of effective treatment and immunization for many deadly infectious diseases and emerging drug resistance in pathogens underlines the need to either develop new vaccines or sufficiently improve the effectiveness of currently available drugs and vaccines. In this review, we discuss the application of advanced tools like bioinformatics, genomics, proteomics and associated techniques for a rational vaccine design.

Interlink between pollution and COVID-19 in India: compelling view and key attributes - Srinivasa R. Vulichi; Atul Kabra; Mohammad Khalid; Rupak Kumar; Natália Cruz-Martins (Environmental Science and Pollution Research, 2021)

Conservation planning of cash crops species (Garcinia gummi-gutta) under current and future climate in the Western Ghats, India - Malay Pramanik; Atul Kumar Diwakar; Poli Dash; Sylvia Szabo; Indrajit Pal (Environment, Development and Sustainability, 2021)

Probiotics and Prebiotics Having Broad Spectrum Anticancer Therapeutic Potential: Recent Trends and Future Perspectives - Varruchi Sharma; Nitin Sharma; Imran Sheikh; Vikas Kumar; Nirmala Sehrawat; Mukesh Yadav; Gobind Ram; Atul Sankhyan; Anil K. Sharma (Current Pharmacology Reports, 2021)

Unfolding antifungals: as a new foe to pancreatic ductal adenocarcinoma—a mini-review - Shruti Gupta; Atul Kumar; Kiran Kumar Tejavath (Molecular Biology Reports, 2021)

Dynamic response of cut and cover tunnel section under blast loading - Palak J. Shukla; Atul K. Desai; Chetankumar D. Modhera (Innovative Infrastructure Solutions, 2021)

Giant axonal neuropathy with novel GAN pathogenic variant in a patient of consanguineous origin from Poonch Jammu and Kashmir-India - Yaser Rafiq Mir; Xue Zeng; Atul K. Taneja; Asima Hassan; Jayesh Sheth; Raja A. H. Kuchay (Molecular Biology Reports, 2021)

Effect of fabricated V-rib roughness experimentally investigated in a rectangular channel of solar air heater: a comprehensive review - Piyush Kumar Jain; Atul Lanjewar; Kunj Bihari Rana; Makkhan Lal Meena (Environmental Science and Pollution Research, 2021)

Is there an association between a history of military service and cancer diagnosis? Results from a US national-level study of self-reported outcomes - Hanan Goldberg; Rodrigo Noorani; John Z. Benton; Atul Lodh; Alejandro Berlin; Thenappan Chandrasekar; Christopher J. D. Wallis; Ardalan E. Ahmad; Zachary Klaassen; Neil E. Fleshner (Cancer Causes & Control, 2021)

Precipitation measurement from SARAL AltiKa and passive microwave radiometer observations - Atul K Varma; Neha Rajput Mangalsinh; Durgesh Nandan Piyush (International Journal of Remote Sensing, 2020)

Cross-genera amplification of Cajanus spp. specific SSR markers in Clitoria ternatea (L.) and their application in genetic diversity studies - Aparupa Naik; Sujit K. Mishra; Atul Nag; Gopal K. Soren; Aditya K. Panda; Sanjib K. Panda; Jogeswar Panigrahi (Physiology and Molecular Biology of Plants, 2020)

Retraction Note: Engineered Polyallylamine Nanoparticles for Efficient In Vitro Transfection - Atul Pathak; Anita Aggarwal; Raj K. Kurupati; Soma Patnaik; Archana Swami; Yogendra Singh; Pradeep Kumar; Suresh P. Vyas; Kailash C. Gupta (Pharmaceutical Research, 2020)

Application of neural network modelling for classifying hydrocarbon bearing zone, water bearing zone and shale with estimation of petrophysical parameters in Cauvery basin, India - Atul Kumar Pandey; Rima Chatterjee; Biswajit Choudhury (Journal of Earth System Science, 2020)

Sources evaluation, ecological and health risk assessment of potential toxic metals (PTMs) in surface soils of an industrial area, India - Krishnendu Kumar Pobi; Sumanta Nayek; Manash Gope; Atul Kumar Rai; Rajnarayan Saha (Environmental Geochemistry and Health, 2020)

Assessment of risk conferred by coding and regulatory variations of TMPRSS2 and CD26 in susceptibility to SARS-CoV-2 infection in human - Sabyasachi Senapati; Shashank Kumar; Atul K. Singh; Pratibha Banerjee; Sandilya Bhagavatula (Journal of Genetics, 2020)

Simulation of monsoon intra‐seasonal oscillations in Geophysical Fluid Dynamics Laboratory models from Atmospheric Model Intercomparison Project integrations of Coupled Model Intercomparison Project phase 5 - Sujata K. Mandke; Prasanth A. Pillai; Atul Kumar Sahai (International Journal of Climatology, 2020)
The simulation of the intra‐seasonal variability (ISV), especially the fidelity of monsoon intra‐seasonal oscillations (MISO) over the South Asian summer monsoon (SASM), has been evaluated in Atmospheric Model Intercomparison Project run of three Geophysical Fluid Dynamics Laboratory (GFDL) atmospheric general circulation models (AGCM), participating in Coupled Model Intercomparison Project phase 5. Two of the models, namely, “GFDL‐HIRAM‐C180” and “GFDL‐HIRAM‐C360” are global high‐resolution atmospheric models (HIRAMs), which are same but at different horizontal resolutions. Third model “GFDL‐CM3” is at moderate horizontal resolution, whose atmospheric component differs from HIRAMs. Results have led to the conclusion that simulation of ISV over SASM remains poor in GFDL AGCMs at higher horizontal resolution, except northwards propagation of 30–60‐day mode of MISO by HIRAMs. Our diagnostics revealed resemblance in key characteristics of ISV simulated in two HIRAMs, except spectral peak at lower frequencies (30–60 day), which is captured only by “GFDL‐HIRAM‐C180” over equatorial Indian Ocean. Based on these results, it is conjectured that although high horizontal resolution is crucial for AGCMs to reproduce observed northwards propagation of 30–60‐day mode of MISO, the simulation of nature of ISV over SASM is not influenced by the difference of horizontal resolution in two HIRAMs. Analysis implicates that a reasonable representation of meridional migration of horizontal moisture advection, the meridional gradient of low‐level specific humidity over Indian longitudes and precipitation–SST relationship over north Indian Ocean, the northwestern tropical Pacific Ocean and tropical Indian Ocean assures the northwards propagation of 30–60‐day mode of MISO in HIRAMs.

Batch leaching testing of stabilized dredged bottom-sea sediments - Atul Singh; Margaret Houlihan; Asli Y. Dayioglu; Ahmet H. Aydilek (Journal of Soils and Sediments, 2020)

Evaluation of rhizospheric Trichoderma species strains for producing cell wall-degrading and defense related enzymes in response to Fusarium oxysporum f. sp. lentis - Shaily Javeria; Atul Kumar; Amit Chandra Kharkwal; Ajit Varma; N. Srinivasa; Pratibha Sharma (Indian Phytopathology, 2020)

Exploring greenhouse gas mitigation strategies for agriculture in Africa: The case of Nigeria - Michael O. Dioha; Atul Kumar (Ambio, 2020)

Object-based change detection for VHR remote sensing images based on a Trisiamese-LSTM - Ran Jing; Shuang Liu; Zhaoning Gong; Zhiheng Wang; Hongliang Guan; Atul Gautam; Wenji Zhao (International Journal of Remote Sensing, 2020)

Supersaturated LFCS type III self-emulsifying delivery systems of sorafenib tosylate with improved biopharmaceutical performance: QbD-enabled development and evaluation - Teenu Sharma; Atul Jain; Ranjot Kaur; Sumant Saini; O P Katare; Bhupinder Singh (Drug Delivery and Translational Research, 2020)

Marine Microbial Response to Heavy Metals: Mechanism, Implications and Future Prospect - Abhay B. Fulke; Atul Kotian; Manisha D. Giripunje (Bulletin of Environmental Contamination and Toxicology, 2020)

Causes of slowing‐down seasonal CO 2 amplitude at Mauna Loa - Kai Wang; Yilong Wang; Xuhui Wang; Yue He; Xiangyi Li; Ralph F. Keeling; Philippe Ciais; Martin Heimann; Shushi Peng; Frédéric Chevallier; Pierre Friedlingstein; Stephen Sitch; et al. (Global Change Biology, 2020)
Changing amplitude of the seasonal cycle of atmospheric CO 2 (SCA) in the northern hemisphere is an emerging carbon cycle property. Mauna Loa (MLO) station (20°N, 156°W), which has the longest continuous northern hemisphere CO 2 record, shows an increasing SCA before the 1980s ( p 2 fertilization. This challenges the view that CO 2 fertilization is the dominant cause of emergent SCA trends at northern sites south of 40°N. The contribution of agricultural intensification on the deceleration of SCA at MLO was elusive according to land–atmosphere CO 2 flux estimated by DGVMs and atmospheric inversions. Our results also show the necessity to adequately account for changing circulation patterns in understanding carbon cycle dynamics observed from atmospheric observations and in using these observations to benchmark DGVMs.

Dynamics and drivers of land use and land cover changes in Bangladesh - Xiaoming Xu; Suravi Shrestha; Hammad Gilani; Murali K. Gumma; Baktiar N. Siddiqui; Atul K. Jain (Regional Environmental Change, 2020)
Bangladesh has undergone dramatic land use and land cover changes (LULCC) in recent years, but no quantitative analysis of LULCC drivers at the national scale exists so far. Here, we quantified the drivers of major LULCC in combination with biophysical and socioeconomic observations at the sub-district level. We used Landsat satellite data to interpret LULCC from 2000 to 2010 and employed a Global Surface Water Dataset to account for the influences of water seasonality. The results suggest that major LULCC in Bangladesh occur between agricultural land and waterbodies and between forest and shrubland. Exclusion of seasonal waterbodies can improve the accuracy of our LULCC results and driver analysis. Although the gross gain and loss of agricultural land are large on the local scale, the net change (gross gain minus gross loss) at a country scale is almost negligible. Climate dynamics and extreme events and changes in urban and rural households were driving the changes from forest to shrubland in the southeast region. The conversion from agricultural land to standing waterbodies in the southwest region was mainly driven by urban household dynamics, population growth, distance to cities and major roads, and precipitation dynamics. This study, which is the first effort accounting for water seasonality and quantifying biophysical and socioeconomic drivers of LULCC at the national scale, provides a perspective on overall LULCC and underlying drivers over a decadal time scale and national spatial scale and can serve as a scientific basis for developing land policies in Bangladesh.

Uncommon non-fermenting Gram-negative bacillary bacteraemia in ICU patients - Sai Saran; Mohan Gurjar; Atul Garg; Chinmoy Sahu; Bhanuprakash Bhaskar; Prabhaker Mishra; Afzal Azim; Banani Poddar; Arvind Kumar Baronia (Infectious Diseases, 2020)

Stimuli Responsive In Situ Gelling Systems Loaded with PLGA Nanoparticles of Moxifloxacin Hydrochloride for Effective Treatment of Periodontitis - Sarwar Beg; Shashi Dhiman; Teenu Sharma; Ashish Jain; Rakesh Kumar Sharma; Atul Jain; Bhupinder Singh (AAPS PharmSciTech, 2020)

Enhanced anti-ageing and wound healing properties of Ficus religiosa L. bark, leaf and aerial root extract in human keratinocytes cell line (HaCaT) - Prem Pandey; Hyo Hyun Seo; Hye-In Kim; Seung Hwan Ryu; Medini Dingre; Sang Hyun Moh; Atul Kulkarni; Varsha A. Parasharami (Vegetos, 2020)

In-Silico Prediction of Peptide Based Vaccine Against Zika Virus - Parul Sharma; Rajbir Kaur; Atul Kumar Upadhyay; Vikas Kaushik (International Journal of Peptide Research and Therapeutics, 2020)

The impact of northern Indian Ocean rivers on the Bay of Bengal using NEMO global ocean model - Atul Srivastava; Anitha Gera; Imran M. Momin; Ashis Kumar Mitra; Ankur Gupta (Acta Oceanologica Sinica, 2020)

Global vegetation biomass production efficiency constrained by models and observations - Yue He; Shushi Peng; Yongwen Liu; Xiangyi Li; Kai Wang; Philippe Ciais; M. Altaf Arain; Yuanyuan Fang; Joshua B. Fisher; Daniel Goll; Daniel Hayes; Deborah N. Huntzinger; et al. (Global Change Biology, 2020)
Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

State of the science in reconciling top‐down and bottom‐up approaches for terrestrial CO 2 budget - Masayuki Kondo; Prabir K. Patra; Stephen Sitch; Pierre Friedlingstein; Benjamin Poulter; Frederic Chevallier; Philippe Ciais; Josep G. Canadell; Ana Bastos; Ronny Lauerwald; Leonardo Calle; Kazuhito Ichii; et al. (Global Change Biology, 2020)
Robust estimates of CO 2 budget, CO 2 exchanged between the atmosphere and terrestrial biosphere, are necessary to better understand the role of the terrestrial biosphere in mitigating anthropogenic CO 2 emissions. Over the past decade, this field of research has advanced through understanding of the differences and similarities of two fundamentally different approaches: “top‐down” atmospheric inversions and “bottom‐up” biosphere models. Since the first studies were undertaken, these approaches have shown an increasing level of agreement, but disagreements in some regions still persist, in part because they do not estimate the same quantity of atmosphere–biosphere CO 2 exchange. Here, we conducted a thorough comparison of CO 2 budgets at multiple scales and from multiple methods to assess the current state of the science in estimating CO 2 budgets. Our set of atmospheric inversions and biosphere models, which were adjusted for a consistent flux definition, showed a high level of agreement for global and hemispheric CO 2 budgets in the 2000s. Regionally, improved agreement in CO 2 budgets was notable for North America and Southeast Asia. However, large gaps between the two methods remained in East Asia and South America. In other regions, Europe, boreal Asia, Africa, South Asia, and Oceania, it was difficult to determine whether those regions act as a net sink or source because of the large spread in estimates from atmospheric inversions. These results highlight two research directions to improve the robustness of CO 2 budgets: (a) to increase representation of processes in biosphere models that could contribute to fill the budget gaps, such as forest regrowth and forest degradation; and (b) to reduce sink–source compensation between regions (dipoles) in atmospheric inversion so that their estimates become more comparable. Advancements on both research areas will increase the level of agreement between the top‐down and bottom‐up approaches and yield more robust knowledge of regional CO 2 budgets.

Estimation of behavioral change of SSC of bed profile in the river using ADCP - Atul Kumar Rahul; Nikita Shivhare; Shyam Bihari Dwivedi; Prabhat Kumar Singh Dikshit (Arabian Journal of Geosciences, 2020)

Human orbital adipose tissue-derived mesenchymal stem cells possess neuroectodermal differentiation and repair ability - Darilang Mawrie; Kasturi Bhattacharjee; Amit Sharma; Renu Sharma; Jina Bhattacharyya; Harsha Bhattacharjee; Nilutparna Deori; Atul Kumar; Bithiah Grace Jaganathan (Cell and Tissue Research, 2019)

Animal-Use Antibiotics Induce Cross-Resistance in Bacterial Pathogens to Human Therapeutic Antibiotics - Atul K. Singh; Arun K. Bhunia (Current Microbiology, 2019)

Suppression of aerosol-induced atmospheric warming by clouds in the Indo-Gangetic Basin, northern India - Parul Srivastava; Sagnik Dey; Atul Kumar Srivastava; Sachchidanand Singh; Suresh Tiwari (Theoretical and Applied Climatology, 2019)

Genomic analysis of Indian strains of Salmonella enterica subsp. enterica serovar Typhi indicates novel genetic repertoire for pathogenicity and adaptations - Prabhjot Kaur Sekhon; Atul Munish Chander; Shanmugam Mayilraj; Praveen Rishi (Molecular Biology Reports, 2019)

Identification and analysis of recent temporal temperature trends for Dehradun, Uttarakhand, India - Atul Kant Piyoosh; Sanjay Kumar Ghosh (Meteorology and Atmospheric Physics, 2019)

Altered physiological responses of LlaNAC gene of Lepidium latifolium over-expressing tobacco plants - Sadhana Singh; Haya Khalid; Atul Grover; Abhinav Singh; M. Nasim (Acta Physiologiae Plantarum, 2019)

Improved Algorithms for the Measurement of Total Precipitable Water and Cloud Liquid Water from SARAL Microwave Radiometer Observations - Rajput Neha Mangalsinh; Atul Kumar Varma (Marine Geodesy, 2019)

Petrographic controls on phosphorous distribution in coal seams of the Jharia basin, India - Atul Kumar Varma; Sumit Mishra; Balram Tiwari; Bodhisatwa Hazra; Susheel Kumar; Durga Charan Panigrahi; Anwita Ojha (Journal of Earth System Science, 2019)

Quantifying the biophysical and socioeconomic drivers of changes in forest and agricultural land in South and Southeast Asia - Xiaoming Xu; Atul K. Jain; Katherine V. Calvin (Global Change Biology, 2019)
South and Southeast Asia (SSEA) has been a hotspot for land use and land cover change (LULCC) in the past few decades. The identification and quantification of the drivers of LULCC are crucial for improving our understanding of LULCC trends. So far, the biophysical and socioeconomic drivers of forest change have not been quantified at the regional scale, particularly for SSEA. In this study, we quantify the biophysical and socioeconomic drivers of forest change on a country‐by‐country basis in SSEA using an integrated quantitative methodology, which systematically accounts for previously published driver information and regional datasets. We synthesize more than 200 publications to identify the drivers of the forest change at different spatial scales in SSEA. Subsequently, we collect spatially explicit proxy data to represent the identified drivers. We quantify the dynamics of forest and agricultural land from 1992 to 2015 using the Climate Change Initiative (CCI) land cover data developed by the European Space Agency (ESA). A geographically weighted regression method is employed to quantify the spatially heterogeneous drivers of forest change. Our results show that socioeconomic drivers are more important than biophysical drivers for the conversion of forest to agricultural land in South Asia and maritime Southeast Asia. In contrast, biophysical drivers are more important than socioeconomic drivers for the conversion of agricultural land to forest in maritime Southeast Asia and less important in South Asia. Both biophysical and socioeconomic drivers contribute approximately equally to both changes in the mainland Southeast Asia region. By quantifying the dynamics of forest and agricultural land and the spatially explicit drivers of their changes in SSEA, this study provides a solid foundation for LULCC modeling and projection.

Identification of Erysiphe quercicola associated with powdery mildew disease on Ailanthus excelsa in India - Ashish Kumar Nayak; Bandamaravuri Kishore Babu; Atul Kumar Srivastava (Australasian Plant Pathology, 2019)

Upper ocean high resolution regional modeling of the Arabian Sea and Bay of Bengal - Dwivedi Suneet; Mishra Alok Kumar; Srivastava Atul (Acta Oceanologica Sinica, 2019)

Longitudinal variability of the equatorial counter electrojet during the solar cycle 24 - Gabriel Soares; Yosuke Yamazaki; Jürgen Matzka; Katia Pinheiro; Claudia Stolle; Patrick Alken; Akimasa Yoshikawa; Teiji Uozumi; Akiko Fujimoto; Atul Kulkarni (Studia Geophysica et Geodaetica, 2019)

OsNAC-like transcription factor involved in regulating seed-storage protein content at different stages of grain filling in rice under aerobic conditions - Gaurav Sharma; Atul Kumar Upadyay; Hanamareddy Biradar; Sonia; Shailaja Hittalmani (Journal of Genetics, 2019)

Calcium Channels, Rho-Kinase, Protein Kinase-C, and Phospholipase-C Pathways Mediate Mercury Chloride-Induced Myometrial Contractions in Rats - Swati Koli; Atul Prakash; Soumen Choudhury; Rajesh Mandil; Satish K. Garg (Biological Trace Element Research, 2019)

Terpene profiling, transcriptome analysis and characterization of cis-β-terpineol synthase from Ocimum - Atul Anand; Ramesha H. Jayaramaiah; Supriya D. Beedkar; Bhushan B. Dholakia; Santosh G. Lavhale; Sachin A. Punekar; Wasudeo N. Gade; Hirekodathakallu V. Thulasiram; Ashok P. Giri (Physiology and Molecular Biology of Plants, 2019)

RNA sequencing-based transcriptomic profiles of embryonic lens development for cataract gene discovery - Deepti Anand; Atul Kakrana; Archana D. Siddam; Hongzhan Huang; Irfan Saadi; Salil A. Lachke (Human Genetics, 2018)

Pesticide residues in Indian raw honeys, an indicator of environmental pollution - Atul Kumar; Jatinder Paul Singh Gill; Jasbir Singh Bedi; Amit Kumar (Environmental Science and Pollution Research, 2018)

Chemical Characteristics of Atmospheric Aerosol at Alaknanda Valley (Srinagar) in the Central Himalaya Region, India - Alok Sagar Gautam; Rajendra Singh Negi; Santosh Singh; Atul Kumar Srivastava; Suresh Tiwari; Deewan Singh Bisht (International Journal of Environmental Research, 2018)

On Strong Positive Frequency Dependencies of Quality Factors in Local-Earthquake Seismic Studies - Igor B. Morozov; Atul Jhajhria; Wubing Deng (Pure and Applied Geophysics, 2018)

Incidence of symptomatic CSF viral escape in HIV infected patients receiving atazanavir/ritonavir (ATV/r)-containing ART: a tertiary care cohort in western India - Atul K. Patel; Ketan K. Patel; Swati Gohel; Ambuj Kumar; Scott Letendre (Journal of NeuroVirology, 2018)

Water use in rice crop through different methods of irrigation in a sodic soil - Atul Kumar Singh; Sanjay Arora; Yash Pal Singh; Chhedi Lal Verma; Ajay Kumar Bhardwaj; Navneet Sharma (Paddy and Water Environment, 2018)

Combined Hepatoprotective Activity of Murraya koenigii and Phyllanthus niruri Extracts Against Paracetamol Induced Hepatotoxicity in Alcoholic Rats - Pallavi Shah; S. P. Singh; Atul Kumar Gupta; Anil Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Novel cationic supersaturable nanomicellar systems of raloxifene hydrochloride with enhanced biopharmaceutical attributes - Atul Jain; Rajpreet Kaur; Sarwar Beg; Varun Kushwah; Sanyog Jain; Bhupinder Singh (Drug Delivery and Translational Research, 2018)

Upper Ocean Four-Dimensional Variational Data Assimilation in the Arabian Sea and Bay of Bengal - Suneet Dwivedi; Atul Srivastava; Alok Kumar Mishra (Marine Geodesy, 2018)

Nanosensors and nanobiosensors in food and agriculture - Anup K. Srivastava; Atul Dev; Surajit Karmakar (Environmental Chemistry Letters, 2018)

Nanomaterial toxicity for plants - Atul Dev; Anup Kumar Srivastava; Surajit Karmakar (Environmental Chemistry Letters, 2018)

Direct shoot regeneration and genetic fidelity analysis in finger millet using ISSR markers - G. Atul Babu; A. Vinoth; R. Ravindhran (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Development and Evaluation of pH-Responsive Cyclodextrin-Based in situ Gel of Paliperidone for Intranasal Delivery - Atul P. Sherje; Vaishali Londhe (AAPS PharmSciTech, 2018)

Silkworm disease incidence trends during the years 1992–2011 in the Murshidabad district of West Bengal, India - Zakir Hossain; Satadal Chakraborty; Sunil Kumar Gupta; Atul Kumar Saha; Bharat Bhushan Bindroo (International Journal of Tropical Insect Science, 2017)

Effect of autocorrelation on temporal trends in rainfall in a valley region at the foothills of Indian Himalayas - Atul Kant Piyoosh; Sanjay Kumar Ghosh (Stochastic Environmental Research and Risk Assessment, 2017)

Organo-petrographic and pore facets of Permian shale beds of Jharia Basin with implications to shale gas reservoir - Vinod Atmaram Mendhe; Subhashree Mishra; Ranjit G. Khangar; Alka Damodhar Kamble; Durgesh Kumar; Atul Kumar Varma; H. Singh; Sujeet Kumar; Mollika Bannerjee (Journal of Earth Science, 2017)

In vivo and in vitro control activity of plant essential oils against three strains of Aspergillus niger - Peeyush Kumar; Sapna Mishra; Atul Kumar; Sanjeev Kumar; Chandra Shekhar Prasad (Environmental Science and Pollution Research, 2017)

Challenging terrestrial biosphere models with data from the long‐term multifactor Prairie Heating and CO 2 Enrichment experiment - Martin G. De Kauwe; Belinda E. Medlyn; Anthony P. Walker; Sönke Zaehle; Shinichi Asao; Bertrand Guenet; Anna B. Harper; Thomas Hickler; Atul K. Jain; Yiqi Luo; Xingjie Lu; Kristina Luus; et al. (Global Change Biology, 2017)
Multifactor experiments are often advocated as important for advancing terrestrial biosphere models ( TBM s), yet to date, such models have only been tested against single‐factor experiments. We applied 10 TBM s to the multifactor Prairie Heating and CO 2 Enrichment ( PHACE ) experiment in Wyoming, USA . Our goals were to investigate how multifactor experiments can be used to constrain models and to identify a road map for model improvement. We found models performed poorly in ambient conditions; there was a wide spread in simulated above‐ground net primary productivity (range: 31–390 g C m −2 yr −1 ). Comparison with data highlighted model failures particularly with respect to carbon allocation, phenology, and the impact of water stress on phenology. Performance against the observations from single‐factors treatments was also relatively poor. In addition, similar responses were predicted for different reasons across models: there were large differences among models in sensitivity to water stress and, among the N cycle models, N availability during the experiment. Models were also unable to capture observed treatment effects on phenology: they overestimated the effect of warming on leaf onset and did not allow CO 2 ‐induced water savings to extend the growing season length. Observed interactive ( CO 2 × warming) treatment effects were subtle and contingent on water stress, phenology, and species composition. As the models did not correctly represent these processes under ambient and single‐factor conditions, little extra information was gained by comparing model predictions against interactive responses. We outline a series of key areas in which this and future experiments could be used to improve model predictions of grassland responses to global change.

Global DNA methylation profiling of manganese-exposed human neuroblastoma SH-SY5Y cells reveals epigenetic alterations in Parkinson’s disease-associated genes - Prashant Tarale; Saravanadevi Sivanesan; Atul P. Daiwile; Reinhard Stöger; Amit Bafana; Pravin K. Naoghare; Devendra Parmar; Tapan Chakrabarti; Krishnamurthi Kannan (Archives of Toxicology, 2017)

Lidocaine-loaded fish scale-nanocellulose biopolymer composite microneedles - Pangkhi Medhi; Ololade Olatunji; Atul Nayak; Chandra Teja Uppuluri; Richard T. Olsson; Buchi N. Nalluri; Diganta B. Das (AAPS PharmSciTech, 2017)

Effect of Microneedle Type on Transdermal Permeation of Rizatriptan - Chandrateja Uppuluri; Ashraf Sultana Shaik; Tao Han; Atul Nayak; Karthik J. Nair; Benjamin R. Whiteside; Buchi N. Nalluri; Diganta B. Das (AAPS PharmSciTech, 2017)

Analysis of synonymous codon usage bias and phylogeny of coat protein gene in banana bract mosaic virus isolates - Atul B. Patil; Vijayendra S. Dalvi; Akhilesh A. Mishra; Bal Krishna; Abdul Azeez (VirusDisease, 2017)

Inclusion Complexes of Nateglinide with HP–β–CD and L-Arginine for Solubility and Dissolution Enhancement: Preparation, Characterization, and Molecular Docking Study - Vasanti Suvarna; Apeksha Kajwe; Manikanta Murahari; Gurubasavaraj V. Pujar; Bharath Kumar Inturi; Atul P. Sherje (Journal of Pharmaceutical Innovation, 2017)

Effect of microneedles on transdermal permeation enhancement of amlodipine - Buchi N. Nalluri; Chandrateja Uppuluri; Jyothirmayee Devineni; Atul Nayak; Karthik J. Nair; Benjamin R. Whiteside; Diganta B. Das (Drug Delivery and Translational Research, 2017)

Performance of small group of geosynthetic-reinforced granular piles - Yogendra Tandel; Mohsin Jamal; Chandresh Solanki; Atul Desai; Jignesh Patel (Marine Georesources & Geotechnology, 2017)

Dynamics and determinants of land change in India: integrating satellite data with village socioeconomics - Prasanth Meiyappan; Parth S. Roy; Yeshu Sharma; Reshma M. Ramachandran; Pawan K. Joshi; Ruth S. DeFries; Atul K. Jain (Regional Environmental Change, 2017)

Host-delivered RNAi-mediated root-knot nematode resistance in Arabidopsis by targeting splicing factor and integrase genes - Anil Kumar; Atul Kakrana; Anil Sirohi; K. Subramaniam; R. Srinivasan; M. Z. Abdin; Pradeep K. Jain (Journal of General Plant Pathology, 2017)

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

Characterization and radiative impact of dust aerosols over northwestern part of India: a case study during a severe dust storm - Atinderpal Singh; Shani Tiwari; Deepti Sharma; Darshan Singh; Suresh Tiwari; Atul Kumar Srivastava; Neeraj Rastogi; A. K. Singh (Meteorology and Atmospheric Physics, 2016)

A comparative assessment of temperature data from different sources for Dehradun, Uttarakhand, India - Atul Kant Piyoosh; Sanjay Kumar Ghosh (Journal of Meteorological Research, 2016)

A Novel Folate-Targeted Nanoliposomal System of Doxorubicin for Cancer Targeting - Atul A. Lohade; Rajesh R. Jain; Krishna Iyer; Sushant K. Roy; Hemant H. Shimpi; Yogita Pawar; M. G. R. Rajan; Mala D. Menon (AAPS PharmSciTech, 2016)

Hotspots of uncertainty in land‐use and land‐cover change projections: a global‐scale model comparison - Reinhard Prestele; Peter Alexander; Mark D. A. Rounsevell; Almut Arneth; Katherine Calvin; Jonathan Doelman; David A. Eitelberg; Kerstin Engström; Shinichiro Fujimori; Tomoko Hasegawa; Petr Havlik; Florian Humpenöder; et al. (Global Change Biology, 2016)
Model‐based global projections of future land‐use and land‐cover ( LULC ) change are frequently used in environmental assessments to study the impact of LULC change on environmental services and to provide decision support for policy. These projections are characterized by a high uncertainty in terms of quantity and allocation of projected changes, which can severely impact the results of environmental assessments. In this study, we identify hotspots of uncertainty, based on 43 simulations from 11 global‐scale LULC change models representing a wide range of assumptions of future biophysical and socioeconomic conditions. We attribute components of uncertainty to input data, model structure, scenario storyline and a residual term, based on a regression analysis and analysis of variance. From this diverse set of models and scenarios, we find that the uncertainty varies, depending on the region and the LULC type under consideration. Hotspots of uncertainty appear mainly at the edges of globally important biomes (e.g., boreal and tropical forests). Our results indicate that an important source of uncertainty in forest and pasture areas originates from different input data applied in the models. Cropland, in contrast, is more consistent among the starting conditions, while variation in the projections gradually increases over time due to diverse scenario assumptions and different modeling approaches. Comparisons at the grid cell level indicate that disagreement is mainly related to LULC type definitions and the individual model allocation schemes. We conclude that improving the quality and consistency of observational data utilized in the modeling process and improving the allocation mechanisms of LULC change models remain important challenges. Current LULC representation in environmental assessments might miss the uncertainty arising from the diversity of LULC change modeling approaches, and many studies ignore the uncertainty in LULC projections in assessments of LULC change impacts on climate, water resources or biodiversity.

Application of Mechanistic Models for Process Design and Development of Biologic Drug Products - Wei Chen; Xiaodong Chen; Rajesh Gandhi; Rao V. Mantri; Vikram Sadineni; Atul Saluja (Journal of Pharmaceutical Innovation, 2016)

Intercomparison of High-Resolution Bay of Bengal Circulation Models Forced with Different Winds - Atul Srivastava; Suneet Dwivedi; Alok Kumar Mishra (Marine Geodesy, 2016)

Identification of GRP78 as a molecular target of medicarpin in osteoblast cells by proteomics - Jyoti Kureel; Aijaz A. John; Ashutosh Raghuvanshi; Pallavi Awasthi; Atul Goel; Divya Singh (Molecular and Cellular Biochemistry, 2016)

Morphological, Pathogenic and Molecular Characterizations of Alternaria Species Causing Early Blight of Tomato in Northern India - Murugan Loganathan; V. Venkataravanappa; Sujoy Saha; Awadhesh Bahadur Rai; Swapnila Tripathi; Rakesh Kumar Rai; Atul Kumar Pandey; P. Chowdappa (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Algorithmic Approach for Removing the Redundancy in Diabetic Gene Categories Based on Semantic Similarity and Gene Expression Data - Atul Kumar; D. Jeya Sundara Sharmila (Interdisciplinary Sciences: Computational Life Sciences, 2016)

A Quantitative Measure of Conformational Changes in Apo, Holo and Ligand-Bound Forms of Enzymes - Satendra Singh; Atul Kumar Singh; Gulshan Wadhwa; Dev Bukhsh Singh; Seema Dwivedi; Budhayash Gautam; Pramod W. Ramteke (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Development and statistical optimization of chitosan and eudragit based gastroretentive controlled release multiparticulate system for bioavailability enhancement of metformin HCl - Atul Kumar Sahu; Amita Verma (Journal of Pharmaceutical Investigation, 2016)

A model-based approach for integration analysis of well log and seismic data for reservoir characterization - Atul Kumar; Mohd Haris Mohd Khir; Wan Ismail Wan Yusoff (Geosciences Journal, 2016)

Dose-dependent response of Trichoderma harzianum in improving drought tolerance in rice genotypes - Veena Pandey; Mohammad W. Ansari; Suresh Tula; Sandep Yadav; Ranjan K. Sahoo; Nandini Shukla; Gurdeep Bains; Shail Badal; Subhash Chandra; A. K. Gaur; Atul Kumar; Alok Shukla; et al. (Planta, 2016)

Stabilization of Live Attenuated Influenza Vaccines by Freeze Drying, Spray Drying, and Foam Drying - Phillip M. Lovalenti; Jeff Anderl; Luisa Yee; Van Nguyen; Behnaz Ghavami; Satoshi Ohtake; Atul Saxena; Thomas Voss; Vu Truong-Le (Pharmaceutical Research, 2016)

Transcriptional response to heat shock in liver of snow trout (Schizothorax richardsonii)—a vulnerable Himalayan Cyprinid fish - Ashoktaru Barat; Prabhati Kumari Sahoo; Rohit Kumar; Chirag Goel; Atul Kumar Singh (Functional & Integrative Genomics, 2016)

Global change pressures on soils from land use and management - Pete Smith; Joanna I. House; Mercedes Bustamante; Jaroslava Sobocká; Richard Harper; Genxing Pan; Paul C. West; Joanna M. Clark; Tapan Adhya; Cornelia Rumpel; Keith Paustian; Peter Kuikman; et al. (Global Change Biology, 2016)
Soils are subject to varying degrees of direct or indirect human disturbance, constituting a major global change driver. Factoring out natural from direct and indirect human influence is not always straightforward, but some human activities have clear impacts. These include land‐use change, land management and land degradation (erosion, compaction, sealing and salinization). The intensity of land use also exerts a great impact on soils, and soils are also subject to indirect impacts arising from human activity, such as acid deposition (sulphur and nitrogen) and heavy metal pollution. In this critical review, we report the state‐of‐the‐art understanding of these global change pressures on soils, identify knowledge gaps and research challenges and highlight actions and policies to minimize adverse environmental impacts arising from these global change drivers. Soils are central to considerations of what constitutes sustainable intensification. Therefore, ensuring that vulnerable and high environmental value soils are considered when protecting important habitats and ecosystems, will help to reduce the pressure on land from global change drivers. To ensure that soils are protected as part of wider environmental efforts, a global soil resilience programme should be considered, to monitor, recover or sustain soil fertility and function, and to enhance the ecosystem services provided by soils. Soils cannot, and should not, be considered in isolation of the ecosystems that they underpin and vice versa. The role of soils in supporting ecosystems and natural capital needs greater recognition. The lasting legacy of the International Year of Soils in 2015 should be to put soils at the centre of policy supporting environmental protection and sustainable development.

Antiproliferative effect of isolated isoquinoline alkaloid from Mucuna pruriens seeds in hepatic carcinoma cells - Pranesh Kumar; Atul Rawat; Amit K. Keshari; Ashok K. Singh; Siddhartha Maity; Arnab De; Amalesh Samanta; Sudipta Saha (Natural Product Research, 2016)

Development of conventional and real time PCR assay for detection and quantification of Rhizoctonia solani infecting pulse crops - Sunil C. Dubey; Aradhika Tripathi; Balendu K. Upadhyay; Atul Kumar (Biologia, 2016)

Biofilms and human health - Shilpi Srivastava; Atul Bhargava (Biotechnology Letters, 2016)

Insight from uncertainty: bootstrap-derived diffusion metrics differentially predict memory function among older adults - Robert S. Vorburger; Christian G. Habeck; Atul Narkhede; Vanessa A. Guzman; Jennifer J. Manly; Adam M. Brickman (Brain Structure and Function, 2016)

Ternary Inclusion Complex of Paliperidone with β-Cyclodextrin and Hydrophilic Polymer for Solubility and Dissolution Enhancement - Atul P. Sherje; Vaishali Londhe (Journal of Pharmaceutical Innovation, 2015)

Pretreatment of garden biomass using Fenton’s reagent: influence of Fe2+ and H2O2 concentrations on lignocellulose degradation - Vivek P Bhange; SPM Prince William; Abhinav Sharma; Jagdish Gabhane; Atul N Vaidya; Satish R Wate (Journal of Environmental Health Science and Engineering, 2015)
Garden biomass (GB) is defined as low density and heterogeneous waste fraction of garden rubbish like grass clippings, pruning, flowers, branches, weeds; roots. GB is generally different from other types of biomass. GB is mostly generated through maintenance of green areas. GB can be processed for bio energy production as it contains considerably good amount of cellulose and hemicellulose. However, pretreatment is necessary to delignify and facilitate disruption of cellulosic moiety. The aim of the present investigation was to pretreat GB using Fenton’s reagent and to study the influence of Fe 2+ and H 2 O 2 concentrations on degradation of lignin and cellulose. The data were statistically analyzed using ANOVA and numerical point prediction tool of MINITAB RELEASE 14 to optimize different process variables such as temperature, concentration of Fe 2+ and H 2 O 2 . The results of the present investigation showed that Fenton’s reagent was effective on GB, however, concentration of Fe 2+ and H 2 O 2 play crucial role in determining the efficiency of pretreatment. An increase in H 2 O 2 concentration in Fenton’s reagent significantly increased the rate of cellulose and lignin degradation in contrast to increasing concentration of Fe 2+ ion which led to a decrease in lignocellulosic degradation.

A brief exposure to thyroxine synchronizes the circannual testicular cycle and associated molt in the subtropical spotted munia (Lonchura punctulata) - Asha Chandola-Saklani; Kiran Negi; Atul Kathait (Journal of Ornithology, 2015)

Molecular characterization of rainbow trout, Oncorhynchus mykiss (Walbaum, 1792) stocks in India - ASHOKTARU BARAT; PRABHATI K. SAHOO; ROHIT KUMAR; JAVAID I. MIR; SHAHNAWAZ ALI; RABINDAR S. PATIYAL; ATUL K. SINGH (Journal of Genetics, 2015)

Isolation of genes conferring salt tolerance from Piriformospora indica by random overexpression in Escherichia coli - Sunayna Gahlot; Amita Joshi; Pratap Singh; Renu Tuteja; Meenakshi Dua; Abhimanyu Jogawat; Manoj Kumar; Sumit Raj; Vikram Dayaman; Atul Kumar Johri; Narendra Tuteja (World Journal of Microbiology and Biotechnology, 2015)

Disentangling the ranges: climate policy scenarios for China and India - Andries F. Hof; Atul Kumar; Sebastiaan Deetman; Sambita Ghosh; Detlef P. van Vuuren (Regional Environmental Change, 2015)

De Novo Assembly and Characterization of Developing Spikes Transcriptome of Finger Millet (Eleusine coracana): a Minor Crop Having Nutraceutical Properties - Anil Kumar; Vikram Singh Gaur; Anshita Goel; Atul Kumar Gupta (Plant Molecular Biology Reporter, 2015)

Spermatogenesis and related plasma androgen and progestin level in wild male golden mahseer, Tor putitora (Hamilton, 1822), during the spawning season - Neetu Shahi; Sumanta Kumar Mallik; Jyoti Pande; Partha Das; Atul Kumar Singh (Fish Physiology and Biochemistry, 2015)

Lidocaine permeation from a lidocaine NaCMC/gel microgel formulation in microneedle-pierced skin: vertical (depth averaged) and horizontal permeation profiles - Atul Nayak; Liam Short; Diganta B. Das (Drug Delivery and Translational Research, 2015)

MiR-206, a Cerebellum Enriched miRNA Is Downregulated in All Medulloblastoma Subgroups and Its Overexpression Is Necessary for Growth Inhibition of Medulloblastoma Cells - Pooja Panwalkar; Aliasgar Moiyadi; Atul Goel; Prakash Shetty; Naina Goel; Epari Sridhar; Neelam Shirsat (Journal of Molecular Neuroscience, 2015)

Compound mouse mutants of bZIP transcription factors Mafg and Mafk reveal a regulatory network of non-crystallin genes associated with cataract - Smriti A. Agrawal; Deepti Anand; Archana D. Siddam; Atul Kakrana; Soma Dash; David A. Scheiblin; Christine A. Dang; Anne M. Terrell; Stephanie M. Waters; Abhyudai Singh; Hozumi Motohashi; Masayuki Yamamoto; et al. (Human Genetics, 2015)

A randomized, double-blind, duloxetine-referenced study comparing efficacy and tolerability of 2 fixed doses of vortioxetine in the acute treatment of adults with MDD - Atul R. Mahableshwarkar; Paula L. Jacobsen; Yinzhong Chen; Michael Serenko; Madhukar H. Trivedi (Psychopharmacology, 2015)

In-vitro Anthelmintic Efficacy of Aqueous Extract of Scindapsus officinalis (Roxb.) Schott Fruits Against Haemonchus contortus of Small Ruminants - Gagandeep Singh; Rajeev Singh; Pawan Kumar Verma; Rajiv Singh; Atul Anand (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Estimates of Biomass Yield for Perennial Bioenergy Grasses in the USA - Yang Song; Atul K. Jain; William Landuyt; Haroon S. Kheshgi; Madhu Khanna (BioEnergy Research, 2015)

Introgression of multiple disease resistance into a maintainer of Basmati rice CMS line by marker assisted backcross breeding - Ashok K. Singh; Vikas K. Singh; Atul Singh; Ranjith K. Ellur; R. T. P. Pandian; S. Gopala Krishnan; U. D. Singh; M. Nagarajan; K. K. Vinod; K. V. Prabhu (Euphytica, 2015)

A quantitative measure of conformational changes in Apo, holo and ligand bound form of enzymes - Satendra Singh; Atul Kumar Singh; Gulshan Wadhwa; Dev Bukhsh Singh; Seema Dwivedi; Budhayash Gautam; Pramod W. Ramteke (Interdisciplinary Sciences: Computational Life Sciences, 2015)

MTBP inhibits migration and metastasis of hepatocellular carcinoma - Qian Bi; Atul Ranjan; Rui Fan; Neeraj Agarwal; Danny R. Welch; Steven A. Weinman; Jie Ding; Tomoo Iwakuma (Clinical & Experimental Metastasis, 2015)

Protein-Functionalized PLGA Nanoparticles of Lamotrigine for Neuropathic Pain Management - Jigar Lalani; Sushilkumar Patil; Atul Kolate; Riddhi Lalani; Ambikanandan Misra (AAPS PharmSciTech, 2015)

Algorithmic approach for removing the redundancy in diabetic gene categories based on semantic similarity and gene expression data - Atul Kumar; D. Jeya Sundara Sharmila (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Design and Optimization of Curcumin–HPβCD Bioadhesive Vaginal Tablets by 23 Factorial Design: In Vitro and In Vivo Evaluation - Umme Hani; H. G. Shivakumar; Atul Srivastava; Nawaz Mahammed; Shailesh Thirumaleshwar; Naga Sravan kumar Varma; Rudra Vaghela; Chetan G. Shinde; M. P. Gowrav (Journal of Pharmaceutical Innovation, 2015)

Identification of salt-tolerant barley varieties by a consolidated physiological and molecular approach - Atul Kamboj; Mark Ziemann; Mrinal Bhave (Acta Physiologiae Plantarum, 2015)

Pretreatment of garden biomass by alkali-assisted ultrasonication: effects on enzymatic hydrolysis and ultrastructural changes - Jagdish Gabhane; SPM Prince William; Atul Narayan Vaidya; Duraisamy Anand; Satish Wate (Journal of Environmental Health Science and Engineering, 2014)
The present investigation aims at studying the effectiveness of alkali-assisted ultrasonication on pretreatment of garden biomass (GB). Dry and powdered GB suspended in 1% NaOH was ultrasonicated for 15, 30 and 60 minutes at a frequency of 25 KHZ. The mode of action and effectiveness of alkali-assisted ultrasonication on GB was established through microscopic, scanning electron microscopic and X-ray diffraction studies. A perusal of results showed that alkali-assisted ultrasonication led to fibrillation of GB which ultimately facilitated enzymatic hydrolysis. The results also indicated that alkali-assisted ultrasonication is an efficient means of pretreatment of GB at moderate (45-50°C) working temperature and low (1%) concentration of alkali. The yield of reducing sugar after enzymatic hydrolysis increased almost six times as compared to control due to alkali-assisted ultrasonication.

Overexpression of NAC gene from Lepidium latifolium L. enhances biomass, shortens life cycle and induces cold stress tolerance in tobacco: potential for engineering fourth generation biofuel crops - Atul Grover; Sadhana Singh; Pankaj Pandey; Vikas Yadav Patade; Sanjay Mohan Gupta; M. Nasim (Molecular Biology Reports, 2014)

Chromenone and quinolinone derivatives as potent antioxidant agents - Praveen Vats; Vera Hadjimitova; Krassimira Yoncheva; Abha Kathuria; Antara Sharma; Karam Chand; Arul J. Duraisamy; Alpesh K. Sharma; Atul K. Sharma; Luciano Saso; Sunil K. Sharma (Medicinal Chemistry Research, 2014)

Synthesis, anti-inflammatory and antioxidant activity of ring-A-monosubstituted chalcone derivatives - Hiba Iqbal; Visakh Prabhakar; Atul Sangith; Baby Chandrika; Ranganathan Balasubramanian (Medicinal Chemistry Research, 2014)

Overexpression of Ran gene from Lepidium latifolium L. (LlaRan) renders transgenic tobacco plants hypersensitive to cold stress - Vimlendu Bhushan Sinha; Atul Grover; Sadhana Singh; Veena Pande; Zakwan Ahmed (Molecular Biology Reports, 2014)

Isolation and characterization of Ras-related GTP-binding protein (Ran) from Lepidium latifolium L. reveals its potential role in regulating abiotic stress tolerance - Vimlendu Bhushan Sinha; Atul Grover; Mohammad Aslam; Veena Pande; Zakwan Ahmed (Acta Physiologiae Plantarum, 2014)

Detection and molecular characterization of naturally transmitted sheep associated malignant catarrhal fever in cattle in India - Richa Sood; Rekha Khandia; Sandeep Bhatia; Divakar Hemadri; Manoj Kumar; Sharan S. Patil; Atul K. Pateriya; Arshi Siddiqui; Malkanna Sanjeev Kumar; Mudalagiri Dasappa Venkatesha; Diwakar D. Kulkarni (Tropical Animal Health and Production, 2014)

Enhancing milk and fertility performances using selection index developed for Indian Murrah buffaloes - Jamuna Valsalan; Atish Kumar Chakravarty; Chandrashekhar Santosh Patil; Shakti Kant Dash; Atul Chandrashekhar Mahajan; Vijay Kumar; Vikas Vohra (Tropical Animal Health and Production, 2014)

RNAi Mediated curcin precursor gene silencing in Jatropha (Jatropha curcas L.) - Vikas Yadav Patade; Deepti Khatri; Kamal Kumar; Atul Grover; Maya Kumari; Sanjay Mohan Gupta; Devender Kumar; Mohammed Nasim (Molecular Biology Reports, 2014)

Significance of Unfolding Thermodynamics for Predicting Aggregation Kinetics: A Case Study on High Concentration Solutions of a Multi-Domain Protein - Atul Saluja; Vikram Sadineni; Amol Mungikar; Vishal Nashine; Andrew Kroetsch; Charles Dahlheim; Venkatramana M. Rao (Pharmaceutical Research, 2014)

3D structure generation, virtual screening and docking of human Ras-associated binding (Rab3A) protein involved in tumourigenesis - Sharad S. Lodhi; Rohit Farmer; Atul Kumar Singh; Yogesh K. Jaiswal; Gulshan Wadhwa (Molecular Biology Reports, 2014)

Hazard assessment of metals in invasive fish species of the Yamuna River, India in relation to bioaccumulation factor and exposure concentration for human health implications - Atul K. Singh; Sharad C. Srivastava; Pankaj Verma; Abubakar Ansari; Ambrish Verma (Environmental Monitoring and Assessment, 2014)

Risk assessment of antibiotic residues in different water matrices in India: key issues and challenges - Pravin K. Mutiyar; Atul K. Mittal (Environmental Science and Pollution Research, 2014)

Microneedle-Assisted Permeation of Lidocaine Carboxymethylcellulose with Gelatine Co-polymer Hydrogel - Atul Nayak; Diganta B. Das; Goran T. Vladisavljević (Pharmaceutical Research, 2014)

ImmPort: disseminating data to the public for the future of immunology - Sanchita Bhattacharya; Sandra Andorf; Linda Gomes; Patrick Dunn; Henry Schaefer; Joan Pontius; Patty Berger; Vince Desborough; Tom Smith; John Campbell; Elizabeth Thomson; Ruth Monteiro; et al. (Immunologic Research, 2014)

Climate‐driven uncertainties in modeling terrestrial gross primary production: a site level to global‐scale analysis - Rahul Barman; Atul K. Jain; Miaoling Liang (Global Change Biology, 2014)
We used a land surface model to quantify the causes and extents of biases in terrestrial gross primary production ( GPP ) due to the use of meteorological reanalysis datasets. We first calibrated the model using meteorology and eddy covariance data from 25 flux tower sites ranging from the tropics to the northern high latitudes and subsequently repeated the site simulations using two reanalysis datasets: NCEP / NCAR and CRUNCEP . The results show that at most sites, the reanalysis‐driven GPP bias was significantly positive with respect to the observed meteorology‐driven simulations. Notably, the absolute GPP bias was highest at the tropical evergreen tree sites, averaging up to ca. 0.45 kg C m −2 yr −1 across sites (ca. 15% of site level GPP ). At the northern mid‐/high‐latitude broadleaf deciduous and the needleleaf evergreen tree sites, the corresponding annual GPP biases were up to 20%. For the nontree sites, average annual biases of up to ca. 20–30% were simulated within savanna, grassland, and shrubland vegetation types. At the tree sites, the biases in short‐wave radiation and humidity strongly influenced the GPP biases, while the nontree sites were more affected by biases in factors controlling water stress (precipitation, humidity, and air temperature). In this study, we also discuss the influence of seasonal patterns of meteorological biases on GPP . Finally, using model simulations for the global land surface, we discuss the potential impacts of site‐level reanalysis‐driven biases on the global estimates of GPP . In a broader context, our results can have important consequences on other terrestrial ecosystem fluxes (e.g., net primary production, net ecosystem production, energy/water fluxes) and reservoirs (e.g., soil carbon stocks). In a complementary study (Barman et al ., ), we extend the present analysis for latent and sensible heat fluxes, thus consistently integrating the analysis of climate‐driven uncertainties in carbon, energy, and water fluxes using a single modeling framework.

Antidyslipidemic effect and antioxidant activity of anthraquinone derivatives from Rheum emodi rhizomes in dyslipidemic rats - Sunil K. Mishra; Shashi Tiwari; Atul Shrivastava; Shishir Srivastava; Goutam K. Boudh; Shivendra K. Chourasia; Upma Chaturvedi; Snober S. Mir; Anil K. Saxena; Gitika Bhatia; Vijai Lakshmi (Journal of Natural Medicines, 2014)

Docking simulation, synthesis and biological evaluation of novel pyridazinone containing thymol as potential antimicrobial agents - Pramod Nagle; Yogesh Pawar; Atul Sonawane; Shyam Bhosale; Dhananjay More (Medicinal Chemistry Research, 2014)

Analysis of Jatropha curcas transcriptome for oil enhancement and genic markers - Atul Grover; Maya Kumari; Sadhana Singh; Shivender Singh Rathode; Sanjay Mohan Gupta; Pankaj Pandey; Sween Gilotra; Devender Kumar; Mohommad Arif; Zakwan Ahmed (Physiology and Molecular Biology of Plants, 2014)

Occurrences and fate of selected human antibiotics in influents and effluents of sewage treatment plant and effluent-receiving river Yamuna in Delhi (India) - Pravin K. Mutiyar; Atul K. Mittal (Environmental Monitoring and Assessment, 2014)

Surface Plasmon Resonance Sensogram Based Characterization of Antibodies Raised Against Intact Teliospores and Purified Diagnostic Antigen for Development of Nano-Immunosensor for Fungal Spore Antigen of Karnal Bunt (Tilletia indica) of Wheat - Sadhna Singh; Sanjay Gupta; Atul Kumar Gupta; Manoj Singh; Anil Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Thermal, kinetic, spectroscopic studies and anti-microbial, anti-tuberculosis, anti-oxidant properties of clioquinol and benzo-coumarin derivatives mixed complexes with copper ion - Hitesh R. Dholariya; Ketan S. Patel; Jiten C. Patel; Atul K. Patel; Kanuprasad D. Patel (Medicinal Chemistry Research, 2013)

Development of EST-SSR markers through data mining and their use for genetic diversity study in Indian accessions of Jatropha curcas L.: a potential energy crop - Maya Kumari; Atul Grover; Patade Vikas Yadav; Mohammad Arif; Zakwan Ahmed (Genes & Genomics, 2013)

Determination of dopamine D2 receptor occupancy by lurasidone using positron emission tomography in healthy male subjects - Dean F. Wong; Hiroto Kuwabara; James Robert Brašić; Thomas Stock; Atul Maini; Emily G. Gean; Antony Loebel (Psychopharmacology, 2013)

A Small-Scale, Material-Saving Approach to Rank-Order Lyophilized Formulations Based on Reconstitution Time - Sachin Chandran; Vishal Nashine; Mary Morcos; Atul Saluja (Journal of Pharmaceutical Innovation, 2013)

Potential of biodegradable microneedles as a transdermal delivery vehicle for lidocaine - Atul Nayak; Diganta Bhusan Das (Biotechnology Letters, 2013)

CO 2 emissions from land‐use change affected more by nitrogen cycle, than by the choice of land‐cover data - Atul K. Jain; Prasanth Meiyappan; Yang Song; Joanna I. House (Global Change Biology, 2013)
The high uncertainty in land‐based CO 2 fluxes estimates is thought to be mainly due to uncertainty in not only quantifying historical changes among forests, croplands, and grassland, but also due to different processes included in calculation methods. Inclusion of a nitrogen (N) cycle in models is fairly recent and strongly affects carbon (C) fluxes. In this study, for the first time, we use a model with C and N dynamics with three distinct historical reconstructions of land‐use and land‐use change ( LULUC ) to quantify LULUC emissions and uncertainty that includes the integrated effects of not only climate and CO 2 but also N. The modeled global average emissions including N dynamics for the 1980s, 1990s, and 2000–2005 were 1.8 ± 0.2, 1.7 ± 0.2, and 1.4 ± 0.2 GtC yr −1 , respectively, (mean and range across LULUC data sets). The emissions from tropics were 0.8 ± 0.2, 0.8 ± 0.2, and 0.7 ± 0.3 GtC yr −1 , and the non tropics were 1.1 ± 0.5, 0.9 ± 0.2, and 0.7 ± 0.1 GtC yr −1 . Compared to previous studies that did not include N dynamics, modeled net LULUC emissions were higher, particularly in the non tropics. In the model, N limitation reduces regrowth rates of vegetation in temperate areas resulting in higher net emissions. Our results indicate that exclusion of N dynamics leads to an underestimation of LULUC emissions by around 70% in the non tropics, 10% in the tropics, and 40% globally in the 1990s. The differences due to inclusion/exclusion of the N cycle of 0.1 GtC yr −1 in the tropics, 0.6 GtC yr −1 in the non tropics, and 0.7 GtC yr −1 globally (mean across land‐cover data sets) in the 1990s were greater than differences due to the land‐cover data in the non tropics and globally (0.2 GtC yr −1 ). While land‐cover information is improving with satellite and inventory data, this study indicates the importance of accounting for different processes, in particular the N cycle.

Genetic variability, heritability and genetic advance of growth and yield components of Jatropha (Jatropha curcas Linn.) genotypes - Atul Tripathi; D. K. Mishra; Jitendra Kumar Shukla (Trees, 2013)

Cloning, in silico characterization and induction of TiKpp2 MAP kinase in Tilletia indica under the influence of host factor(s) from wheat spikes - Atul K. Gupta; G. K. Joshi; J. M. Seneviratne; Dinesh Pandey; Anil Kumar (Molecular Biology Reports, 2013)

Erratum to: Syntheses and in vitro biological screening of 1-aryl-10H-[1,2,4]triazolo[3′,4′:3,4][1,2,4]triazino[5,6-b]indoles - Kuldip Upadhyay; Atul Manvar; Vijay Virsodiya; Jalpa Trivedi; Ravi Chaniyara; Anamik Shah; Gabriele Giliberti; Barbara Secci; Bernardetta Busonera; Giuseppina Sanna; Roberta Loddo; Paolo La Colla (Medicinal Chemistry Research, 2013)

Synthesis and biological evaluation of novel condensed pyrimidinylmethylsulfinylbenzimidazoles as antiulcer agent - Prashik B. Dudhe; Kishor S. Jain; Vikas K. Raskar; Atul S. Deodhe; Jasminkumar G. Patel; Manisha S. Phoujdar; Muthu K. Kathiravan (Medicinal Chemistry Research, 2013)

Syntheses and in vitro biological screening of 1-aryl-10H-[1,2,4]triazolo[3′,4′:3,4][1,2,4]triazino[5,6-b]indoles - Kuldip Upadhyay; Atul Manvar; Roberta Loddo; Paolo La Colla; Vijay Virsodiya; Jalpa Trivedi; Ravi Chaniyara; Anamik Shah (Medicinal Chemistry Research, 2013)

Cloning and characterization of GPAT gene from Lepidium latifolium L.: a step towards translational research in agri-genomics for food and fuel - Sanjay Mohan Gupta; Pankaj Pandey; Atul Grover; Vikas Yadav Patade; Sadhana Singh; Zakwan Ahmed (Molecular Biology Reports, 2013)

In vitro cytotoxicity evaluation of diversely substituted N-aryl-2-oxindoles - Atul Manvar; Abhay Bavishi; Rajesh Loriya; Manu Jaggi; Anamik Shah (Medicinal Chemistry Research, 2013)

Quantitative Appraisal of the Probiotic Attributes and In Vitro Adhesion Potential of Anti-listerial Bacteriocin-producing Lactic Acid Bacteria - Sandipan Mukherjee; Atul Kumar Singh; Manab Deb Adhikari; Aiyagari Ramesh (Probiotics and Antimicrobial Proteins, 2013)

Analysis of the barley leaf transcriptome under salinity stress using mRNA-Seq - Mark Ziemann; Atul Kamboj; Runyararo M. Hove; Shanon Loveridge; Assam El-Osta; Mrinal Bhave (Acta Physiologiae Plantarum, 2013)

Forest water use and water use efficiency at elevated CO 2 : a model‐data intercomparison at two contrasting temperate forest FACE sites - Martin G. De Kauwe; Belinda E. Medlyn; Sönke Zaehle; Anthony P. Walker; Michael C. Dietze; Thomas Hickler; Atul K. Jain; Yiqi Luo; William J. Parton; I. Colin Prentice; Benjamin Smith; Peter E. Thornton; et al. (Global Change Biology, 2013)
Predicted responses of transpiration to elevated atmospheric CO 2 concentration ( eCO 2 ) are highly variable amongst process‐based models. To better understand and constrain this variability amongst models, we conducted an intercomparison of 11 ecosystem models applied to data from two forest free‐air CO 2 enrichment ( FACE ) experiments at Duke University and Oak Ridge National Laboratory. We analysed model structures to identify the key underlying assumptions causing differences in model predictions of transpiration and canopy water use efficiency. We then compared the models against data to identify model assumptions that are incorrect or are large sources of uncertainty. We found that model‐to‐model and model‐to‐observations differences resulted from four key sets of assumptions, namely (i) the nature of the stomatal response to elevated CO 2 (coupling between photosynthesis and stomata was supported by the data); (ii) the roles of the leaf and atmospheric boundary layer (models which assumed multiple conductance terms in series predicted more decoupled fluxes than observed at the broadleaf site); (iii) the treatment of canopy interception (large intermodel variability, 2–15%); and (iv) the impact of soil moisture stress (process uncertainty in how models limit carbon and water fluxes during moisture stress). Overall, model predictions of the CO 2 effect on WUE were reasonable (intermodel μ = approximately 28% ± 10%) compared to the observations (μ = approximately 30% ± 13%) at the well‐coupled coniferous site (Duke), but poor (intermodel μ = approximately 24% ± 6%; observations μ = approximately 38% ± 7%) at the broadleaf site (Oak Ridge). The study yields a framework for analysing and interpreting model predictions of transpiration responses to eCO 2 , and highlights key improvements to these types of models.

Systematic identification of interaction effects between genome- and environment-wide associations in type 2 diabetes mellitus - Chirag J. Patel; Rong Chen; Keiichi Kodama; John P. A. Ioannidis; Atul J. Butte (Human Genetics, 2013)

Influence of Chemical Reaction on Stability of Thermo-Solutal Convection of Couple-Stress Fluid in a Horizontal Porous Layer - Atul K. Srivastava; P. Bera (Transport in Porous Media, 2013)

DRE-binding transcription factor gene (LlaDREB1b) is regulated by various abiotic stresses in Lepidium latifolium L. - Sanjay Mohan Gupta; Pankaj Pandey; P. S. Negi; V. Pande; Atul Grover; Vikas Y. Patade; Zakwan Ahmed (Molecular Biology Reports, 2013)

Application of Near-Infrared Spectroscopy in Real-Time Monitoring of Product Attributes of Ribbed Roller Compacted Flakes - Asim Kumar Samanta; Atul D. Karande; Ka Yun Ng; Paul Wan Sia Heng (AAPS PharmSciTech, 2013)

Hepatitis E virus from India exhibits significant amino acid mutations in fulminant hepatic failure patients - Nischay Mishra; Atul M. Walimbe; Vidya A. Arankalle (Virus Genes, 2013)

Studies on the life cycle of five microsporidian isolates and histopathology of the mid-gut of the silkworm Bombyx mori (Lepidoptera: Bombycidae) - Zakir Hossain; Sunil Kumar Gupta; Satadal Chakrabarty; Atul Kumar Saha; Bharat Bhushan Bindroo (International Journal of Tropical Insect Science, 2012)

Environmental Monitoring and Health Risk Assessment of African Catfish Clarias gariepinus (Burchell, 1822) Cultured in Rural Ponds, India - Atul K. Singh; Sharad C. Srivastava; Abubakar Ansari; Dinesh Kumar; Ruchi Singh (Bulletin of Environmental Contamination and Toxicology, 2012)

Exploration and characterization of agriculturally and industrially important haloalkaliphilic bacteria from environmental samples of hypersaline Sambhar lake, India - Harmesh Sahay; Sahil Mahfooz; Atul K. Singh; Surendra Singh; Rajeev Kaushik; Anil K. Saxena; Dilip K. Arora (World Journal of Microbiology and Biotechnology, 2012)

Non-steroidal anti-inflammatory drugs (NSAIDs) and hypertension treatment intensification: a population-based cohort study - Jean-Pascal Fournier; Agnès Sommet; Robert Bourrel; Stéphane Oustric; Atul Pathak; Maryse Lapeyre-Mestre; Jean-Louis Montastruc (European Journal of Clinical Pharmacology, 2012)

Phylogenetic footprinting: a boost for microbial regulatory genomics - Pramod Katara; Atul Grover; Vinay Sharma (Protoplasma, 2012)

Female plants of Hippophae salicifolia D. Don are more responsive to cold stress than male plants - Sanjay Mohan Gupta; Atul Grover; Pankaj Pandey; Zakwan Ahmed (Physiology and Molecular Biology of Plants, 2012)

Isolation and characterization of cold responsive NAC gene from Lepidium latifolium - Mohammad Aslam; Atul Grover; Vimlendu Bhushan Sinha; Beenish Fakher; Veena Pande; Patade Vikas Yadav; Sanjay Mohan Gupta; Sivalingam Anandhan; Zakwan Ahmed (Molecular Biology Reports, 2012)

Effect of ring A and ring B substitution on the cytotoxic potential of pyrazole tethered chalcones - Kunal Nepali; Kanika Kadian; Ritu Ojha; Rajni Dhiman; Atul Garg; Gagandip Singh; Abhishek Buddhiraja; Preet Mohinder Singh Bedi; Kanaya Lal Dhar (Medicinal Chemistry Research, 2012)

Antimicrobial screening of novel synthesized benzimidazole nucleus containing 4-oxo-thiazolidine derivatives - N. C. Desai; Amit M. Dodiya; Atul H. Makwana (Medicinal Chemistry Research, 2012)

Synthesis and biological evaluation of naphthalene, furan and pyrrole based chalcones as cytotoxic and antimicrobial agents - Abhishek Budhiraja; Kanika Kadian; Mandeep Kaur; Vikas Aggarwal; Atul Garg; Sameer Sapra; Kunal Nepali; O. P. Suri; K. L. Dhar (Medicinal Chemistry Research, 2012)

One-dimensional solute dispersion along unsteady flow through a heterogeneous medium, dispersion being proportional to the square of velocity - Atul Kumar; Dilip Kumar Jaiswal; Naveen Kumar (Hydrological Sciences Journal, 2012)

Degradation of Fentrazamide Herbicide in Soil Under Aerobic Condition - Shishir Tandon; Atul Pujari; N. K. Sand (Bulletin of Environmental Contamination and Toxicology, 2012)

Antitussive effects of azepino[2,1-b]quinazolones - Kunal Nepali; Mukunda S. Bande; Sameer Sapra; Atul Garg; Sunil Kumar; Punita Sharma; Rohit Goyal; Naresh Kumar Satti; Om Parkash Suri; Kanaya Lal Dhar (Medicinal Chemistry Research, 2012)

Inhibition of HIV-1 Integrase gene expression by 10-23 DNAzyme - Nirpendra Singh; Atul Ranjan; Souvik Sur; Ramesh Chandra; Vibha Tandon (Journal of Biosciences, 2012)

Fluorescence-Based Comparative Evaluation of Bactericidal Potency and Food Application Potential of Anti-listerial Bacteriocin Produced by Lactic Acid Bacteria Isolated from Indigenous Samples - Atul Kumar Singh; Sandipan Mukherjee; Manab Deb Adhikari; Aiyagari Ramesh (Probiotics and Antimicrobial Proteins, 2012)

Three distinct global estimates of historical land-cover change and land-use conversions for over 200 years - Prasanth Meiyappan; Atul K. Jain (Frontiers of Earth Science, 2012)

Erratum to: Agro-economic evaluation of water resource project—a modeling approach - Prashant Thawale; Tarunkanti Ghosh; Sanjeev Kumar Singh; Atul Kulkarni (Environmental Monitoring and Assessment, 2012)

Contribution of anthropogenic aerosols in direct radiative forcing and atmospheric heating rate over Delhi in the Indo-Gangetic Basin - Atul K. Srivastava; Sachchidanand Singh; S. Tiwari; D. S. Bisht (Environmental Science and Pollution Research, 2012)

Expression analysis of MAP2K9 and MAPK6 during pathogenesis of Alternaria blight in Arabidopsis thaliana ecotype Columbia - P. Kannan; Dinesh Pandey; Atul K. Gupta; H. Punetha; Gohar Taj; Anil Kumar (Molecular Biology Reports, 2012)

Agro-economic Evaluation of Water Resource Project – A Modeling Approach - Prashant Thawale; Tarunkanti Ghosh; Sanjiv Singh; Atul Kulkarni (Environmental Monitoring and Assessment, 2012)

Understanding the differential nitrogen sensing mechanism in rice genotypes through expression analysis of high and low affinity ammonium transporter genes - Vikram Singh Gaur; U. S. Singh; Atul K. Gupta; Anil Kumar (Molecular Biology Reports, 2012)

Spatial distribution pattern analysis of Dof1 transcription factor in different tissues of three Eleusine coracana genotypes differing in their grain colour, yield and photosynthetic efficiency - Nidhi Gupta; Atul Kumar Gupta; Anil Kumar (Molecular Biology Reports, 2012)

A Prehospital Acute Coronary Syndrome in a Cocaine User: An Unstable Clinical Situation - Nicolas Franchitto; Claudine Cabot; Nicolas Dumonteil; Vincent Bounes; Atul Pathak; Daniel Rougé (Journal of Medical Toxicology, 2012)

Luminescence Properties of Dual Valence Eu Doped Nano-crystalline BaF2 Embedded Glass-ceramics and Observation of Eu2+ → Eu3+ Energy Transfer - Kaushik Biswas; Atul D. Sontakke; R. Sen; K. Annapurna (Journal of Fluorescence, 2012)

Sex differences in disease risk from reported genome-wide association study findings - Linda Y. Liu; Marc A. Schaub; Marina Sirota; Atul J. Butte (Human Genetics, 2012)

Controlled Release of Modified Insulin Glargine from Novel Biodegradable Injectable Gels - Om Anand; Hassan Almoazen; Nitin Mehrotra; James Johnson; Atul Shukla (AAPS PharmSciTech, 2012)

Improvement of Tablet Coating Uniformity Using a Quality by Design Approach - Atul Dubey; Fani Boukouvala; Golshid Keyvan; Richard Hsia; Kostas Saranteas; Dean Brone; Tushar Misra; Marianthi G. Ierapetritou; Fernando J. Muzzio (AAPS PharmSciTech, 2012)

Searching microsatellites in DNA sequences: approaches used and tools developed - Atul Grover; Veenu Aishwarya; P. C. Sharma (Physiology and Molecular Biology of Plants, 2012)

Role of stochastic forcing in ENSO in observations and a coupled GCM - Atul Kapur; Chidong Zhang; Javier Zavala-Garay; Harry H. Hendon (Climate Dynamics, 2012)

Aerosol characteristics during the coolest June month over New Delhi, northern India - Atul Kumar Srivastava; Suresh Tiwari; Deewan Singh Bisht; Panuganti China Sattilingam Devara; Philippe Goloub; Zhengqiang Li; Manoj K. Srivastava (International Journal of Remote Sensing, 2011)

The influence of a south Asian dust storm on aerosol radiative forcing at a high-altitude station in central Himalayas - Atul K. Srivastava; P. Pant; P. Hegde; Sachchidanand Singh; U. C. Dumka; Manish Naja; Narendra Singh; Y. Bhavanikumar (International Journal of Remote Sensing, 2011)

Prescribed drugs and violence: a case/noncase study in the French PharmacoVigilance Database - Nadège Rouve; Haleh Bagheri; Norbert Telmon; Atul Pathak; Nicolas Franchitto; Laurent Schmitt; Daniel Rougé; Maryse Lapeyre-Mestre; Jean-Louis Montastruc (European Journal of Clinical Pharmacology, 2011)

PAH Composition of Water Based Drilling Mud and Drill Cuttings in the Offshore Region, East Coast of India - Devaanshi Jagwani; Atul Kulkarni; Parth Shukla; Dilip S. Ramteke; Harjeet D. Juneja (Bulletin of Environmental Contamination and Toxicology, 2011)

In silico prediction of drug targets in Vibrio cholerae - Pramod Katara; Atul Grover; Himani Kuntal; Vinay Sharma (Protoplasma, 2011)

Breaking seed dormancy in Hippophae salicifolia, a high value medicinal plant - Sanjay Mohan Gupta; Pankaj Pandey; Atul Grover; Zakwan Ahmed (Physiology and Molecular Biology of Plants, 2011)

Involvement of vascular endothelial nitric oxide synthase in development of experimental diabetic nephropathy in rats - Atul Arya; Harlokesh Naryan Yadav; P. L. Sharma (Molecular and Cellular Biochemistry, 2011)

Analysis of Pharmaceutical Tablet Coating Uniformity by Laser-Induced Breakdown Spectroscopy (LIBS) - Atul Dubey; Golshid Keyvan; Richard Hsia; Kostas Saranteas; Dean Brone; Tushar Misra; Fernando J. Muzzio (Journal of Pharmaceutical Innovation, 2011)

One-dimensional unsteady solute transport along unsteady flow through inhomogeneous medium - SANJAY K YADAV; ATUL KUMAR; DILIP K JAISWAL; NAVEEN KUMAR (Journal of Earth System Science, 2011)

Determination of genetic relationships among elite thermosensitive genic male sterile lines (TGMS) of rice (Oryza sativa L.) employing morphological and simple sequence repeat (SSR) markers - VIKAS KUMAR SINGH; PRITI UPADHYAY; PALLAVI SINHA; ASHISH KUMAR MALL; SANJAY KUMAR JAISWAL; ATUL SINGH; RANJITH KUMAR ELLUR; SUNIL BIRADAR; R. M. SUNDARAM; SUKHPAL SINGH; ILYAS AHMED; B. MISHRA; et al. (Journal of Genetics, 2011)

Differential Expression of PBF Dof Transcription Factor in Different Tissues of Three Finger Millet Genotypes Differing in Seed Protein Content and Color - Nidhi Gupta; Atul Kumar Gupta; N. K. Singh; Anil Kumar (Plant Molecular Biology Reporter, 2011)

Prediction of hybrid performance based on the genetic distance of parental lines in two-line rice (Oryza sativa L.) hybrids - Vikas Kumar Singh; Priti Upadhyay; Pallavi Sinha; Ashish Kumar Mall; Ranjith K. Ellur; Atul Singh; Sanjay K. Jaiswal; Sunil Biradar; S. Ramakrishna; R.M. Sundaram; Ilyas Ahmed; B. C. Viraktamath; et al. (Journal of Crop Science and Biotechnology, 2011)

Risk and benefit assessment of alien fish species of the aquaculture and aquarium trade into India - Atul K. Singh; Wazir S. Lakra (Reviews in Aquaculture, 2011)
There has been an increasing demand for alien fish species in India. However, environmental, socioeconomic and biodiversity issues are important considerations when regulating the unauthorized culture and spread of alien species. Information collected in the present review revealed the presence of over 300 alien species imported intentionally or illegally; 291 ornamental species, 31 aquaculture species and two larvicidal fishes. Field data demonstrated the widespread occurrence of some of the world’s worst invasive species, for example, Cyprinus carpio, Oreochromis niloticus, Aristichthys nobilis, Pygocentrus nattereri and Pterygoplichthys spp., in inland waters; other species are emerging as a threat to aquatic biodiversity. The benefits and risks of alien species were analysed and the impact was quantified using a simple developed ‘Fish Invasiveness Screening Test’ (FIST). Our information suggests that alien species, despite possessing some attractive culture characteristics, generally reduce the availability of local species and establish in natural water bodies becoming invasive and consequently adversely affecting fish biodiversity and aquatic ecosystems. In light of the adverse ecological impacts of alien species, we developed strategic regulations and quarantine procedures and advised aquaculturists to strictly follow them to contain potential and plausible menaces.

Expedient synthesis of some novel pregnane derivatives and their evaluation as anti-oxidant and anti-dyslipidemic agents - Arun Sethi; Gitika Bhatia; Ashok K. Khanna; Mohammad Mobin Khan; Abha Bishnoi; Anil K. Pandey; Atul Maurya (Medicinal Chemistry Research, 2011)

Development of EST-based new SSR markers in seabuckthorn - Ankit Jain; Rajesh Ghangal; Atul Grover; Saurabh Raghuvanshi; Prakash C. Sharma (Physiology and Molecular Biology of Plants, 2010)

Coal fly ash utilization in agriculture: its potential benefits and risks - Rajeev Pratap Singh; Amit K. Gupta; M. Hakimi Ibrahim; Atul Kumar Mittal (Reviews in Environmental Science and Bio/Technology, 2010)

Novel mutation in ATP-binding domain of ABCD1 gene in adrenoleucodystrophy - Neeraj Kumar; Krishna K. Taneja; Atul Kumar; Deepti Nayar; Bhupesh Taneja; Satindra Aneja; Madhuri Behari; Veena Kalra; Surendra K. Bansal (Journal of Genetics, 2010)

Biochemical and molecular characterization of thermo-alkali tolerant xylanase producing bacteria from thermal springs of Manikaran - Atul K. Singh; B. M. Tripathi; Harmesh Sahay; R. N. Singh; Rajeev Kaushik; A. K. Saxena; D. K. Arora (Indian Journal of Microbiology, 2010)

Seismotectonic zones demarcation in the Shillong Plateau using the microearthquakes and radon emanation rate - Devesh Walia; Andrew C. Lyngdoh; Atul Saxena (Acta Geophysica, 2010)

Performance of Low Energy Water Application Device - Atul Kumar Singh; S. P. Sharma; A. Upadhyaya; A. Rahman; A. K. Sikka (Water Resources Management, 2010)

Diversity-oriented synthesis of benzimidazole, benzoxazole, benzothiazole and quinazolin-4(3H)-one libraries via potassium persulfate–CuSO4-mediated oxidative coupling reactions of aldehydes in aqueous micelles - Atul Kumar; Ram Awatar Maurya; Deepti Saxena (Molecular Diversity, 2010)

Synthesis, in vitro antitubercular activity and 3D-QSAR study of 1,4-dihydropyridines - Atul T. Manvar; Raghuvir R. S. Pissurlenkar; Vijay R. Virsodia; Kuldip D. Upadhyay; Dinesh R. Manvar; Arun K. Mishra; Hrishikesh D. Acharya; Alpesh R. Parecha; Chintan D. Dholakia; Anamik K. Shah; Evans C. Coutinho (Molecular Diversity, 2010)

Novel strategies for the treatment of inflammatory hyperalgesia - Atul R. Chopade; Wahid A. Mulla (European Journal of Clinical Pharmacology, 2010)

Enteroaggregative Escherichia coli infection induces IL-8 production via activation of mitogen-activated protein kinases and the transcription factors NF-κB and AP-1 in INT-407 cells - Krishnendu Khan; Monica Konar; Atul Goyal; Sujata Ghosh (Molecular and Cellular Biochemistry, 2010)

In vivo evaluation of substituted 3-phenyl,7-methoxy-benzopyrans as modified estrogens - Atul Gupta; Govind Keshri; M. M. Singh; Suprabhat Ray (Medicinal Chemistry Research, 2010)

Time Resolved Fluorescence and Energy Transfer Analysis of Nd3+–Yb3+–Er3+ Triply-Doped Ba–Al-Metaphosphate Glasses for an Eye Safe Emission (1.54 μm) - Atul D. Sontakke; Kaushik Biswas; Ashis K. Mandal; Kalyandurg Annapurna (Journal of Fluorescence, 2010)

Identification of biomarker for determining genotypic potential of nitrogen-use-efficiency and optimization of the nitrogen inputs in crop plants - Anil Kumar; Nidhi Gupta; Atul Kumar Gupta; Vikram Singh Gaur (Journal of Crop Science and Biotechnology, 2009)

Brewing trouble: coffee invasion in relation to edges and forest structure in tropical rainforest fragments of the Western Ghats, India - Atul Arvind Joshi; Divya Mudappa; T. R. Shankar Raman (Biological Invasions, 2009)

Biochemical responses in tree foliage exposed to coal-fired power plant emission in seasonally dry tropical environment - Atul Prakash Sharma; B. D. Tripathi (Environmental Monitoring and Assessment, 2009)

Development of microsatellite markers in potato and their transferability in some members of Solanaceae - Atul Grover; B. Ramesh; P. C. Sharma (Physiology and Molecular Biology of Plants, 2009)

Analytical solutions of one-dimensional advection-diffusion equation with variable coefficients in a finite domain - Atul Kumar; Dilip Kumar Jaiswal; Naveen Kumar (Journal of Earth System Science, 2009)

Endpoints and Analyses to Discern Disease-Modifying Drug Effects in Early Parkinson’s Disease - Venkatesh Atul Bhattaram; Ohidul Siddiqui; Leonard P. Kapcala; Jogarao V. S. Gobburu (The AAPS Journal, 2009)

Quantitative effect and regulatory function of cyclic adenosine 5′-phosphate in Escherichia coli - Atul Narang (Journal of Biosciences, 2009)

Genome-wide analysis of conservation and divergence of microsatellites in rice - Manish Roorkiwal; Atul Grover; Prakash C. Sharma (Molecular Genetics and Genomics, 2009)

Efficiency evaluation of sewage treatment plants with different technologies in Delhi (India) - Priyanka Jamwal; Atul K. Mittal; Jean-Marie Mouchel (Environmental Monitoring and Assessment, 2009)

Development and Evaluation of Sustained Release Gastroretentive Minimatrices for Effective Treatment of H. pylori Infection - Atul C. Badhan; Rajashree C. Mashru; Punit P. Shah; Arti R. Thakkar; Nitin B. Dobaria (AAPS PharmSciTech, 2009)

Effect of Ions on Agitation- and Temperature-Induced Aggregation Reactions of Antibodies - R. Matthew Fesinmeyer; Sabine Hogan; Atul Saluja; Stephen R. Brych; Eva Kras; Linda O. Narhi; David N. Brems; Yatin R. Gokarn (Pharmaceutical Research, 2009)

The arbuscular mycorrhizal symbiosis links N mineralization to plant demand - A. Atul-Nayyar; C. Hamel; K. Hanson; J. Germida (Mycorrhiza, 2009)

Black carbon and chemical characteristics of PM10 and PM2.5 at an urban site of North India - Suresh Tiwari; Atul K. Srivastava; Deewan S. Bisht; Tarannum Bano; Sachchidanand Singh; Sudhamayee Behura; Manoj K. Srivastava; D. M. Chate; B. Padmanabhamurty (Journal of Atmospheric Chemistry, 2009)

In vivo evaluation of substituted 2,3-diaryl acrylophenone amide derivatives as anti-implantation agents - Atul Gupta; Govind Keshri; M. M. Singh; Suprabhat Ray (Medicinal Chemistry Research, 2009)

Assessment of atmospheric PAHs profile through Calotropis gigantea R.Br. leaves in the vicinity of an Indian coal-fired power plant - Atul Prakash Sharma; B. D. Tripathi (Environmental Monitoring and Assessment, 2009)

Small Holders’ Irrigation—Problems and Options - Atul Kumar Singh; A. Rahman; S. P. Sharma; A. Upadhyaya; A. K. Sikka (Water Resources Management, 2009)

Anion Binding Mediated Precipitation of a Peptibody - Atul Saluja; Shon Crampton; Eva Kras; R. Matthew Fesinmeyer; Richard L. Remmele; Linda O. Narhi; David N. Brems; Yatin R. Gokarn (Pharmaceutical Research, 2009)

Thioflavin T Displays Enhanced Fluorescence Selectively Inside Anionic Micelles and Mammalian Cells - Satish Kumar; Atul K. Singh; G. Krishnamoorthy; Rajaram Swaminathan (Journal of Fluorescence, 2008)

Hydraulic response of a tidally forced coastal aquifer, Pontal do Paraná, Brazil - D. S. Suresh Babu; Atul Kumar Sahai; Mauricio Almeida Noernberg; Eduardo Marone (Hydrogeology Journal, 2008)

Scientific Perceptions and Community Responses in a Participatory Water Management Endeavor - Atul Kumar Singh; A. K. Sikka; A. Upadhyaya; P. R. Bhatnagar; S. Dhanphule; M. K. Singh; S. R. Singh (Water Resources Management, 2008)

Learning about the ocean carbon cycle from observational constraints and model simulations of multiple tracers - Long Cao; Atul K. Jain (Climatic Change, 2008)

Magnetic mapping of fly-ash pollution and heavy metals from soil samples around a point source in a dry tropical environment - Atul Prakash Sharma; B. D. Tripathi (Environmental Monitoring and Assessment, 2008)

Chenopodium: a prospective plant for phytoextraction - Atul Bhargava; Sudhir Shukla; Jatin Srivastava; Nandita Singh; Deepak Ohri (Acta Physiologiae Plantarum, 2007)

Monitoring of Pathogenicity of Effluents from the UASB Based Sewage Treatment Plant - Anju Pant; Atul K. Mittal (Environmental Monitoring and Assessment, 2007)

RETRACTED ARTICLE: Engineered Polyallylamine Nanoparticles for Efficient In Vitro Transfection - Atul Pathak; Anita Aggarwal; Raj K. Kurupati; Soma Patnaik; Archana Swami; Yogendra Singh; Pradeep Kumar; Suresh P. Vyas; Kailash C. Gupta (Pharmaceutical Research, 2007)

Biased distribution of microsatellite motifs in the rice genome - Atul Grover; Veenu Aishwarya; P. C. Sharma (Molecular Genetics and Genomics, 2007)

Gynomonoecy in Chenopodium quinoa (Chenopodiaceae): variation in inflorescence and floral types in some accessions - Atul Bhargava; Sudhir Shukla; Deepak Ohri (Biologia, 2007)

Evaluation of foliage yield and leaf quality traits in Chenopodium spp. in multiyear trials - Atul Bhargava; Sudhir Shukla; Deepak Ohri (Euphytica, 2007)

Molecular cloning, stable expression and cellular localization of human α1-adrenergic receptor subtypes: effect of charcoal/dextran treated serum on expression and localization of α1D -adrenergic receptor - Sunil K. Khattar; Roop Singh Bora; Priyanka Priyadarsiny; Aarti Gautam; Dikshi Gupta; Atul Tiwari; Kamna Nanda; Rahul Singh; Anita Chugh; Vinay Bansal; Kasim Mookhtiar; Kulvinder Singh Saini (Biotechnology Letters, 2006)

Deterioration in sugarcane due to pokkah boeng disease - Atul Singh; S. S. Chauhan; Aneg Singh; S. B. Singh (Sugar Tech, 2006)

Formulation and in vitro, in vivo evaluation of extended- release matrix tablet of Zidovudine: Influence of combination of hydrophilic and hydrophobic matrix formers - Atul Kuksal; Ashok K. Tiwary; Narendra K. Jain; Subheet Jain (AAPS PharmSciTech, 2006)

Genomic distribution of genes encoding 68 cytoplasmic ribosomal protein families in rice - Subhash Mohan Agarwal; Mukesh Jain; Atul Grover (Acta Physiologiae Plantarum, 2005)

Adverse drug reactions related to drugs used in orthostatic hypotension: a prospective and systematic pharmacovigilance study in France - Atul Pathak; Valérie Raoul; Jean-Louis Montastruc; Jean-Michel Senard (European Journal of Clinical Pharmacology, 2005)

Role and differential expression of calpastatin mRNA and protein in cultured cardiomyocytes exposed to hypoxic stress - Huey Lin; Milish P. Risbood; Atul Jain; Victor Vacanti; Techung Lee (Molecular and Cellular Biochemistry, 2004)

Measurement of fluid viscosity at microliter volumes using quartz impedance analysis - Atul Saluja; Devendra S. Kalonia (AAPS PharmSciTech, 2004)

Carbon Management Response Curves: Estimates of Temporal Soil Carbon Dynamics - Tristram O. West; Gregg Marland; Anthony W. King; Wilfred M. Post; Atul K. Jain; Kenneth Andrasko (Environmental Management, 2004)

Recent insights on biochemical and molecular basis for developing antihaemostatic agents: A review - Rahat Kumar; Narinder Singh; Kartar Singh; Atul Kalhan; K. K. Prasad (Indian Journal of Clinical Biochemistry, 2004)

Substitution of Natural Gas for Coal: Climatic Effects of Utility Sector Emissions - Katharine Hayhoe; Haroon S. Kheshgi; Atul K. Jain; Donald J. Wuebbles (Climatic Change, 2002)

Effect of collection date on capsule moisture content and germination of Populus ciliata Wall. ex Royle from central Himalaya - Atul Pandit; Kavita Pant; Jeet Ram (New Forests, 2002)

The tylosin-biosynthetic genes of Streptomyces fradiae - Eric Cundliffe; Neil Bate; Andrew Butler; Steven Fish; Atul Gandecha; Louise Merson-Davies (Antonie van Leeuwenhoek, 2001)

A Mathematical Model for Chemoattractant Gradient Sensing Based on Receptor-Regulated Membrane Phospholipid Signaling Dynamics - Atul Narang; K. K. Subramanian; D. A. Lauffenburger (Annals of Biomedical Engineering, 2001)

Impacts on Global Ozone and Climate from Use and Emission of 2,2-Dichloro-1,1,1-Trifluoroethane (HCFC-123) - James M. Calm; Donald J. Wuebbles; Atul K. Jain (Climatic Change, 1999)

Degradation of alpha, beta, gamma and delta-hexachlorocyclohexanes by Sphingomonas paucimobilis - Atul K. Johri; Meenakshi Dua; Dipika Tuteja; Renu Saxena; D.M. Saxena; Rup Lal (Biotechnology Letters, 1998)

The cholecystokinin-B receptor antagonist CI-988 failed to affect CCK-4 induced symptoms in panic disorder patients - Harold J. G. M. van Megen; Herman G. M. Westenberg; Johan A. den Boer; Bernard Slaap; Fenny van Es-Radhakishun; Atul C. Pande (Psychopharmacology, 1997)

Statistical analysis of the envelope gene and the prM region of Japanese encephalitis virus: Evidence suggestive of positive selection - Shirish Paranjpe; Atul Walimbe; K. Banerjee (Journal of Genetics, 1997)